Absolute quantification of DcR3 and GDF15 from human serum by LC-ESI MS - Lancrajan, Ioana Maria; Schneider-Stock, Regine; Naschberger, Elisabeth; Schellerer, Vera; Stürzl, Michael; Enz, Ralf (Journal of Cellular and Molecular Medicine, 2015)
Biomarkers are widely used in clinical diagnosis, prognosis and therapy monitoring. Here, we developed a protocol for the efficient and selective enrichment of small and low concentrated biomarkers from human serum, involving a 95% effective depletion of high-abundant serum proteins by partial denaturation and enrichment of low-abundant biomarkers by size exclusion chromatography. The recovery of low-abundance biomarkers was above 97%. Using this protocol, we quantified the tumour markers DcR3 and growth/differentiation factor (GDF)15 from 100 ?l human serum by isotope dilution mass spectrometry, using (15) N metabolically labelled and concatamerized fingerprint peptides for the both proteins. Analysis of three different fingerprint peptides for each protein by liquid chromatography electrospray ionization mass spectrometry resulted in comparable concentrations in three healthy human serum samples (DcR3: 27.23 ± 2.49 fmol/ml; GDF15: 98.11 ± 0.49 fmol/ml). In contrast, serum levels were significantly elevated in tumour patients for DcR3 (116.94 ± 57.37 fmol/ml) and GDF15 (164.44 ± 79.31 fmol/ml). Obtained data were in good agreement with ELISA and qPCR measurements, as well as with literature data. In summary, our protocol allows the reliable quantification of biomarkers, shows a higher resolution at low biomarker concentrations than antibody-based strategies, and offers the possibility of multiplexing. Our proof-of-principle studies in patient sera encourage the future analysis of the prognostic value of DcR3 and GDF15 for colon cancer patients in larger patient cohorts.
EVALuna2:4708

Activation of matrix-metalloproteinase-2 and membrane-type-1-matrix-metalloproteinase in endothelial cells and induction of vascular permeability in vivo by human immunodeficiency virus-1 Tat protein and basic fibroblast growth factor. - Tosch, Elena; Barillari, Giovanni; Sgadari, Cecilia; Bacigalupo, Ilaria; Cereseto, Anna; Carlei, Davide; Palladino, Clelia; Zietz, Christian; Leone, Patrizia; Stürzl, Michael; Buttò, Stefano; Cafaro, Aurelio; et al. (Molecular Biology of the Cell, 2001)
Previous studies indicated that the Tat protein of human immunodeficiency virus type-1 (HIV-1) is a progression factor for Kaposi's sarcoma (KS). Specifically, extracellular Tat cooperates with basic fibroblast growth factor (bFGF) in promoting KS and endothelial cell growth and locomotion and in inducing KS-like lesions in vivo. Here we show that Tat and bFGF combined increase matrix-metalloproteinase-2 (MMP-2) secretion and activation in endothelial cells in an additive/synergistic manner. These effects are due to the activation of the membrane-type-1-matrix-metalloproteinase and to the induction of the membrane-bound tissue inhibitor of metalloproteinase-2 (TIMP-2) by Tat and bFGF combined, but also to Tat-mediated inhibition of both basal or bFGF-induced TIMP-1 and -2 secretion. Consistent with this, Tat and bFGF promote vascular permeability and edema in vivo that are blocked by a synthetic MMP inhibitor. Finally, high MMP-2 expression is detected in acquired immunodeficiency virus syndrome (AIDS)-KS lesions, and increased levels of MMP-2 are found in plasma from patients with AIDS-KS compared with HIV-uninfected individuals with classic KS, indicating that these mechanisms are operative in AIDS-KS. This suggests a novel pathway by which Tat can increase KS aggressiveness or induce vasculopathy in the setting of HIV-1 infection.

Activation of NF-κB by the Kaposi's sarcoma-associated herpesvirus K15 protein involves recruitment of the NF-κB-inducing kinase, IκB kinases, and phosphorylation of p65. - Havemeier, Anika; Gramolelli, Silvia; Pietrek, Marcel; Jochmann, Ramona; Stürzl, Michael; Schulz, Thomas F. (Journal of Virology, 2014)
Kaposi's sarcoma herpesvirus (KSHV) (or human herpesvirus 8) is the cause of Kaposi's sarcoma, primary effusion lymphoma (PEL), and the plasma cell variant of multicentric Castleman's disease (MCD). The transmembrane K15 protein, encoded by KSHV, has been shown to activate NF-κB and the mitogen-activated protein kinases (MAPKs) c-jun-N-terminal kinase (JNK) and extracellular signal-regulated kinase (Erk) as well as phospholipase C gamma (PLCγ) and to contribute to KSHV-induced angiogenesis. Here we investigate how the K15 protein activates the NF-κB pathway. We show that activation of NF-κB involves the recruitment of NF-κB-inducing kinase (NIK) and IKK α/β to result in the phosphorylation of p65/RelA on Ser536. A K15 mutant devoid in NIK/IKK recruitment fails to activate NF-κB but remains proficient in the stimulation of both NFAT- and AP1-dependent promoters, showing that the structural integrity of the mutant K15 protein has not been altered dramatically. Direct recruitment of NIK represents a novel way for a viral protein to activate and manipulate the NF-κB pathway. KSHV K15 is a viral protein involved in the activation of proinflammatory and angiogenic pathways. Previous studies reported that K15 can activate the NF-κB pathway. Here we show the molecular mechanism underlying the activation of this signaling pathway by K15, which involves direct recruitment of the NF-κB-inducing kinase NIK to K15 as well as NIK-mediated NF-κB p65 phosphorylation on Ser536. K15 is the first viral protein shown to activate NF-κB through direct recruitment of NIK. These results indicate a new mechanism whereby a viral protein can manipulate the NF-κB pathway. UNLABELLED IMPORTANCE
EVALuna2:15180

Alpha interferon inhibits human herpesvirus 8 (HHV-8) reactivation in primary effusion lymphoma cells and reduces HHV-8 load in cultured peripheral blood mononuclear cells. - Monini, Paolo; Carlini, Francesca; Stürzl, Michael; Rimessi, Paola; Superti, Fabiana; Franco, Marina; Melucci-Vigo, Gianna; Cafaro, Aurelio; Goletti, Delia; Sgadari, Cecilia; Buttò, Stefano; Leone, Patrizia; et al. (Journal of Virology, 1999)
Infection by human herpesvirus 8 (HHV-8) is associated with the development of Kaposi's sarcoma (KS). Since regression of KS can be achieved by treatment of the patients with alpha interferon (IFN-alpha), we analyzed the effects of IFN-alpha or anti-IFN-alpha antibodies (Ab) on HHV-8 latently infected primary effusion lymphoma-derived cell lines (BCBL-1 and BC-1) and on peripheral blood mononuclear cells (PBMC) from patients with all forms of KS and from at-risk subjects. IFN-alpha inhibited in a dose-dependent manner the amplification of HHV-8 DNA in BCBL-1 cells induced to lytic infection with tetradecanoyl phorbol acetate (TPA). This effect was associated with the inhibition of the expression of HHV-8 nut-1 and kaposin genes that are induced early and several hours, respectively, after TPA treatment. In addition, IFN-alpha inhibited virus production and/or release from BCBL-1 cells. Inhibition of nut-1 and kaposin genes by IFN-alpha was also observed in BC-1 cells induced with n-butyrate. Conversely, the addition of anti-IFN-alpha Ab to TPA-induced BCBL-1 cells resulted in a larger number of mature enveloped particles and in a more extensive cytopathic effect due to the neutralization of the endogenous IFN produced by these cells. IFN was also produced by cultured PBMC from HHV-8-infected individuals, and this was associated with a loss of viral DNA during culture. However, the addition of anti-IFN-alpha Ab or anti-type I IFN receptor Ab promoted the maintenance of HHV-8 DNA in these cells that was associated with the detection of the latency-associated kaposin RNA. Finally, the addition of IFN-alpha reduced the HHV-8 load in PBMC. Thus, IFN-alpha appears to have inhibitory effects on HHV-8 persistent infection of PBMC. These results suggest that, in addition to inhibiting the expression of angiogenic factors that are key to KS development, IFN-alpha may induce KS regression by reducing the HHV-8 load and/or inhibiting virus reactivation.

AMIGO2 characterizes cancer-associated fibroblasts in metastatic colon cancer and induces the release of paracrine active tumorigenic secretomes - Yong, Yong-song; Demmler, Richard; Zohud, Bisan; Fang, Qi; Zhang, Tong; Zhou, Yonghua; Petter, Katja; Flierl, Christian; Gass, Tobias; Geppert, Carol-Immanuel; Merkel, Susanne; Schellerer, Vera; et al. (Journal of Pathology, 2024)
Secretomes of cancer-associated fibroblasts (CAFs) in colorectal cancer (CRC) contribute to malignancy. Detailed knowledge is available on the components and functions of CAF secretomes. Little is known about the regulation of CAF secretomes. Here, we searched for receptor-like membrane-bound molecules in CAFs, which may regulate the production and release of tumor-activating secretomes. The adhesion molecule with Ig-like domain 2 (AMIGO2) was significantly upregulated in cultivated CAFs compared to normal tissue-associated fibroblasts (NAFs), and this was confirmed in patient-derived tissues. AMIGO2 expression was low or absent in healthy colon, significantly increased in fibroblasts of primary CRC, and highest in the stromal tissues of CRC-derived liver metastases. AMIGO2 expression in CAFs correlated with a higher T-category, increased lymph node metastasis, progressed tumor stages and was associated with reduced survival in different cohorts of CRC patients. Interestingly, AMIGO2 expression was induced by transforming growth factor-β and higher in female patients, who exhibit a more aggressive disease course. In functional studies, conditioned media of NAFs with experimentally induced AMIGO2 overexpression enhanced proliferation and migration of different CRC tumor cells, while siRNA-mediated inhibition of AMIGO2 in CAFs attenuated these effects. Accordingly, therapeutic inhibition of the receptor-like AMIGO2 protein in CRC CAFs could prevent tumorigenic secretomes in CRC. © 2024 The Author(s). The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.
CRIS-Team Scopus Importer:2024-11-22
Keywords: cancer-associated fibroblasts; colorectal cancer; secretion; secretomes; tumor microenvironment

Analysis of the interferon-γ-induced secretome of intestinal endothelial cells: putative impact on epithelial barrier dysfunction in IBD - Naschberger, Elisabeth; Flierl, Christian; Huang, Jinghao; Erkert, Lena; Gámez Belmonte, Maria de los Reyes; Gonzalez Acera, Miguel; Bober, Magdalena; Mehnert, Martin; Becker, Christoph; Schellerer, Vera S.; Britzen-Laurent, Nathalie; Stürzl, Michael (Frontiers in Cell and Developmental Biology, 2023)
The development of inflammatory bowel diseases (IBD) involves the breakdown of two barriers: the epithelial barrier and the gut-vascular barrier (GVB). The destabilization of each barrier can promote initiation and progression of the disease. Interestingly, first evidence is available that both barriers are communicating through secreted factors that may accordingly serve as targets for therapeutic modulation of barrier functions. Interferon (IFN)-γ is among the major pathogenesis factors in IBD and can severely impair both barriers. In order to identify factors transmitting signals from the GVB to the epithelial cell barrier, we analyzed the secretome of IFN-γ-treated human intestinal endothelial cells (HIEC). To this goal, HIEC were isolated in high purity from normal colon tissues. HIEC were either untreated or stimulated with IFN-γ (10 U/mL). After 48 h, conditioned media (CM) were harvested and subjected to comparative hyper reaction monitoring mass spectrometry (HRM™ MS). In total, 1,084 human proteins were detected in the HIEC-CM. Among these, 43 proteins were present in significantly different concentrations between the CM of IFN-γ- and control-stimulated HIEC. Several of these proteins were also differentially expressed in various murine colitis models as compared to healthy animals supporting the relevance of these proteins secreted by inflammatory activated HIEC in the inter-barrier communication in IBD. The angiocrine pathogenic impact of these differentially secreted HIEC proteins on the epithelial cell barrier and their perspectives as targets to treat IBD by modulation of trans-barrier communication is discussed in detail.
CRIS-Team Scopus Importer:2023-09-08
Keywords: angiocrine; barrier; cytokines; endothelial; IBD-inflammatory bowel disease; interferon; paracrine; secretion

Angiocrine Regulation of Epithelial Barrier Integrity in Inflammatory Bowel Disease - Stürzl, Michael; Kunz, Meik; Krug, Susanne M.; Naschberger, Elisabeth (Frontiers in Medicine, 2021)
Inflammatory bowel disease describes chronic inflammatory disorders. The incidence of the disease is rising. A major step in disease development is the breakdown of the epithelial cell barrier. Numerous blood vessels are directly located underneath this barrier. Diseased tissues are heavily vascularized and blood vessels significantly contribute to disease progression. The gut-vascular barrier (GVB) is an additional barrier controlling the entry of substances into the portal circulation and to the liver after passing the first epithelial barrier. The presence of the GVB rises the question, whether the vascular and endothelial barriers may communicate bi-directionally in the regulation of selective barrier permeability. Communication from epithelial to endothelial cells is well-accepted. In contrast, little is known on the respective backwards communication. Only recently, perfusion-independent angiocrine functions of endothelial cells were recognized in a way that endothelial cells release specific soluble factors that may directly act on the epithelial barrier. This review discusses the putative involvement of angiocrine inter-barrier communication in the pathogenesis of IBD.
CRIS-Team Scopus Importer:2021-08-27
Keywords: angiocrine; angiogenesis; barrier; endothelial; epithelial; inflammation; inflammatory bowel disease

Angiostatic immune reaction in colorectal carcinoma: Impact on survival and perspectives for antiangiogenic therapy - Naschberger, Elisabeth; Croner, Roland S.; Merkel, Susanne; Dimmler, Arno; Tripal, Philipp; Amann, Kerstin Ute; Kremmer, Elisabeth; Brueckl, Wolfgang M.; Papadopoulos, Thomas; Hohenadl, Christine; Hohenberger, Werner; Stürzl, Michael (International Journal of Cancer, 2008)
Angiogenesis and inflammation are the 2 major stroma reactions in colorectal carcinoma (CRC). Guanylate binding protein-1 (GBP-1) is a key mediator of angiostatic effects of inflammation. Therefore, we hypothesized that GBP-1 may be a biomarker of intrinsic angiostasis associated with an improved outcome in CRC patients. GBP-1 was strongly expressed in endothelial cells and immune cells in the desmoplastic stroma of 32% of CRC as determined by immunohistochemical investigation of 388 sporadic CRC. Cancer-related 5-year survival was highly significant (p < 0.001) increased (16.2%) in patients with GBP-1-positive CRC. Multivariate analysis showed that GBP-1 is an independent prognostic factor indicating a reduction of the relative risk of cancer-related death by the half (p = 0.032). A comparative transcriptome analysis (22,215 probe sets) of GBP-1-positive (n = 12) and -negative (n = 12) tumors showed that particularly IFN-γ-induced genes including the major antiangiogenic chemokines CXCL9, CXCL10 and CXCL11 were coexpressed with GBP-1. Altogether our findings indicated that GBP-1 may be a novel biomarker and an active component of a Th-1-like angiostatic immune reaction in CRC. This reaction may affect patient's response to antiangiogenic therapy and the identification of such tumors may provide a novel criterion for patient selection. Moreover, the induction of a Th-1-like angiostatic immune reaction may be a promising approach for the clinical treatment of CRC. © 2008 Wiley-Liss, Inc.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Colorectal carcinoma; Guanylate binding protein-1; Inflammation; Interferon-γ

A novel chip-based parallel transfection assay to evaluate paracrine cell interactions - Kühn, Elisabeth; Naschberger, Elisabeth; Konrad, Andreas; Croner, Roland S.; Britzen-Laurent, Nathalie; Jochmann, Ramona; Münstedt, Helmut; Stürzl, Michael (Lab on A Chip, 2012)
Created from Fastlane, Scopus look-up

Anti-DNA-IgM Favors the Detection of NET-Associated Extracellular DNA - Wang, Han; Stehr, Antonia; Singh, Jeeshan; Zlatar, Leticija; Hartmann, Arndt; Evert, Katja; Naschberger, Elisabeth; Von Stillfried, Saskia; Boor, Peter; Munoz, Luis Enrique; Knopf, Jasmin; Stürzl, Michael; et al. (International Journal of Molecular Sciences, 2023)
During inflammatory responses, neutrophils enter the sites of attack where they execute various defense mechanisms. They (I) phagocytose microorganisms, (II) degranulate to release cytokines, (III) recruit various immune cells by cell-type specific chemokines, (IV) secrete anti-microbials including lactoferrin, lysozyme, defensins and reactive oxygen species, and (V) release DNA as neutrophil extracellular traps (NETs). The latter originates from mitochondria as well as from decondensed nuclei. This is easily detected in cultured cells by staining of DNA with specific dyes. However, in tissues sections the very high fluorescence signals emitted from the condensed nuclear DNA hamper the detection of the widespread, extranuclear DNA of the NETs. In contrast, when we employ anti-DNA-IgM antibodies, they are unable to penetrate deep into the tightly packed DNA of the nucleus, and we observe a robust signal for the extended DNA patches of the NETs. To validate anti-DNA-IgM, we additionally stained the sections for the NET-markers histone H2B, myeloperoxidase, citrullinated histone H3, and neutrophil elastase. Altogether, we have described a fast one-step procedure for the detection of NETs in tissue sections, which provides new perspectives to characterize neutrophil-associated immune reactions in disease.
CRIS-Team Scopus Importer:2023-03-10
Keywords: anti-DNA-IgM; extracellular DNA; NETs

A possible role for interferon-alpha and activated natural killer cells in remission of AIDS-related Kaposi's sarcoma: in vitro studies. - Reiter, Z; Ozés, O N; Blatt, L M; Stürzl, Michael; Taylor, M W (Journal of Acquired Immune Deficiency Syndromes, 1992)
The effect of consensus interferon-alpha on the growth of AIDS-related Kaposi's sarcoma-derived cells was studied. Interferon caused a low but significant in vitro inhibition of cell growth. Whereas Kaposi's sarcoma cells were resistant to the cytotoxic effect of natural killer (NK) cells, treatment of NK cells with either interferon or interleukin-2 activated the cell-mediated cytotoxic response. Pretreatment of the Kaposi's sarcoma cells with interferon reduced their sensitivity to interferon-primed natural killer cell or lymphokine (interleukin-2)-activated killer (LAK) cell cytotoxicity. The resistance of Kaposi's sarcoma cells to NK cell-mediated cytotoxicity did not reside in conjugate formation but was due to an inability of Kaposi's sarcoma cells to induce NK cytotoxic factor. Although interferon reduces the sensitivity of Kaposi's sarcoma cells to interferon-primed NK cell and LAK cell activities, the level of natural killing susceptibility remained significantly higher than the poor sensitivity of Kaposi's sarcoma cells to unprimed NK cell activity. Thus, the potential antitumor effect of interferon against Kaposi's sarcoma cells could be mediated both directly (antiproliferative) and/or indirectly by activation of NK cells.

Application of machine learning algorithms for multiparametric MRI-based evaluation of murine colitis - Ellmann, Stephan; Langer, Victoria; Britzen-Laurent, Nathalie; Hildner, Kai; Huber, Carina; Tripal, Philipp; Seyler, Lisa; Waldner, Maximilian; Uder, Michael; Stürzl, Michael; Bäuerle, Tobias (PLoS ONE, 2018)
Magnetic resonance imaging (MRI) allows non-invasive evaluation of inflammatory bowel disease (IBD) by assessing pathologically altered gut. Besides morphological changes, relaxation times and diffusion capacity of involved bowel segments can be obtained by MRI. The aim of this study was to assess the use of multiparametric MRI in the diagnosis of experimentally induced colitis in mice, and evaluate the diagnostic benefit of parameter combinations using machine learning. This study relied on colitis induction by Dextran Sodium Sulfate (DSS) and investigated the colon of mice in vivo as well as ex vivo. Receiver Operating Characteristics were used to calculate sensitivity, specificity, positive- and negative-predictive values (PPV and NPV) of these single values in detecting DSS-treatment as a reference condition. A Model Averaged Neural Network (avNNet) was trained on the multiparametric combination of the measured values, and its predictive capacity was compared to those of the single parameters using exact binomial tests. Within the in vivo subgroup (n = 19), the avNNet featured a sensitivity of 91.3% (95% CI: 86.6-96.0%), specificity of 92.3% (95% CI: 85.1-99.6%), PPV of 96.9% (94.0-99.9%) and NPV of 80.0% (95% CI: 69.9-90.1%), significantly outperforming all single parameters in at least 2 accuracy measures (p < 0.003) and performing significantly worse compared to none of the single values. Within the ex vivo subgroup (n = 30), the avNNet featured a sensitivity of 87.4% (95% CI: 82.6-92.2%), specificity of 82.9% (95% CI: 76.1-89.7%), PPV of 88.9% (84.3-93.5%) and NPV of 80.8% (95% CI: 73.8-87.9%), significantly outperforming all single parameters in at least 2 accuracy measures (p < 0.015), exceeded by none of the single parameters. In experimental mouse colitis, multiparametric MRI and the combination of several single measured values to an avNNet can significantly increase diagnostic accuracy compared to the single parameters alone. This pilot study will provide new avenues for the development of an MR-derived colitis score for optimized diagnosis and surveillance of inflammatory bowel disease.
EVALuna2:35135

A role for MALT1 activity in Kaposi's sarcoma-associated herpes virus latency and growth of primary effusion lymphoma - Bonsignore, L.; Passelli, K.; Pelzer, C.; Perroud, M.; Konrad, A.; Thurau, Mathias; Stürzl, Michael; Dai, L.; Trillo-Tinoco, Jimena; Del Valle, L.; Qin, Z.; Thome, Margot (Leukemia, 2017)
Primary effusion lymphoma (PEL) is an incurable malignancy that develops in immunodeficient patients as a consequence of latent infection of B-cells with Kaposi's sarcoma-associated herpes virus (KSHV). Malignant growth of KSHV-infected B cells requires the activity of the transcription factor nuclear factor (NF)-?B, which controls maintenance of viral latency and suppression of the viral lytic program. Here we show that the KSHV proteins K13 and K15 promote NF-?B activation via the protease mucosa-associated lymphoid tissue lymphoma translocation protein-1 (MALT1), a key driver of NF-?B activation in lymphocytes. Inhibition of the MALT1 protease activity induced a switch from the latent to the lytic stage of viral infection, and led to reduced growth and survival of PEL cell lines in vitro and in a xenograft model. These results demonstrate a key role for the proteolytic activity of MALT1 in PEL, and provide a rationale for the pharmacological targeting of MALT1 in PEL therapy.
EVALuna2:15308

A systems biology approach to identify the combination effects of human herpesvirus 8 genes on NF-κB activation - Konrad, Andreas; Wies, Effi; Thurau, Mathias; Marquardt, Gaby; Naschberger, Elisabeth; Hentschel, Sonja; Jochmann, Ramona; Schulz, Thomas F.; Erfle, Holger; Brors, Benedikt; Lausen, Berthold; Neipel, Frank; et al. (Journal of Virology, 2009)
Human herpesvirus 8 (HHV-8) is the etiologic agent of Kaposi's sarcoma and primary effusion lymphoma. Activation of the cellular transcription factor nuclear factor-kappa B (NF-κB) is essential for latent persistence of HHV-8, survival of HHV-8-infected cells, and disease progression. We used reverse-transfected cell microarrays (RTCM) as an unbiased systems biology approach to systematically analyze the effects of HHV-8 genes on the NF-κB signaling pathway. All HHV-8 genes individually (n = 86) and, additionally, all K and latent genes in pairwise combinations (n = 231) were investigated. Statistical analyses of more than 14,000 transfections identified ORF75 as a novel and confirmed K13 as a known HHV-8 activator of NF-κB. K13 and ORF75 showed cooperative NF-κB activation. Small interfering RNA-mediated knockdown of ORF75 expression demonstrated that this gene contributes significantly to NF-κB activation in HHV-8-infected cells. Furthermore, our approach confirmed K10.5 as an NF-κB inhibitor and newly identified K1 as an inhibitor of both K13- and ORF75-mediated NF-κB activation. All results obtained with RTCM were confirmed with classical transfection experiments. Our work describes the first successful application of RTCM for the systematic analysis of pathofunctions of genes of an infectious agent. With this approach, ORF75 and K1 were identified as novel HHV-8 regulatory molecules on the NF-κB signal transduction pathway. The genes identified may be involved in fine-tuning of the balance between latency and lytic replication, since this depends critically on the state of NF-κB activity. Copyright © 2009, American Society for Microbiology.
Created from Fastlane, Scopus look-up

Automated Lesion Detection in Endoscopic Imagery for Small Animal Models - Eixelberger, Thomas; Fang, Qi; Zohud, Bisan; Hackner, Ralf; Jackstadt, Rene; Stürzl, Michael; Naschberger, Elisabeth; Wittenberg, Thomas (Bildverarbeitung für die Medizin 2024. BVM 2024, 2024)
Murine animal models are routinely used in research of gastrointestinal diseases, for example to analyze colorectal cancer or chronic inflammatory bowel diseases. By using suitable (miniaturized) endoscopy systems, it is possible to examine the large intestine of mice with respect to inflammatory, vascular or neoplastic changes without the need to sacrifice the animals. This enables the acquisition of high-resolution colonoscopy image sequences that can be used for the visual examination of tumors, the assessment of inflammation or the vasculature. Since the human resources for analyzing a multitude of videos, are limited, an automated evaluation of such image data is desirable. Video recordings (n = 49) of mice with and without colorectal cancer (CRC) were employed for this purpose and scored by clinical experts. The videos contained mice with tumors in 33 cases and 16 are pathologically normal. For the automatic detection of neoplastic changes (e.g. polyps), a deep neural network based on the YOLOv7- tiny architecture was applied. This network was previously trained on >36,000 human colon images with neoplasias visible in all frames. On test data with human images, the precision of the network is Prec = 0.92, and Rec = 0.90. The network was applied to the mouse data without any changes. To avoid falsepositive detections a color-based method was added to differentiate between stool residues and polyps. With the framework for the detection of neoplastic changes and classification of stool residues, we achieve results of Prec = 0.90, Rec = 0.98, F1 score = 0.94.Without the detection of stool residues, the values were dropping to Prec = 0.65 and Rec = 0.98, as 19 occurrences of stool are incorrectly classified as tumors. Our network trained on human data for neoplasia detection is able to accurately detect tumors in the murine colon. An additional module for the separation of stool residues is essential to avoid integration of wrongly positive cases.
CRIS-Team Scopus Importer:2024-03-29

Autonomously vascularized cellular constructs in tissue engeneering: opening a new perspective for biomedical science - Polykandriotis, Elias; Arkudas, Andreas; Horch, Raymund E.; Stürzl, Michael; Kneser, Ulrich (Journal of cellular and molecular medicine, 2007)
In tissue engineering cell cultures play a crucial role besides the matrix materials for the end of substituting lost tissue functions. The cell itself is situated at the cross-roads leading to different orders of scale, from molecule to organism and different levels of function, from biochemistry to macrophysiology. Extensive in vitro investigations have dissected a vast amount of cellular phenomena and the role of a number of bioactive substances has been elucidated in the past. Further, recombinant DNA technologies allow modulation of the expression profiles of virtually all kinds of cells. However, issues of vascularization in vivo limit transferability of these observations and restrict upscaling into clinical applications. Novel in vivo models of vascularization have evolved inspired from reconstructive microsurgical concepts and they encompass axial neovascularization by means of vascular induction. This work represents a brief description of latest developments and potential applications of neovascularization and angiogenesis in tissue engineering.
UnivIS-Import:2015-04-14:Pub.2007.med.packli.pchw2.autono

Autonomously vascularized cellular constructs in tissue engineering: opening a new perspective for biomedical science. - Polykandriotis, Elias; Arkudas, Andreas; Horch, Raymund E.; Stürzl, Michael; Kneser, Ulrich (Journal of Cellular and Molecular Medicine, 2007)
In tissue engineering cell cultures play a crucial role besides the matrix materials for the end of substituting lost tissue functions. The cell itself is situated at the cross-roads leading to different orders of scale, from molecule to organism and different levels of function, from biochemistry to macrophysiology. Extensive in vitro investigations have dissected a vast amount of cellular phenomena and the role of a number of bioactive substances has been elucidated in the past. Further, recombinant DNA technologies allow modulation of the expression profiles of virtually all kinds of cells. However, issues of vascularization in vivo limit transferability of these observations and restrict upscaling into clinical applications. Novel in vivo models of vascularization have evolved inspired from reconstructive microsurgical concepts and they encompass axial neovascularization by means of vascular induction. This work represents a brief description of latest developments and potential applications of neovascularization and angiogenesis in tissue engineering.

Axial prevascularization of porous matrices using an arteriovenous loop promotes survival and differentiation of transplanted autologous osteoblasts. - Arkudas, Andreas; Beier, Justus P.; Heidner, Kristina; Tjiawi, Jimmy; Polykandriotis, Elias; Srour, Safwan; Stürzl, Michael; Horch, Raymund E.; Kneser, Ulrich (Tissue Engineering -Larchmont, 2007)
Generation of axially vascularized bioartificial bone might be performed using matrix neovascularization in connection with osteoblast injection. We sought to evaluate whether prevascularization of porous hard matrices using an arteriovenous (AV) loop promotes survival of transplanted osteoblasts. A processed bovine cancellous bone matrix was inserted into the AV loop. Six weeks later, 5 x 10(6) carboxyfluorescein diacetate-stained osteoblasts were injected into the matrix (group A, n = 34). Osteoblast-seeded matrices without prevascularization were implanted subcutaneously as controls (group B, n = 32). Specimens were subjected to histologic, morphometric, and molecular-biological analysis after 1, 4, 8, and 16 weeks. Upon cell injection, matrices were completely vascularized. An intense foreign body reaction was observed in matrices from both groups. Group A was significantly superior to group B in terms of osteoblast survival at any time point. Expression of bone-specific genes was detected in the AV loop group but not in the subcutaneous control. Bone formation was only detectable in 1 long-term animal of group A. This study demonstrates for the first time that axial prevascularization increases the survival of implanted osteoblasts in porous matrices. Matrices with optimized biocompatibility might eventually facilitate generation of axially vascularized bone tissue after injection of osteogenic cells in the AV loop model.

Azidothymidine Sensitizes Primary Effusion Lymphoma Cells to Kaposi Sarcoma-Associated Herpesvirus-Specific CD4+ T Cell Control and Inhibits vIRF3 Function - Williamson, Samantha J.; Nicol, Samantha M.; Stürzl, Michael; Sabbah, Shereen; Hislop, Andrew D. (PLoS Pathogens, 2016)
Kaposi sarcoma-associated herpesvirus (KSHV) is linked with the development of Kaposi sarcoma and the B lymphocyte disorders primary effusion lymphoma (PEL) and multi-centric Castleman disease. T cell immunity limits KSHV infection and disease, however the virus employs multiple mechanisms to inhibit efficient control by these effectors. Thus KSHV-specific CD4+ T cells poorly recognize most PEL cells and even where they can, they are unable to kill them. To make KSHV-infected cells more sensitive to T cell control we treated PEL cells with the thymidine analogue azidothymidine (AZT), which sensitizes PEL lines to Fas-ligand and TRAIL challenge; effector mechanisms which T cells use. PELs co-cultured with KSHV-specific CD4+ T cells in the absence of AZT showed no control of PEL outgrowth. However in the presence of AZT PEL outgrowth was controlled in an MHC-restricted manner. To investigate how AZT sensitizes PELs to immune control we first examined BJAB cells transduced with individual KSHV-latent genes for their ability to resist apoptosis mediated by stimuli delivered through Fas and TRAIL receptors. This showed that in addition to the previously described vFLIP protein, expression of vIRF3 also inhibited apoptosis delivered by these stimuli. Importantly vIRF3 mediated protection from these apoptotic stimuli was inhibited in the presence of AZT as was a second vIRF3 associated phenotype, the downregulation of surface MHC class II. Although both vFLIP and vIRF3 are expressed in PELs, we propose that inhibiting vIRF3 function with AZT may be sufficient to restore T cell control of these tumor cells.
EVALuna2:15266

Beta-6-Integrin serves as a novel tumor marker and therapeutic target for colorectal carcinoma - Bengs, Susan; Becker, Eugenia; Spalinger, Marianne R.; Raselli, Tina; Kasper, Stephanie; Lang, Silvia; Atrott, Kirstin; Mamie, Celine; Britzen-Laurent, Nathalie; Von Boehmer, Lotta; Knuth, Alexander; Tuomisto, Anne; et al. (2017)
EVALuna2:35840

Big but weak: how many pathogenic genes does human herpesvirus-8 need to cause Kaposi's sarcoma? (Review). - Stürzl, Michael; Ensoli, Barbara (International Journal of Oncology, 1999)
Human herpesvirus-8 (HHV-8) is implicated in the pathogenesis of Kaposi's sarcoma (KS). In the last two years several HHV-8 gene products were heralded to 'cause KS' without any evidence that the respective gene is expressed in the tumor cells of KS lesions. In this framework it is of interest that almost 10% of the genes encoded by HHV-8 have been suggested to promote KS development due to either mitogenic, anti-apoptotic, chemoattractive, angiogenic or transforming activities. The rapidly growing number of HHV-8-encoded genes with 'KS causing' activities raises the question of why HHV-8 may need so many genes to trigger growth of KS that appears to be more closely related to a hyperplasia than to a real sarcoma. In this review an overview of the current knowledge of HHV-8 gene expressions in KS lesions in vivo is presented.

Biology of Kaposi's sarcoma. - Ensoli, Barbara; Sgadari, Cecilia; Barillari, Giovanni; Sirianni, Maria Caterina; Stürzl, Michael; Monini, Paolo (European Journal of Cancer, 2001)
Kaposi's sarcoma (KS) is an angioproliferative disease occurring in several different clinical-epidemiological forms that, however, share the same histological traits and are all associated with infection by the human herpesvirus 8 (HHV8). KS initiates in a context of immune dysregulation characterised by CD8+ T cell activation and the production of Th1-type cytokines that induce a generalised activation of endothelial cells leading to adhesion and tissue extravasation of lympho-monocytes, spindle cell formation and angiogenesis. These phenomena are triggered or enhanced by infection with HHV8 that, in turn, is reactivated by the same cytokines. Productively-infected circulating cells are recruited into 'activated' tissue sites where HHV8 finds an optimal environment for establishing a persistent, latent infection of KS spindle cells (KSC). HHV8 dissemination is favoured by virus escape mechanisms and immune dysregulation, and leads to immune responses that are not effective against the virus but, paradoxically, exacerbates the reactive process. Although early KS is a reactive process of polyclonal nature that can regress, in time it can progress in to a true sarcoma. The progression of KS appears to be due to the deregulated expression of oncogenes and oncosuppressor genes, to the long-lasting expression of the HHV8 latency genes and, for AIDS-KS, is promoted by the proliferative and angiogenic effects of the HIV-1 Tat protein.
Keywords: KS; Spindle cells; Inflammatory cytokines; Angiogenic factors; AIDS; HIV-1 Tat; HHV8; Angiogenesis; bcl-2; Immune evasion

Blood Vessel-Targeted Therapy in Colorectal Cancer: Current Strategies and Future Perspectives - Jacobsen, Anne; Siebler, Jürgen; Grützmann, Robert; Stürzl, Michael; Naschberger, Elisabeth (Cancers, 2024)
The vasculature is a key player and regulatory component in the multicellular microenvironment of solid tumors and, consequently, a therapeutic target. In colorectal carcinoma (CRC), antiangiogenic treatment was approved almost 20 years ago, but there are still no valid predictors of response. In addition, treatment resistance has become a problem. Vascular heterogeneity and plasticity due to species-, organ-, and milieu-dependent phenotypic and functional differences of blood vascular cells reduced the hope of being able to apply a standard approach of antiangiogenic therapy to all patients. In addition, the pathological vasculature in CRC is characterized by heterogeneous perfusion, impaired barrier function, immunosuppressive endothelial cell anergy, and metabolic competition-induced microenvironmental stress. Only recently, angiocrine proteins have been identified that are specifically released from vascular cells and can regulate tumor initiation and progression in an autocrine and paracrine manner. In this review, we summarize the history and current strategies for applying antiangiogenic treatment and discuss the associated challenges and opportunities, including normalizing the tumor vasculature, modulating milieu-dependent vascular heterogeneity, and targeting functions of angiocrine proteins. These new strategies could open perspectives for future vascular-targeted and patient-tailored therapy selection in CRC.
CRIS-Team Scopus Importer:2024-03-22
Keywords: aflibercept; angiocrine; antiangiogenic treatment; bevacizumab; cancer; colorectal cancer; endothelial cells; fruquintinib; ramucirumab; regorafenib; tumor microenvironment; vascular heterogeneity; vasculature

Cell death inhibition by KSHV - Murtadak, Vinay; Becker, Christoph; Stürzl, Michael (Aging-Us, 2015)
EVALuna2:1975

Cellular and molecular features of HIV-associated Kaposi's sarcoma. - Roth, Willi Kurt; Brandstetter, Heinz; Stürzl, Michael (Aids, 1992)

Centrosomal protein TRIM43 restricts herpesvirus infection by regulating nuclear lamina integrity - Full, Florian; Van Gent, Michiel; Sparrer, Konstantin M. J.; Chiang, Cindy; Zurenski, Matthew A.; Scherer, Myriam; Brockmeyer, Norbert H.; Heinzerling, Lucie; Stürzl, Michael; Korn, Klaus; Stamminger, Thomas; Enßer, Armin; et al. (Nature Microbiology, 2019)
Tripartite motif (TRIM) proteins mediate antiviral host defences by either directly targeting viral components or modulating innate immune responses. Here we identify a mechanism of antiviral restriction in which a TRIM E3 ligase controls viral replication by regulating the structure of host cell centrosomes and thereby nuclear lamina integrity. Through RNAi screening we identified several TRIM proteins, including TRIM43, that control the reactivation of Kaposi's sarcoma-associated herpesvirus. TRIM43 was distinguished by its ability to restrict a broad range of herpesviruses and its profound upregulation during herpesvirus infection as part of a germline-specific transcriptional program mediated by the transcription factor DUX4. TRIM43 ubiquitinates the centrosomal protein pericentrin, thereby targeting it for proteasomal degradation, which subsequently leads to alterations of the nuclear lamina that repress active viral chromatin states. Our study identifies a role of the TRIM43-pericentrin-lamin axis in intrinsic immunity, which may be targeted for therapeutic intervention against herpesviral infections.
EVALuna2:35255

Chronic intestinal inflammation in mice expressing viral Flip in epithelial cells - Ruder, Barbara; Murtadak, Vinay; Stürzl, Michael; Wirtz, Stefan; Distler, Ute; Tenzer, Stefan; Mahapatro, Mousumi; Greten, Florian R.; Hu, Yinling; Neurath, Markus; Cesarman, Ethel; Ballon, Gianna; et al. (Mucosal Immunology, 2018)
Viruses are present in the intestinal microflora and are currently discussed as a potential causative mechanism for the development of inflammatory bowel disease. A number of viruses, such as Human Herpesvirus-8, express homologs to cellular FLIPs, which are major contributors for the regulation of epithelial cell death. In this study we analyzed the consequences of constitutive expression of HHV8-viral FLIP in intestinal epithelial cells (IECs) in mice. Surprisingly, expression of vFlip disrupts tissue homeostasis and induces severe intestinal inflammation. Moreover vFlipIEC-tg mice showed reduced Paneth cell numbers, associated with excessive necrotic cell death. On a molecular level vFlip expression altered classical and alternative NFκB activation. Blocking of alternative NFκB signaling by deletion of Ikka in vivo largely protected mice from inflammation and Paneth cell loss induced by vFLIP. Collectively, our data provide functional evidence that expression of a single viral protein in IECs can be sufficient to disrupt epithelial homeostasis and to initiate chronic intestinal inflammation.
EVALuna2:35131

Clearance of human herpesvirus 8 from blood and regression of leukopenia-associated aggressive classic Kaposi's sarcoma during interferon-alpha therapy: a case report. - Monini, Paolo; Sirianni, Maria Caterina; Franco, Marina; Vincenzi, Laura; Topino, Simone; Goletti, Delia; Leone, Patrizia; Leone, Pasqualina; Chiozzini, Chiara; Nicastri, Emanuele; Andreoni, Massimo; Borduagni, Osvaldo; et al. (Clinical Infectious Diseases, 2001)
A human immunodeficiency virus-negative woman with severe classic Kaposi's sarcoma, idiopathic leukopenia, and massive spread of human herpesvirus 8 (HHV-8) in circulating cells showed stable disease remission in response to systemic interferon-alpha treatment that was accompanied by increased CD3(+) and CD4(+) T cell numbers and complete clearance of HHV-8 from the circulation. These results suggest a direct relationship between HHV-8 clearance from blood and regression of Kaposi's sarcoma and are consistent with the in vitro inhibitory effects of interferon-alpha on HHV-8 infection.

Cocultivation of Mesenchymal Stem Cells and Endothelial Progenitor Cells Reveals Antiapoptotic and Proangiogenic Effects - Steiner, Dominik; Köhn, Katrin; Beier, Justus; Stürzl, Michael; Horch, Raymund E.; Arkudas, Andreas (Cells Tissues Organs, 2017)
Integrating bioartificial tissues into the host vasculature is a prerequisite for tissue engineering applications. Endothelial progenitor cells (EPCs) display a high angiogenic potential and a low donor-site morbidity, making them ideal for tissue engineering applications. In our study we used a murine EPC cell line (T17b) and rat mesenchymal stem cells (MSCs) for cocultivation experiments. MSCs were cocultured with increasing T17b EPC amounts. Furthermore, MSCs in monoculture were treated with conditioned medium (CM) from T17b EPCs and T17b EPCs were treated with CM from MSCs. Proliferation and apoptosis were quantified with a bromodeoxyuridine ELISA and a DNA fragmentation ELISA, respectively. Osteogenic differentiation was detected with an alkaline phosphatase assay and bone morphogenetic protein-2 ELISA. The production of proangiogenic molecules was measured with a matrix metalloproteinase-3 and vascular endothelial growth factor ELISA as well as nitric oxide assay. We could show that T17b EPCs stimulated MSC proliferation but not vice versa. On the other hand, MSCs promoted the cell survival of EPCs. The growth-inducing and antiapoptotic effects were dependent on heterotypic cell contacts and paracrine mediators. Moreover, proangiogenic growth factors were found in the coculture. Collectively, our results indicate that the coapplication of MSCs and T17b EPCs provides new perspectives for tissue engineering applications.
EVALuna2:15306

Comprehensive screening for mutations associated with colorectal cancer in unselected cases reveals penetrant and nonpenetrant mutations - Kraus, Cornelia; Rau, Tilman; Lux, Philipp; Erlenbach-Wuensch, Katharina; Loehr, Sabine; Krumbiegel, Mandy; Thiel, Christian; Stoehr, Robert; Agaimy, Abbas; Croner, Roland S.; Stürzl, Michael; Hohenberger, Werner; et al. (International Journal of Cancer, 2015)
Germline mutation testing in patients with colorectal cancer (CRC) is offered only to a subset of patients with a clinical presentation or tumor histology suggestive of familial CRC syndromes, probably underestimating familial CRC predisposition. The aim of our study was to determine whether unbiased screening of newly diagnosed CRC cases with next generation sequencing (NGS) increases the overall detection rate of germline mutations. We analyzed 152 consecutive CRC patients for germline mutations in 18 CRC-associated genes using NGS. All patients were also evaluated for Bethesda criteria and all tumors were investigated for microsatellite instability, immunohistochemistry for mismatch repair proteins and the BRAF*V600E somatic mutation. NGS based sequencing identified 27 variants in 9 genes in 23 out of 152 patients studied (18%). Three of them were already reported as pathogenic and 12 were class 3 germline variants with an uncertain prediction of pathogenicity. Only 1 of these patients fulfilled Bethesda criteria and had a microsatellite instable tumor and an MLH1 germline mutation. The others would have been missed with current approaches: 2 with a MSH6 premature termination mutation and 12 uncertain, potentially pathogenic class 3 variants in APC, MLH1, MSH2, MSH6, MSH3 and MLH3. The higher NGS mutation detection rate compared with current testing strategies based on clinicopathological criteria is probably due to the large genetic heterogeneity and overlapping clinical presentation of the various CRC syndromes. It can also identify apparently nonpenetrant germline mutations complicating the clinical management of the patients and their families.
EVALuna2:6598

Contribution of Blood Vessel Activation, Remodeling and Barrier Function to Inflammatory Bowel Diseases - Britzen-Laurent, Nathalie; Weidinger, Carl; Stürzl, Michael (International Journal of Molecular Sciences, 2023)
Inflammatory bowel diseases (IBDs) consist of a group of chronic inflammatory disorders with a complex etiology, which represent a clinical challenge due to their often therapy-refractory nature. In IBD, inflammation of the intestinal mucosa is characterized by strong and sustained leukocyte infiltration, resulting in the loss of epithelial barrier function and subsequent tissue destruction. This is accompanied by the activation and the massive remodeling of mucosal micro-vessels. The role of the gut vasculature in the induction and perpetuation of mucosal inflammation is receiving increasing recognition. While the vascular barrier is considered to offer protection against bacterial translocation and sepsis after the breakdown of the epithelial barrier, endothelium activation and angiogenesis are thought to promote inflammation. The present review examines the respective pathological contributions of the different phenotypical changes observed in the microvascular endothelium during IBD, and provides an overview of potential vessel-specific targeted therapy options for the treatment of IBD.
CRIS-Team Scopus Importer:2023-04-07
Keywords: angiogenesis; gut vascular barrier; inflammatory bowel diseases (IBDs); vasculature; vessel permeability

Cytochemical and molecular properties of simian virus 40 transformed Kaposi's sarcoma-derived cells: evidence for the secretion of a member of the fibroblast growth factor family. - Werner, Sabine; Hofschneider, Peter Hans; Stürzl, Michael; Dick, Irene; Roth, Willi Kurt (Journal of Cellular Physiology, 1989)
Contact-inhibited Kaposi's sarcoma-derived cells (KS cells) were transfected with Simian Virus 40 (SV40) DNA. Transformed cells (SV-KSC) were selected for their capacity to form foci on monolayers of the low-malignant KS cells. Isolated SV-KSC foci were found to contain integrated SV40 DNA sequences and to express SV40 large T-antigen. Several differentiation properties of KS cells are retained in the SV40 transformants, e.g., expression of vimentin and the endothelial cell marker BMA 120. In contrast to the maternal KS cells, SV-KSC are capable of growing in platelet-derived growth factor (PDGF)-depleted platelet-poor-plasma serum (PPPS) and in soft agar. However, they are not tumorigenic in nude mice. Expression of the oncogenes c-myc, c-N-ras, c-Ha-ras, and p53 is significantly elevated in SV-KSC, whereas c-fos and c-erb B expression is comparable to that of KS cells and fibroblasts. Conditioned medium from SV-KSC can substitute for PDGF when PDGF-dependent, nontransformed KS cells are grown in PPPS. Biochemical analysis of the SV-KSC supernatant and PDGF A and B mRNA expression analysis provide evidence that the mitogenic activity is not due to a PDGF-like growth factor. On the other hand, there is evidence to indicate that the SV-KSC mitogen is a member of the fibroblast growth factor family. SV-KSC represent an interesting model system for the study of different degrees of malignancy of cultured mesenchymal cells and especially provide an important source for the isolation of a potent growth factor for KS cells and other mesenchymal cells in vitro.

Cytokine-induced guanylate binding protein 1 (GBP1) release from human ovarian cancer cells - Carbotti, Grazia; Petretto, Andrea; Naschberger, Elisabeth; Stürzl, Michael; Martini, Stefania; Mingari, Maria Cristina; Filaci, Gilberto; Ferrini, Silvano; Fabbi, Marina (Cancers, 2020)
We showed that IL-27 shares several effects with IFN-γ in human cancer cells. To identify novel extracellular mediators, potentially involved in epithelial ovarian cancer (EOC) biology, we analyzed the effect of IL-27 or IFN-γ on the secretome of cultured EOC cells by mass-spectrometry (nano-UHPLC-MS/MS). IL-27 and IFN-γ modulate the release of a limited fraction of proteins among those induced in the whole cell. We focused our attention on GBP1, a guanylate-binding protein and GTPase, which mediates several biological activities of IFNs. Cytokine treatment induced GBP1, 2, and 5 expressions in EOC cells, but only GBP1 was secreted. ELISA and immunoblotting showed that cytokine-stimulated EOC cells release full-length GBP1 in vitro, through non-classical pathways, not involving microvesicles. Importantly, full-length GBP1 accumulates in the ascites of most EOC patients and ex-vivo EOC cells show constitutive tyrosine-phosphorylated STAT1/3 proteins and GBP1 expression, supporting a role for Signal Transducer And Activator Of Transcription (STAT)-activating cytokines in vivo. High GBP1 gene expression correlates with better overall survival in the TCGA (The Cancer Genome Atlas) dataset of EOC. In addition, GBP1 transfection partially reduced EOC cell viability in an MTT assay. Our data show for the first time that cytokine-stimulated tumor cells release soluble GBP1 in vitro and in vivo and suggest that GBP1 may have anti-tumor effects in EOC.
CRIS-Team Scopus Importer:2020-02-28
Keywords: Guanylate binding protein 1; Interferon-γ; Interleukin-27; Microenvironment; Ovarian cancer; Secretome

Cytokine-mediated growth promotion of Kaposi's sarcoma and primary effusion lymphoma. - Ensoli, Barbara; Stürzl, Michael; Monini, Paolo (Seminars in Cancer Biology, 2000)
Kaposi's sarcoma (KS) is an angioproliferative disease particularly frequent and aggressive in patients with AIDS but occurring also in post-transplant patients or in immunocompetent individuals of certain geographic areas. At least in its early stages, KS behaves as a reactive hyperplastic process mediated by inflammatory cytokines and angiogenic factors triggered or exacerbated by human herpesvirus-8 (HHV-8) infection. The HIV Tat protein appears to be responsible for the highly aggressive nature of AIDS-KS. Over time, however, KS may evolve into a true sarcoma in association with the expression of oncogenes and/or HHV-8 latency genes endowed with growth and anti-apoptotic properties. HHV-8 infection is also associated with primary effusion lymphoma (PEL), a rare tumor that similarly develops more frequently in the setting of HIV infection. HHV-8 latency genes are likely to contribute to the neoplastic phenotype of PEL cells, whose growth in vivo may require cytokines and factors from the host, or encoded by the virus.

Cytokine profile of HIV-positive Kaposi's sarcoma derived cells in vitro. - Brockmeyer, Norbert H.; Willers, C P; Anders, S; Mertins, L; Rockstroh, Jürgen; Stürzl, Michael (European Journal of Medical Research, 1999)
Kaposi's sarcoma (KS) is the most frequent neoplastic complication observed in HIV-infected patients. Cutaneous KS is the most common manifestation but visceral and lymph node involvement may occur. HIV-infection does not only lead to a decrease of certain cell types (CD4 T-lymphocytes), but also modifies the function of non-infected cells such as B-lymphocytes and NK-cells by upregulating cytokine release of IL-1, IL-6, GM-CSF, IFN-gamma and TNF-alpha. These multifunctional mediators show both autocrine and paracrine proliferative effects on normal endothelial cells and AIDS-related KS-cells. Using ELISA-, RIA- and IRMA-techniques we analysed the influence of seven cytokines (IL-1beta, IL-6, TNF-alpha, GM-CSF, IFN-alpha, IFN-beta, IFN-gamma) and the soluble IL-2 receptor (sIL-2R) on the growth of eight different KS-derived cell lines compared with eight fibroblast cell lines, established from skin biopsies of HIV-positive individuals. Furthermore, we analysed the dose-dependent effect of the above mentioned cytokines on KS-derived cells in vitro. The KS-derived cell culture medium demonstrated significantly higher concentrations than the fibroblast cell lines in view of the following cytokines: sIL-2R, IL-1beta, IL-6, TNF-alpha, GM-CSF, IFN-gamma (p<0.05). The most pronounced differences between KS-cells and fibroblasts were observed for IL-1beta and IFN-gamma. The antiproliferative effect of IFN-beta and IFN-gamma began at a concentration of 20 and 50 IU/ml, respectively, whereas for IFN-alpha an antiproliferative effect was observed at a concentration of 100 U/ml. Furthermore we observed a proliferative effect in low concentrations (2-5 IU/ml) of IFN-gamma in our in vitro model

Cytotoxic effect of Efavirenz in BxPC-3 pancreatic cancer cells is based on oxidative stress and is synergistic with ionizing radiation - Hecht, Markus; Harrer, Thomas; Koeber, Verena; Sarpong, Eric Opoku; Moser, Fabian; Fiebig, Nora; Schwegler, Manuela; Stürzl, Michael; Fietkau, Rainer; Distel, Luitpold (Oncology Letters, 2018)
The non-nucleoside reverse transcriptase inhibitor (NNRTI) Efavirenz is frequently used in human immunodeficiency virus treatment, but also efficient against cancer in mouse models. Its radiosensitizing effect makes it a promising drug for combination with radiotherapy. The efficacy of Efavirenz combined with irradiation was assessed with immunostaining of DNA-damage markers and colony formation assays in BxPC-3 pancreatic cancer cells. Gene expression and protein phosphorylation of the Efavirenz-sensitive BxPC-3 cells was compared to the resistant primary fibroblasts SBL-5. Oxidative stress, mitochondrial damage and cell death were studied with live-cell microscopy and flow cytometry. Combined Efavirenz and radiation significantly increased the number of γH2AX and phospho-ataxia telangiectasia mutated foci. Efavirenz and ionizing radiation had a synergistic effect using the clonogenic survival assay. Efavirenz selectively induced cell death in the BxPC-3 cells. The differing gene expression of cell cycle and apoptotic regulator genes in both cell cultures after Efavirenz treatment match with this selective effect against cancer cells. In the phosphoprotein array, an early phosphorylation of extracellular signal-related kinase 1/2 and p38 mitogen-activated protein kinase was notably detected in the cancer cells. The phosphorylation of AKT decreased in the cancer cells whereas it increased in the fibroblasts. Oxidative stress and mitochondrial membrane depolarization appeared in the cancer cells immediately after Efavirenz treatment, but not in the fibroblasts. Efavirenz has an anti-cancer effect against pancreatic cancer mainly by the induction of oxidative stress. The antitumor potential of Efavirenz and radiotherapy are additive.
EVALuna2:36443

Deletion of Kaposi's sarcoma-associated herpesvirus FLICE inhibitory protein, vFLIP, from the viral genome compromises the activation of STAT1-responsive cellular genes and spindle cell formation in endothelial cells. - Stürzl, Michael; et al. (Journal of Virology, 2011)
Kaposi's sarcoma herpesvirus (KSHV) Fas-associated death domain (FADD)-like interleukin-1 beta-converting enzyme (FLICE)-inhibitory protein, vFLIP, has antiapoptotic properties, is a potent activator of the NF-κB pathway, and induces the formation of endothelial spindle cells, the hallmark of Kaposi's sarcoma, when overexpressed in primary endothelial cells. We used a reverse genetics approach to study several functions of KSHV vFLIP in the context of the whole viral genome. Deletion of the gene encoding vFLIP from a KSHV genome cloned in a bacterial artificial chromosome (BAC) reduced the ability of the virus to persist and induce spindle cell formation in primary human umbilical vein endothelial cells (HUVECs). Only a few, mainly interferon (IFN)-responsive, genes were expressed in wild-type KSHV (KSHV-wt)-infected endothelial cells at levels higher than those in KSHV-ΔFLIP-infected endothelial cells, in contrast to the plethora of cellular genes induced by overexpressed vFLIP. In keeping with this observation, vFLIP induces the phosphorylation of STAT1 and STAT2 in an NF-κB-dependent manner in endothelial cells. vFLIP-dependent phosphorylation of STAT1 and STAT2 could be demonstrated after endothelial cells were infected with KSHV-wt, KSHV-ΔFLIP, and a KSHV-vFLIP revertant virus. These findings document the impact of KSHV vFLIP on the transcriptome of primary endothelial cells during viral persistence and highlight the role of vFLIP in the activation of STAT1/STAT2 and STAT-responsive cellular genes by KSHV.

Differential Effects of Ontamalimab Versus Vedolizumab on Immune Cell Trafficking in Intestinal Inflammation and Inflammatory Bowel Disease - Schulze, Lisa; Becker, Emily; Dedden, Mark; Liu, Lijuan; Van Passen, Chiara; Mohamed Abdou, Mariam; Müller, Tanja; Wiendl, Maximilian; Ullrich, Karen; Atreya, Imke; Leppkes, Moritz; Ekici, Arif Bülent; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: The anti-MAdCAM-1 antibody ontamalimab demonstrated efficacy in a phase II trial in ulcerative colitis and results of early terminated phase III trials are pending, but its precise mechanisms of action are still unclear. Thus, we explored the mechanisms of action of ontamalimab and compared it to the anti-α4β7 antibody vedolizumab. Methods: We studied MAdCAM-1 expression with RNA sequencing and immunohistochemistry. The mechanisms of action of ontamalimab were assessed with fluorescence microscopy, dynamic adhesion and rolling assays. We performed in vivo cell trafficking studies in mice and compared ontamalimab and vedolizumab surrogate [-s] antibodies in experimental models of colitis and wound healing. We analysed immune cell infiltration under anti-MAdCAM-1 and anti-α4β7 treatment by single-cell transcriptomics and studied compensatory trafficking pathways. Results: MAdCAM-1 expression was increased in active inflammatory bowel disease. Binding of ontamalimab to MAdCAM-1 induced the internalization of the complex. Functionally, ontamalimab blocked T cell adhesion similar to vedolizumab, but also inhibited L-selectin-dependent rolling of innate and adaptive immune cells. Despite conserved mechanisms in mice, the impact of ontamalimab-s and vedolizumab-s on experimental colitis and wound healing was similar. Single-cell RNA sequencing demonstrated enrichment of ontamalimab-s-treated lamina propria cells in specific clusters, and in vitro experiments indicated that redundant adhesion pathways are active in these cells. Conclusions: Ontamalimab has unique and broader mechanisms of action compared to vedolizumab. However, this seems to be compensated for by redundant cell trafficking circuits and leads to similar preclinical efficacy of anti-α4β7 and anti-MAdCAM-1 treatment. These results will be important for the interpretation of pending phase III data.
CRIS-Team Scopus Importer:2023-12-15

DNA stool test for colorectal cancer: hypermethylation of the secreted frizzled-related protein-1 gene. - Zhang, Wei; Bauer, Michael; Croner, Roland S.; Pelz, Jörg Otto Wilhelm; Lodygin, Dimitri; Hermeking, Heiko; Stürzl, Michael; Hohenberger, Werner; Matzel, Klaus (Diseases of the colon & rectum, 2007)
To investigate a potential mode of noninvasive screening for colorectal cancer, we evaluated the hypermethylation of the secreted frizzled-related protein-1 gene promoter in human stool DNA. In stool samples from 36 patients with colorectal neoplasia (7 adenoma, 29 colorectal cancer) and 17 healthy control subjects, isolated DNA was treated with sodium bisulfite and analyzed by methylation-specific polymerase chain reaction with primers specific for methylated or unmethylated promoter sequences of the secreted frizzled-related protein-1 gene. Hypermethylation of the secreted frizzled-related protein-1 promoter was present in the stool DNA of patients with adenoma and colorectal cancer. A sensitivity of 89 percent and specificity of 86 percent were achieved in the detection of colorectal neoplasia. The difference in hypermethylation status of the secreted frizzled-related protein-1 promoter between the patients with colorectal neoplasia and the control group was statistically highly significant (P < 0.001). Adenoma and early tumor Stage I (International Union Against Cancer) displayed both unmethylated and methylated secreted frizzled-related protein-1 promoter sequences, whereas advanced tumor stages showed only methylated secreted frizzled-related protein-1 (P = 0.05). The results indicate that this DNA stool test of hypermethylation of the secreted frizzled-related protein-1 promoter is a sensitive and specific method. It has the potential of a clinically useful test for the early detection of colorectal cancer. PURPOSE METHODS RESULTS CONCLUSIONS
Keywords: DNA methylation; Colorectal cancer; Secreted frizzled-related protein; Stool DNA test; Epigenetic marker; Cancer screening

EBV latent membrane protein-1 protects B cells from apoptosis by inhibition of BAX - Naschberger, Elisabeth; Stürzl, Michael; et al. (Blood, 2005)
Latent membrane protein 1 (LMP-1) of Epstein-Barr virus (EBV) promotes tumorigenesis by inhibiting apoptosis. We show that an important antiapoptotic activity of LMP-1 is the inhibition of Bcl2-associated protein X (Bax), a potent proapoptotic protein. BAX expression was regulated by LMP-1 activation of nuclear factor κB (NF-κB) via the C-terminal activation region 1 (CTAR-1) and CTAR-2. Interestingly, p65/p50 inhibited, whereas p50/p50 increased, BAX promoter activity as demonstrated by overexpression and selective inhibition of these NF-κB isoforms. Electrophoretic mobility shift analysis revealed that LMP-1 activates 2 of the 3 NF-κB binding sites (κB1-κB3) in the BAX promoter. LMP-1 induced binding of the NF-κB heterodimer p65/p50 to the κB2 site and of the p50/p50 homodimer to the κB3 site. Promoter mutation analysis revealed that the κB2 site is necessary for inhibition of BAX promoter activity and the κB3 site, for its activation. However, the activation of the BAX promoter by LMP-1 was observed only in the presence of specific inhibitors of p65/p50. In all other cases, LMP-1 inhibited BAX promoter activity. Most importantly, the antiapoptotic activity of LMP-1 was considerably decreased in cells deficient for BAX. These results indicate that the inhibition of Bax may be an important antiapoptotic activity of LMP-1. © 2005 by The American Society of Hematology.
Created from Fastlane, Scopus look-up

Endothelial CCR2 signaling induced by colon carcinoma cells enables extravasation via the JAK2-Stat5 and p38MAPK pathway. - Wolf, Monika Julia; Hoos, Alexandra; Bauer, Judith; Boettcher, Steffen; Knust, Markus; Weber, Achim; Simonavicius, Nicole; Schneider, Christoph; Lang, Matthias; Stürzl, Michael; Croner, Roland S.; Konrad, Andreas; et al. (Cancer Cell, 2012)
Increased expression of the chemokine CCL2 in tumor cells correlates with enhanced metastasis, poor prognosis, and recruitment of CCR2(+)Ly6C(hi) monocytes. However, the mechanisms driving tumor cell extravasation through the endothelium remain elusive. Here, we describe CCL2 upregulation in metastatic UICC stage IV colon carcinomas and demonstrate that tumor cell-derived CCL2 activates the CCR2(+) endothelium to increase vascular permeability in vivo. CCR2 deficiency prevents colon carcinoma extravasation and metastasis. Of note, CCR2 expression on radio-resistant cells or endothelial CCR2 expression restores extravasation and metastasis in Ccr2(-/-) mice. Reduction of CCR2 expression on myeloid cells decreases but does not prevent metastasis. CCL2-induced vascular permeability and metastasis is dependent on JAK2-Stat5 and p38MAPK signaling. Our study identifies potential targets for treating CCL2-dependent metastasis.

Endothelial cells of human colorectal cancer and healthy colon reveal phenotypic differences in culture - Stürzl, Michael; Naschberger, Elisabeth; et al. (Laboratory Investigation, 2007)
Antiangiogenic drugs have been used successfully for the treatment of colorectal cancer (CRC). Viable tumor endothelial cells (TEC) and normal endothelial cells (NEC) of uninvolved colon tissue of the same patient have not been available to optimize treatment strategies in vitro. Therefore, our target was to establish a protocol for the isolation of TEC and NEC. These cells were isolated with very high purity via magnetic cell sorting of tissue samples obtained from CRC and healthy colon of eight patients. TEC and NEC expressed CD31, CD105, VE-cadherin, VCAM-1, ICAM-1 and E-selectin, formed capillaries in basal membrane extract and were able to take up acetylated low-density lipoprotein. They were negative for podoplanin, CD45, CD68 and cytokeratin-20 indicating blood vessel endothelial lineage. Intense staining of von Willebrand factor (vWF) was observed in five of eight NEC cultures, whereas vWF was absent or only slightly expressed in all TEC cultures in vitro. Low intracellular concentration of vWF was also detected in TEC and NEC at the tissue level. This demonstrated that differences exhibited by TEC and NEC in vivo are stably perpetuated in culture. The isolated cultures may provide a useful in vitro model to elucidate epigenetic effects on angiogenesis in cancer and to optimize antiangiogenic therapy. © 2007 USCAP, Inc All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Colorectal cancer; Endothelial cells; Von Willebrand factor

Endothelial progenitor cells are integrated in newly formed capillaries and alter adjacent fibrovascular tissue after subcutaneous implantation in a fibrin matrix - Bleiziffer, Oliver; Hammon, Matthias; Naschberger, Elisabeth; Lipnik, Karoline; Arkudas, Andreas; Rath, Subha; Pryymachuk, Galyna; Beier, Justus; Stürzl, Michael; Horch, Raymund E.; Kneser, Ulrich (Journal of Cellular and Molecular Medicine, 2011)
Vascularization of bioartificial matrices is crucial for successful tissue engineering. Endothelial progenitor cells (EPC) have shown vascularization potential in ischemic conditions and may also support blood vessel formation in tissue-engineered matrices. The aim of our study was to investigate the impact of a well-characterized murine embryonal EPC line (T17b-EPC) on vascularization and fibrovascular granulation tissue formation after suspension in a fibrine matrix followed by subcutaneous implantation in a separation chamber in rats. EPC were fluorescently labelled in vitro prior to implantation. After 3, 7 or 14 days, animals were killed followed by explantation and histological analysis of the constructs. Before the end of the experiment, Bandeirea Simplicifolia lectin was intravenously injected to mark the vascular ingrowth into the implanted constructs. The transplanted cells were histologically detected at all time-points and located almost exclusively within the fibrin matrix at day 3 but the number of cells in the clot continuously decreased over day 7 to day 14. Conversely, cells were detected within the newly formed granulation tissue in increasing numbers from day 3 over day 7 to day 14. Transplanted cells were also found in the intermuscular septa. Cell viability was confirmed by use of an EPC clone expressing β-galactosidase. Fluorescence microscopy demonstrated integration of the transplanted cells in newly formed blood vessels within the fibrovascular granulation tissue adjacent to the fibrin clot. Presence of cells in the fibrin clot lead to thicker granulation tissue and an increased blood vessel diameter compared to cell-free controls. Organ standard controls showed presence of the transplanted cells in spleens at day 14 after transplantation. In summary, EPC exhibited biological activity after subcutaneous implantation in a fibrin matrix by migration from the fibrin clot into the granulation tissue and along intermuscular septae, undergoing differentiation into mature endothelial cells and integration into newly formed blood vessels and altering fibrovascular granulation tissue development. EPC may hold promise to modulate blood vessel formation in bioartificial matrices. © 2011 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Endothelial progenitor cells; Fibrin matrix; Tissue engineering

Engineering of vascularized transplantable bone tissues: induction of axial vascularization in an osteoconductive matrix using an arteriovenous loop. - Kneser, Ulrich; Polykandriotis, Elias; Ohnolz, Jan; Heidner, Kristina; Grabinger, Lucia; Euler, Simon; Amann, Kerstin Ute; Heß, Andreas; Brune, Kay; Greil, Peter; Stürzl, Michael; Horch, Raymund E. (Tissue Engineering -Larchmont, 2006)
This study demonstrates for the first time successful vascularization of solid porous matrices by means of an AV loop. Injection of osteogenic cells into axially prevascularized matrices may eventually create functional bioartificial bone tissues for reconstruction of large defects. Vascularization remains an obstacle to engineering of larger volume bone tissues. Our aim was to induce axial vascularization in a processed bovine cancellous bone (PBCB) matrix using an arteriovenous (AV) loop (artery, vein graft, and vein). Custom-made PBCB discs (9 x 5 mm) were implanted into rats. In group A (n = 19), the matrices were inserted into microsurgically constructed AV loops between the femoral vessels using a vein graft from the contralateral side. In group B (n = 19), there was no vascular carrier. The matrices were encased in isolation chambers. After 2, 4, and 8 weeks, the animals were perfused with India ink via the abdominal aorta. Matrices were explanted and subjected to histological and morphometric analysis. Results were compared with intravital dynamic micro & magnetic resonance imaging and scanning electron microscopy images of vascular corrosion replicas. In group A, significant vascularization of the matrix had occurred by the 8th week. At this time, vascular remodeling with organization into vessels of different sizes was evident. Blood vessels originated from all 3 zones of the AV loop. Group A was significantly superior to group B in terms of vascular density and vascularization kinetics. DISCUSSION INTRODUCTION METHODS RESULTS

Engineering Therapeutic Regulatory T Cells to Overexpress G Protein-Coupled Receptor 15 Improves Functional Fitness for In Vivo Gut Homing - Müller, Tanja; Liu, Lijuan; Wiesinger, Manuel; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; Diefenbach, Andreas; et al. (Gastroenterology, 2025)
CRIS-Team Scopus Importer:2025-01-31

Epithelial OPA1 links mitochondrial fusion to inflammatory bowel disease - Bao, Lili; Yu, Yidong; Gonzalez Acera, Miguel; Patankar, Jay; Gießl, Andreas; Sturm, Gregor; Kühl, Anja A.; Atreya, Raja; Erkert, Lena; Gamez-Belmonte, Reyes; Krug, Susanne M.; Schmid, Benjamin; et al. (Science Translational Medicine, 2025)
Dysregulation at the intestinal epithelial barrier is a driver of inflammatory bowel disease (IBD). However, the molecular mechanisms of barrier failure are not well understood. Here, we demonstrate dysregulated mitochondrial fusion in intestinal epithelial cells (IECs) of patients with IBD and show that impaired fusion is sufficient to drive chronic intestinal inflammation. We found reduced expression of mitochondrial fusion–related genes, such as the dynamin-related guanosine triphosphatase (GTPase) optic atrophy 1 (OPA1), and fragmented mitochondrial networks in crypt IECs of patients with IBD. Mice with Opa1 deficiency in the gut epithelium (Opa1i∆IEC) spontaneously developed chronic intestinal inflammation with mucosal ulcerations and immune cell infiltration. Intestinal inflammation in Opa1i∆IEC mice was driven by microbial translocation and associated with epithelial progenitor cell death and gut barrier dysfunction. Opa1-deficient epithelial cells and human organoids exposed to a pharmacological OPA1 inhibitor showed disruption of the mitochondrial network with mitochondrial fragmentation and changes in mitochondrial size, ultrastructure, and function, resembling changes observed in patient samples. Pharmacological inhibition of the GTPase dynamin-1–like protein in organoids derived from Opa1i∆IEC mice partially reverted this phenotype. Together, our data demonstrate a role for epithelial OPA1 in regulating intestinal immune homeostasis and epithelial barrier function. Our data provide a mechanistic explanation for the observed mitochondrial dysfunction in IBD and identify mitochondrial fusion as a potential therapeutic target in this disease.
CRIS-Team Scopus Importer:2025-01-31

Epithelial presenilin-1 drives colorectal tumour growth by controlling EGFR-COX2 signalling - Gámez Belmonte, Maria de los Reyes; Mahapatro, Mousumi; Erkert, Lena; Gonzalez Acera, Miguel; Naschberger, Elisabeth; Yu, Yuqiang; Tena-Garitaonaindia, Mireia; Patankar, Jay; Wagner, Yara; Podstawa, Eva; Schoedel, Lena; Bubeck, Marvin; et al. (Gut, 2022)
Objective Psen1 was previously characterised as a crucial factor in the pathogenesis of neurodegeneration in patients with Alzheimer's disease. Little, if any, is known about its function in the gut. Here, we uncovered an unexpected functional role of Psen1 in gut epithelial cells during intestinal tumourigenesis. Design Human colorectal cancer (CRC) and control samples were investigated for PSEN1 and proteins of the gamma-secretase complex. Tumour formation was analysed in the AOM-DSS and Apc (min/+) mouse models using newly generated epithelial-specific Psen1 deficient mice. Psen1 deficient human CRC cells were studied in a xenograft tumour model. Tumour-derived organoids were analysed for growth and RNA-Seq was performed to identify Psen1-regulated pathways. Tumouroids were generated to study EGFR activation and evaluation of the influence of prostanoids. Results PSEN1 is expressed in the intestinal epithelium and its level is increased in human CRC. Psen1-deficient mice developed only small tumours and human cancer cell lines deficient in Psen1 had a reduced tumourigenicity. Tumouroids derived from Psen1-deficient Apc (min/+) mice exhibited stunted growth and reduced cell proliferation. On a molecular level, PSEN1 potentiated tumour cell proliferation via enhanced EGFR signalling and COX-2 production. Exogenous administration of PGE(2) reversed the slow growth of PSEN1 deficient tumour cells via PGE(2) receptor 4 (EP4) receptor signalling. Conclusions Psen1 drives tumour development by increasing EGFR signalling via NOTCH1 processing, and by activating the COX-2-PGE(2) pathway. PSEN1 inhibition could be a useful strategy in treatment of CRC.
CRIS-Team WoS Importer:2022-11-04
Keywords: colorectal cancer; colorectal adenomas; arachidonic and metabolism

Evaluating predictive modeling algorithms to assess patient eligibility for clinical trials from routine data - Köpcke, Felix; Lubgan, Dorota; Fietkau, Rainer; Scholler, Axel; Nau, Carla; Stürzl, Michael; Croner, Roland S.; Prokosch, Hans-Ulrich; Toddenroth, Dennis (BMC Medical Informatics and Decision Making, 2013)
Background: The necessity to translate eligibility criteria from free text into decision rules that are compatible with data from the electronic health record (EHR) constitutes the main challenge when developing and deploying clinical trial recruitment support systems. Recruitment decisions based on case-based reasoning, i.e. using past cases rather than explicit rules, could dispense with the need for translating eligibility criteria and could also be implemented largely independently from the terminology of the EHR's database. We evaluated the feasibility of predictive modeling to assess the eligibility of patients for clinical trials and report on a prototype's performance for different system configurations. Methods. The prototype worked by using existing basic patient data of manually assessed eligible and ineligible patients to induce prediction models. Performance was measured retrospectively for three clinical trials by plotting receiver operating characteristic curves and comparing the area under the curve (ROC-AUC) for different prediction algorithms, different sizes of the learning set and different numbers and aggregation levels of the patient attributes. Results: Random forests were generally among the best performing models with a maximum ROC-AUC of 0.81 (CI: 0.72-0.88) for trial A, 0.96 (CI: 0.95-0.97) for trial B and 0.99 (CI: 0.98-0.99) for trial C. The full potential of this algorithm was reached after learning from approximately 200 manually screened patients (eligible and ineligible). Neither block- nor category-level aggregation of diagnosis and procedure codes influenced the algorithms' performance substantially. Conclusions: Our results indicate that predictive modeling is a feasible approach to support patient recruitment into clinical trials. Its major advantages over the commonly applied rule-based systems are its independency from the concrete representation of eligibility criteria and EHR data and its potential for automation. © 2013 Köpcke et al.; licensee BioMed Central Ltd.
UnivIS-Import:2015-04-14:Pub.2013.tech.IMMD.infome.evalua_3

Expression and localization of axin 2 in colorectal carcinoma and its clinical implication - Schaal, Ute; Grenz, Sandra; Merkel, Susanne; Rau, Tilman; Hadjihannas, Michel; Kremmer, Elisabeth; Chudasama, Priya; Croner, Roland S.; Behrens, Jürgen; Stürzl, Michael; Naschberger, Elisabeth (International Journal of Colorectal Disease, 2013)
Purpose: Aberrant activation of the Wnt/β-catenin pathway plays a major role in the development of colorectal carcinoma (CRC). Axin 2 is a key protein of this pathway and is upregulated in CRC. Here, we investigated RNA- and protein expression of axin 2 in CRC tissues at the single cell level. Moreover, the association of axin 2 with prognosis and survival was investigated in a large cohort of CRC patients (n = 280). Methods: Localization and expression of axin 2 and β-catenin was investigated using in situ hybridization and immunohistochemical staining. The quantitative expression levels of axin 2 were determined using RT-qPCR. The association of axin 2 expression with prognosis and survival of the patients was determined by statistical analysis (logrank test, Kaplan-Meier). Results: Our results confirmed the upregulation of axin 2 in CRC and showed that it is broadly expressed in the cytoplasm of the tumor epithelial cells both, in the tumor center and at the invasion front. Axin 2 was rarely expressed by tumor stromal cells and only weakly by normal colonic epithelial cells. Staining of β-catenin and axin 2 in consecutive CRC tissue sections revealed that nuclear translocation of β-catenin in the tumor front was not associated with changes in the cytoplasmic localization of axin 2. Axin 2 did not show any association with proven prognostic factors or survival of the CRC patients. Conclusion: The generally increased expression of axin 2 in all tumor stages as compared to normal tissue suggests an initiating pathogenic function in the development of CRC. © 2013 Springer-Verlag Berlin Heidelberg.
Created from Fastlane, Scopus look-up
Keywords: β-Catenin; Axin 2; Colorectal carcinoma; Wnt/β-catenin signaling

Expression of adhesion molecules, platelet-activating factor, and chemokines by Kaposi's sarcoma cells. - Sciacca, Francesca L; Stürzl, Michael; Bussolino, Federico; Sironi, Manuela; Brandstetter, Hans; Zietz, C; Zhou, D; Matteucci, C; Peri, G; Sozzani, Silvano (Journal of Immunology, 1994)
The present study was designed to investigate whether cells cultured from Kaposi's sarcoma (KS), a vascular tumor with a prominent leukocyte infiltration, express molecules important for the recruitment and activation of leukocytes. KS cells expressed intercellular adhesion molecule-1, which was augmented by exposure to IL-1 beta or TNF-alpha. Unlike endothelial cells, resting or cytokine-activated KS cells did not express appreciable levels of intercellular adhesion molecule-2, vascular cell adhesion molecule-1, and E-selectin on their surface. Weak expression of vascular cell adhesion molecule-1 mRNA was detectable by Northern blot analysis and, most clearly, by PCR analysis. Upon exposure to inflammatory cytokines, KS cells produced the attractant/activating lipid platelet-activating factor. KS cells expressed appreciable levels of the chemotactic cytokines, monocyte chemotactic protein-1 (MCP-1) and IL-8, as determined by Northern blot analysis, immunoassay, or bioassay. Chemokine production was augmented by IL-1 beta or TNF-alpha. MCP-1 expression was also detected in KS lesions by in situ hybridization. The set of molecules identified in the present study is probably important in determining the prominent leukocyte infiltration observed in KS. Tumor-associated leukocytes may amplify autocrine/paracrine circuits that sustain KS proliferation and contribute to recruitment of host vascular cells.

Expression of calcitonin receptor-like receptor in human vascular tumours. - Hagner, Stefanie; Stahl, Ulrich; Grimm, T.; Stürzl, Michael; Lang, R. E. (Journal of Clinical Pathology, 2006)
Background: Vascular tumours such as Kaposi’s sarcoma and capillary haemangioma are characterised by abnormal vascularisation and proliferation of endothelial cells or neoplastic cells. Adrenomedullin, a potent vasodilative peptide, and its receptor, calcitonin receptor-like receptor (CRLR), play an important part in angiogenesis. Aim: To establish whether this system also plays a part in vascular diseases, showing abnormal proliferation such as vascular tumours. Methods: CRLR expression was investigated in several specimens of Kaposi’s sarcoma and other vascular tumours, using immunohistochemical analysis with a previously described CRLR-specific polyclonal antibody and reverse transcriptase-polymerase chain reaction. Results: Intense and specific CRLR-immunoreactive staining of neoplastic cells was observed in all specimens, which was of greater intensity than similar staining of adjacent normal endothelium. Conclusions: CRLR is expressed in vascular tumours and, with adrenomedullin, may have a role in neoplastic vascular growth.

Expression of K13/v-FLIP gene of human herpesvirus 8 and apoptosis in Kaposi's sarcoma spindle cells. - Stürzl, Michael; Hohenadl, Christine; Zietz, Christian; Castanos-Velez, Esmeralda; Wunderlich, Anneliese; Ascherl, Gudrun; Biberfeld, Peter; Monini, Paolo; Browning, Philip J.; Ensoli, Barbara (Journal of the National Cancer Institute, 1999)
Human herpesvirus 8 (HHV8) infection is associated with all forms of Kaposi's sarcoma (KS). The HHV8 genome locus ORFK13-72-73 (ORF = open reading frame) encodes proteins that may be important in HHV8-mediated pathogenesis, i.e., the latency-associated nuclear antigen (encoded by ORF73), viral-cyc-D (v-cyc-D), a viral homologue of cellular cyclin D (encoded by ORF72), and viral-FLIP (v-FLIP), a homologue of the cellular FLICE (Fas-associated death domain-like interleukin 1 beta-converting enzyme) inhibitory protein (encoded by ORFK13; is an inhibitor of apoptosis [programmed cell death]). Through differential splicing events, this locus expresses individual RNA transcripts that encode all three proteins (tricistronic transcripts) or just two of them (v-FLIP and v-cyc-D; bicistronic transcripts). We examined expression of these transcripts in KS tissues. We collected tissues from patients with KS of different stages. By use of an optimized in situ hybridization procedure, we examined different ORFK13-72-73 locus transcripts in HHV8-infected cells in skin lesions and in one adjacent lymph node. Apoptosis in KS lesions was determined by use of an in situ assay. Our results indicate the following: 1) Transcripts from the ORFK13-72-73 locus appear to be spliced differentially in latently infected KS cells in skin lesions and in HHV8-infected cells in lymph nodes; specifically, ORFK13-ORF72 bicistronic transcripts were expressed abundantly in KS cells, whereas ORFK13-ORF72-ORF73 tricistronic transcripts were detected only in lymph node cells. 2) Sequences encoding the antiapoptotic protein v-FLIP are expressed at very low levels in early KS lesions, but expression increases dramatically in late-stage lesions. 3) The increase in expression of v-FLIP-encoding transcripts is associated with a reduction in apoptosis in KS lesions. These data suggest that functional v-FLIP is produced in vivo and that antiapoptotic mechanisms may be involved in the rapid growth of KS lesions, where only a few cells undergoing mitosis are generally observed. BACKGROUND METHODS RESULTS AND CONCLUSIONS IMPLICATIONS

Expression of platelet-derived growth factor and its receptor in AIDS-related Kaposi sarcoma in vivo suggests paracrine and autocrine mechanisms of tumor maintenance. - Stürzl, Michael; Roth, W K; Brockmeyer, Norbert H.; Zietz, C; Speiser, B; Hofschneider, Peter Hans (Proceedings of the National Academy of Sciences of the United States of America, 1992)
As previously described, proliferation of Kaposi sarcoma (KS)-derived cells in vitro is dependent on the presence of platelet-derived growth factor (PDGF). To test the hypothesis that PDGF may also be a major growth factor for KS cells in vivo, we performed in situ hybridization and immunohistochemical staining for PDGF and PDGF receptors in tissue sections of AIDS-related KS. The data suggest that KS consists of two types of tumor cells. (i) The main population are spindle-shaped cells with elongated nuclei (KS-s cells). They reveal a strong expression of PDGF beta receptors but do not express the PDGF-A and PDGF-B isoforms. (ii) A minor population of KS cells express PDGF beta receptor as well as PDGF-A and PDGF-B (KS-p cells). These cells are often grouped in whorls and surrounding vascular slits. They reveal spherical nuclei with evenly distributed chromatin and inconspicuous nucleoli. PDGF alpha receptor is not expressed in either form of KS cells. The results suggest that the isoforms of PDGF and the PDGF beta receptor are differentially expressed in two different cell types in KS and that PDGF isoforms may contribute to the pathogenesis of KS.

Fibrin gel-immobilized VEGF and bFGF efficiently stimulate angiogenesis in the AV loop model. - Arkudas, Andreas; Tjiawi, Jimmy; Bleiziffer, Oliver; Grabinger, Lucia; Polykandriotis, Elias; Beier, Justus P.; Stürzl, Michael; Horch, Raymund E.; Kneser, Ulrich (Molecular Medicine, 2007)
The modulation of angiogenic processes in matrices is of great interest in tissue engineering. We assessed the angiogenic effects of fibrin-immobilized VEGF and bFGF in an arteriovenous loop (AVL) model in 22 AVLs created between the femoral artery and vein in rats. The loops were placed in isolation chambers and were embedded in 500 microL fibrin gel (FG) (group A) or in 500 microL FG loaded with 0.1 ng/microL VEGF and 0.1 ng/microL bFGF (group B). After two and four weeks specimens were explanted and investigated using histological, morphometrical, and ultramorphological [scanning electron microscope (SEM) of vascular corrosion replicas] techniques. In both groups, the AVL induced formation of densely vascularized connective tissue with differentiated and functional vessels inside the fibrin matrix. VEGF and bFGF induced significantly higher absolute and relative vascular density and a faster resorption of the fibrin matrix. SEM analysis in both groups revealed characteristics of an immature vascular bed, with a higher vascular density in group B. VEGF and bFGF efficiently stimulated sprouting of blood vessels in the AVL model. The implantation of vascular carriers into given growth factor-loaded matrix volumes may eventually allow efficient generation of axially vascularized, tissue-engineered composites.
Keywords: Vascular Endothelial Growth Factor (VEGF); Fibrin Matrix; Arteriovenous Loop (AVL); Vascular Carrier; High Vascular Density

Gamma interferon-induced guanylate binding protein 1 is a novel actin cytoskeleton remodeling factor - Ostler, Nicole; Britzen-Laurent, Nathalie; Liebl, Andrea; Naschberger, Elisabeth; Lochnit, Guenter; Ostler, Markus; Forster, Florian; Kunzelmann, Peter; Ince, Semra; Supper, Verena; Praefcke, Gerrit J. K.; Schubert, Dirk W.; et al. (Molecular and Cellular Biology, 2014)
Gamma interferon (IFN-?) regulates immune defenses against viruses, intracellular pathogens, and tumors by modulating cell proliferation, migration, invasion, and vesicle trafficking processes. The large GTPase guanylate binding protein 1 (GBP-1) is among the cellular proteins that is the most abundantly induced by IFN-? and mediates its cell biologic effects. As yet, the molecular mechanisms of action of GBP-1 remain unknown. Applying an interaction proteomics approach, we identified actin as a strong and specific binding partner of GBP-1. Furthermore, GBP-1 colocalized with actin at the subcellular level and was both necessary and sufficient for the extensive remodeling of the fibrous actin structure observed in IFN-?-exposed cells. These effects were dependent on the oligomerization and the GTPase activity of GBP-1. Purified GBP-1 and actin bound to each other, and this interaction was sufficient to impair the formation of actin filaments in vitro, as demonstrated by atomic force microscopy, dynamic light scattering, and fluorescence-monitored polymerization. Cosedimentation and band shift analyses demonstrated that GBP-1 binds robustly to globular actin and slightly to filamentous actin. This indicated that GBP-1 may induce actin remodeling via globular actin sequestering and/or filament capping. These results establish GBP-1 as a novel member within the family of actin-remodeling proteins specifically mediating IFN-?-dependent defense strategies.
EVALuna2:15143

GBP-1 acts as a tumor suppressor in colorectal cancer cells - Britzen-Laurent, Nathalie; Lipnik, Karoline; Ocker, Matthias; Naschberger, Elisabeth; Schellerer, Vera; Croner, Roland S.; Vieth, Michael; Waldner, Maximilian; Steinberg, Pablo; Hohenadl, Christine; Stürzl, Michael (Carcinogenesis, 2013)
The human guanylate-binding protein 1 (GBP-1) is among the proteins the most highly induced by interferon-γ (IFN-γ) in every cell type investigated as yet. In vivo, GBP-1 expression is associated with the presence of inflammation and has been observed in autoimmune diseases, inflammatory bowel diseases (IBD) and cancer. In colorectal carcinoma (CRC), the expression of GBP-1 in the desmoplastic stroma has been previously reported to correlate with the presence of an IFN-γ-dominated T helper type 1 (Th1) micromilieu and with an increased cancer-related 5-year survival. In the present study, the analysis of GBP-1 expression in a series of 185 CRCs by immunohistochemistry confirmed that GBP-1 is expressed in stroma cells of CRCs and revealed a significantly less frequent expression in tumor cells, which was contradictory with the broad inducibility of GBP-1. Furthermore, three of six CRC cell lines treated with IFN-γ were unable to express GBP-1 indicating that colorectal tumor cells tend to downregulate GBP-1. On the contrary, non-transformed colon epithelial cells strongly expressed GBP-1 in vitro in presence of IFN-γ and in vivo in inflammatory bowel diseases. Reconstitution of GBP-1 expression in a negative CRC cell line inhibited cell proliferation, migration and invasion. Using RNA interference, we showed that GBP-1 mediates the antitumorigenic effects of IFN-γ in CRC cells. In addition, GBP-1 was able to inhibit tumor growth in vivo. Altogether, these results suggested that GBP-1 acts directly as a tumor suppressor in CRC and the loss of GBP-1 expression might indicate tumor evasion from the IFN-γ-dominated Th1 immune response. © The Author 2012. Published by Oxford University Press. All rights reserved.
Created from Fastlane, Scopus look-up

Gene expression analysis of ischaemia and reperfusion in human microsurgical free muscle tissue transfer. - Dragu, Adrian; Schnuerer, Stefan; Surmann-Schmitt, Cordula; von der Mark, Klaus; Stürzl, Michael; Unglaub, Frank; Wolf, Maya B.; Leffler, Mareike; Beier, Justus; Kneser, Ulrich; Horch, Raymund E. (Journal of Cellular and Molecular Medicine, 2011)
The aim of this study was to analyse various gene expression profiles of muscle tissue during normoxia, ischaemia and after reperfusion in human muscle free flaps, to gain an understanding of the occurring regulatory, inflammatory and apoptotic processes on a cellular and molecular basis. Eleven Caucasian patients with soft tissue defects needing coverage with microsurgical free muscle flaps were included in this study. In all patients, the muscle samples were taken from free myocutaneous flaps. The first sample was taken before induction of ischaemia in normoxia (I), another one after ischaemia (II), and the last one was taken after reperfusion (III). The samples were analysed using DNA-microarray, real-time-quantitative-PCR and immunohistochemistry. DNA-microarray analysis detected multiple, differentially regulated genes when comparing the different groups (I-III) with statistical significance. Comparing ischaemia (II) versus normoxia (I) educed 13 genes and comparing reperfusion (III) versus ischaemia (II) educed 19 genes. The comparison of reperfusion (III) versus normoxia (I) yielded 100 differentially regulated genes. Real-time-quantitative-PCR confirmed the results of the DNA-microarrays for a subset of four genes (CASP8, IL8, PLAUR and S100A8). This study shows that ischaemia and reperfusion induces alterations on the gene expression level in human muscle free flaps. Data may suggest that the four genes CASP8, IL8, PLAUR and S100A8 are of great importance in this context. We could not confirm the DNA-microarry and real-time-quantitative-PCR results on the protein level. Finally, these findings correspond with the surgeon's clinical experience that the accepted times of ischaemia, generally up to 90 min., are not sufficient to induce pathophysiological processes, which can ultimately lead to flap loss. When inflammatory and apoptotic proteins are expressed at high levels, flap damage might occur and flap loss is likely. The sole expression on mRNA level might explain why flap loss is unlikely.

Guanylate-binding protein 1 expression from embryonal endothelial progenitor cells reduces blood vessel density and cellular apoptosis in an axially vascularised tissue-engineered construct - Bleiziffer, Oliver; Hammon, Matthias; Arkudas, Andreas; Taeger, Christian; Beier, Justus; Amann, Kerstin Ute; Naschberger, Elisabeth; Stürzl, Michael; Horch, Raymund E.; Kneser, Ulrich (BMC Biotechnology, 2012)
Background: Guanylate binding protein-1 (GBP-1) is a large GTPase which is actively secreted by endothelial cells. It is a marker and intracellular inhibitor of endothelial cell proliferation, migration, and invasion. We previously demonstrated that stable expression of GBP-1 in murine endothelial progenitor cells (EPC) induces their premature differentiation and decreases their migration capacity in vitro and in vivo. The goal of the present study was to assess the antiangiogenic capacity of EPC expressing GBP-1 (GBP-1-EPC) and their impact on blood vessel formation in an axially vascularized 3-D bioartificial construct in vivo.Results: Functional in vitro testing demonstrated a significant increase in VEGF secretion by GBP-1-EPC after induction of cell differentiation. Undifferentiated GBP-1-EPC, however, did not secrete increased levels of VEGF compared to undifferentiated control EPC expressing an empty vector (EV-EPC). In our In vivo experiments, we generated axially vascularized tissue-engineered 3-D constructs. The new vascular network arises from an arterio-venous loop (AVL) embedded in a fibrin matrix inside a separation chamber. Total surface area of the construct as calculated from cross sections was larger after transplantation of GBP-1-EPC compared to control EV-EPC. This indicated reduced formation of fibrovascular tissue and less resorption of fibrin matrix compared to constructs containing EV-EPC. Most notably, the ratio of blood vessel surface area over total construct surface area in construct cross sections was significantly reduced in the presence of GBP-1-EPC. This indicates a significant reduction of blood vessel density and thereby inhibition of blood vessel formation from the AVL constructs caused by GBP-1. In addition, GBP-1 expressed from EPC significantly reduced cell apoptosis compared to GBP-1-negative controls.Conclusion: Transgenic EPC expressing the proinflammatory antiangiogenic GTPase GBP-1 can reduce blood vessel density and inhibit apoptosis in a developing bioartificial vascular network and may become a new powerful tool to manipulate angiogenetic processes in tissue engineering and other pathological conditions such as tumour angiogenesis. © 2012 Bleiziffer et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Endothelial progenitor cells; Guanylate-binding protein 1; In vivo tissue engineering

Guanylate-binding protein-1 expression is selectively induced by inflammatory cytokines and is an activation marker of endothelial cells during inflammatory diseases - Naschberger, Elisabeth; Stürzl, Michael; et al. (American Journal of Pathology, 2002)
During angiogenesis and inflammatory processes, endothelial cells acquire different activation phenotypes, whose identification may help in understanding the complex network of angiogenic and inflammatory interactions in vivo. To this goal we investigated the expression of the human guanylate-binding protein (GBP)-1 that is highly induced by inflammatory cytokines (ICs) and, therefore, may characterize IC-activated cells. Using a new rat monoclonal antibody raised against GBP-1, we show that GBP-1 is a cytoplasmic protein and that its expression in endothelial cells is selectively induced by interferon-γ, interleukin-1α, interleukin-1β, or tumor necrosis factor-α, but not by other cytokines, chemokines, or growth factors. Moreover, we found that GBP-1 expression is highly associated with vascular endothelial cells as confirmed by the simultaneous detection of GBP-1 and the endothelial cell-associated marker CD31 in a broad range of human tissues. Notably, GBP-1 expression was undetectable in the skin, but it was highly induced in vessels of skin diseases with a high-inflammatory component including psoriasis, adverse drug reactions, and Kaposi's sarcoma. These results indicate that GBP-1 is a novel cellular activation marker that characterizes the IC-activated phenotype of endothelial cells.
Created from Fastlane, Scopus look-up

Guanylate binding protein-1 inhibits spreading and migration of endothelial cells through induction of integrin α4 expression - Weinlaender, Kristina; Naschberger, Elisabeth; Lehmann, Michael H.; Tripal, Philipp; Paster, Wolfgang; Stockinger, Hannes; Hohenadl, Christine; Stürzl, Michael (The FASEB Journal, 2008)
Human guanylate binding protein-1 (GBP-1) is a large GTPase that is induced by inflammatory cytokines and acts antiangiogenically through the inhibition of endothelial cell proliferation and migration. In this study, we detected that GBP-1-expressing cells show a significantly reduced spreading and migration on fibronectin matrices. Investigating possible mechanisms of these effects, we found that integrin α4 (ITGA4) was consistently up-regulated at both the RNA and protein level in GBP-1-expressing cell cultures. Inhibition of cell spreading and migration by GBP-1 was dependent on the binding of ITGA4 to fibronectin. The inflammatory cytokines IL-1β and TNF-α induced ITGA4 expression in HUVECs and inhibited spreading and migration. Knockdown of GBP-1 by shRNA abrogated inflammatory cytokine induced ITGA4 expression and restored spreading and migration capabilities of the cells. These results show that inhibition of endothelial cell spreading and migration by inflammatory cytokines is mediated by GBP-1 through induction of ITGA4 expression. Endothelial cell migration is a key process during angiogenesis. Therefore, ITGA4 may be a novel molecular target to modulate angiogenesis in human disease. © FASEB.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Inflammation; Integrins; Large GTPase

Guanylate binding protein 1-mediated interaction of T cell antigen receptor signaling with the cytoskeleton - Forster, Florian; Paster, Wolfgang; Supper, Verena; Schatzlmaier, Philipp; Sunzenauer, Stefan; Ostler, Nicole; Saliba, Anna; Eckerstorfer, Paul; Britzen-Laurent, Nathalie; Schuetz, Gerhard; Schmid, Johannes A.; Zlabinger, Gerhard J.; et al. (Journal of Immunology, 2014)
GTPases act as important switches in many signaling events in cells. Although small and heterotrimeric G proteins are subjects of intensive studies, little is known about the large IFN-inducible GTPases. In this article, we show that the IFN-?-inducible guanylate binding protein 1 (GBP-1) is a regulator of T cell activation. Silencing of GBP-1 leads to enhanced activation of early T cell Ag receptor/CD3 signaling molecules, including Lck, that is translated to higher IL-2 production. Mass spectrometry analyses showed that regulatory cytoskeletal proteins, like plastin-2 that bundles actin fibers and spectrin ?-chain, brain 1 that links the plasma membrane to the actin cytoskeleton, are binding partners of GBP-1. The spectrin cytoskeleton influences cell spreading and surface expression of TCR/CD3 and the leukocyte phosphatase CD45. We found higher cell spreading and enhanced surface expression of TCR/CD3 and CD45 in GBP-1 silenced T cells that explain their enhanced TCR/CD3 signaling. We conclude that GBP-1 is a downstream processor of IFN-? via which T cells regulate cytoskeleton-dependent cell functions.
EVALuna2:15147

HHV-8 and multistep tumorigenesis. - Ensoli, Barbara; Stürzl, Michael (Trends in Microbiology, 1999)
Human herpesvirus 8 [HHV-8 or Kaposi’s sarcoma-associated herpesvirus (KSHV)] is associated with pleural effusion lymphoma (PEL), multicentric Castleman’s disease (MCD) and Kaposi’s sarcoma (KS) 1. These diseases are rare, but HHV-8 can infect more than 50% of the general population, depending on the geographical area. This indicates that additional factors are required for HHV-8 pathogenicity 1. This is not surprising, as the concept of multistep tumorigenesis is now generally accepted and it does not rule out an etiologic role for HHV-8 in tumor development.
Keywords: Virology; Microbiology; Cell biology; Kaposi's sarcoma; Human herpesvirus-8; Cytokine; Angiogenesis; Pleural effusion lymphomas; Multicentric Castelman's disease

High throughput screening of gene functions in mammalian cells using reversely transfected cell arrays: review and protocol. - Stürzl, Michael; Konrad, Andreas; Sander, Gaby; Wies, Effi; Neipel, Frank; Naschberger, Elisabeth; Reipschlaeger, Simone; Gonin-Laurent, Nathalie; Horch, Raymund E.; Kneser, Ulrich; Hohenberger, Werner; Erfle, Holger; et al. (Combinatorial Chemistry & High Throughput Screening, 2008)
Reversely transfected cell microarrays (RTCM) have been introduced as a method for parallel high throughput analysis of gene functions in mammalian cells. Hundreds to thousands of different recombinant DNA or RNA molecules can be transfected into different cell clusters at the same time on a single glass slide with this method. This allows either the simultaneous overexpression or–by using the recently developed RNA interference (RNAi) techniques–knockdown of a huge number of target genes. A growing number of sophisticated detection systems have been established to determine quantitatively the effects of the transfected molecules on the cell phenotype. Several different cell types have been successfully used for this procedure. This review summarizes the presently available knowledge on this technique and provides a laboratory protocol.

HIV-1 Tat increases the adhesion of monocytes and T-cells to the endothelium in vitro and in vivo: implications for AIDS-associated vasculopathy. - Matzen, Kathrin; Dirkx, Anita E.M; Egbrink, Mirjam G.Aoude; Speth, Cornelia; Götte, Matthias; Ascherl, Gudrun; Grimm, Thomas; Griffioen, Arjan W; Stürzl, Michael (Virus Research, 2004)
HIV-1-infected patients exhibit severe damages of the aortic endothelium, develop angioproliferative lesions such as Kaposi's sarcoma (KS), and have an increased risk of cardiovascular diseases and atherosclerosis. An increased adhesion of leukocytes to the endothelium is a common pathogenic parameter of AIDS-associated vascular diseases. Here we show that the HIV-1 Tat protein, a regulatory protein of HIV-1 released by infected cells, and TNF-alpha, a cytokine increased in sera and tissues of HIV-1-infected patients, activate synergistically the adhesion of leukocytes to endothelial cells both in vitro and in vivo. This effect is selectively mediated by HIV-1 Tat, since HIV-1 Nef, another HIV-1 regulatory protein, and the HIV-1 envelope protein gp41, had no effect. In vitro adhesion assays with PBMC and quantitative cell type analysis of adherent cells by FACS demonstrated that HIV-1 Tat selectively activates the adhesion of T-cells and monocytes but not of B-cells. Intravital microscopic studies in mice confirmed the synergistic activity of HIV-1 Tat and TNF-alpha on leukocyte adhesion to the endothelium in vivo. These data indicate that HIV-1 Tat in cooperation with TNF-alpha may contribute to the vascular damage and cardiovascular diseases observed in AIDS patients but also to the prominent extravasation of T-cells and monocytes which is a key process in the formation and progression of KS lesions.

Human guanylate binding protein-1 (hGBP-1) characterizes and establishes a non-angiogenic endothelial cell activation phenotype in inflammatory diseases - Naschberger, Elisabeth; Stürzl, Michael; et al. (Advances in Enzyme Regulation, 2005)
Blood vessel activation in inflammatory diseases is triggered by a myriad of different factors that partially reveal opposite activities on endothelial cells (EC). For example, inflammatory cytokines (IC) inhibit EC proliferation and induce cell adhesiveness for leukocytes. In contrast, angiogenic growth factors (AGF) activate EC proliferation and inhibit cell adhesiveness for leukocytes. In consequence, IC and AGF may induce two different activation phenotypes in EC that appear in a temporally and/or spatially coordinated manner in inflammatory tissues. Human guanylate binding protein-1 (hGBP-1) is a member of the large GTPase protein family. New results demonstrate that hGBP-1 is a specific marker of IC-activated EC that allows to differentiate the IC- and AGF-activated phenotype of EC at the single cell level, both in vitro and in vivo. In addition, hGBP-1 is the key mediator of the inhibitory effects of IC on EC proliferation and invasiveness. Both the expression pattern of hGBP-1 and its activity in EC supported the hypothesis that IC- and AGF-activation induce distinct adversely related phenotypes in EC. In future, hGBP-1 may be used as a marker to monitor the IC-induced phenotype of EC in inflammation and may also be exploited as a target to modulate EC activity in inflammatory diseases and tumor angiogenesis. © 2005 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up

Human guanylate binding protein-1 is a secreted GTPase present in increased concentrations in the cerebrospinal fluid of patients with bacterial meningitis - Naschberger, Elisabeth; Stürzl, Michael; et al. (American Journal of Pathology, 2006)
Created from Fastlane, Scopus look-up

Human herpesvirus-8 and Kaposi's sarcoma: relationship with the multistep concept of tumorigenesis. - Stürzl, Michael; Zietz, Christian; Monini, Paolo; Ensoli, Barbara (Advances in Cancer Research, 2001)
Kaposi's sarcoma (KS) develops through discrete inflammatory-angiogenic stages of polyclonal nature (early-stage lesions) to monomorphic nodules of spindle-shaped cells that can be clonal (late-stage lesions) and resemble true sarcomas. Molecular and epidemiological studies indicate that development of KS is tightly associated with infection by the human herpesvirus-8 (HHV-8). However, only individuals with specific conditions of immunodysregulation develop KS. In these individuals the systemic and tissue increase of Th-1-type cytokines (IC) reactivate HHV-8 infection, leading to increased viral load, antibody titers, and an expanded cell tropism that precedes the clinical appearance of KS. Recruitment of the virus into tissues by infected monocytes and other cell types is facilitated by the endothelial cell activation due to IC. In clinical lesions, HHV-8 infection increases with lesion stage and in late-stage lesions most of the spindle cells are latently infected, whereas only few lyrically infected cells are present, suggesting that latent genes may have a role in the transformation of the early inflammatory-hyperplastic lesion into a real sarcoma. The development of tumors, however, is regulated through a multistep process based on the acquisition by cells of several different capabilities leading to malignant growth. Here we review the available data on the expression of HHV-8-encoded genes in primary KS lesions and, in view of their biological activity, analyze their potential function in different steps of tumorigenesis. By this pragmatic approach interesting insights into potential key functions of HHV-8-encoded genes are found and steps of potential cooperativity with other viral factors (HIV-1-Tat) in the pathogenesis of KS are identified.

Human herpesvirus-8 (HHV-8) gene expression in Kaposi's sarcoma (KS) primary lesions: an in situ hybridization study. - Stürzl, Michael; Wunderlich, A; Ascherl, Gudrun; Hohenadl, C; Monini, Paolo; Zietz, Christian; Browning, Philip J.; Neipel, Frank; Biberfeld, Peter; Ensoli, Barbara (Leukemia, 1999)

Hypoxia generates a more invasive phenotype of tumour cells: An in vivo experimental setup based on the chorioallantoic membrane - Demir, Resit; Naschberger, Elisabeth; Demir, Ilknur; Melling, Nathaniel; Dimmler, Arno; Papadopoulus, Thomas; Stürzl, Michael; Klein, Peter; Hohenberger, Werner (Pathology & Oncology Research, 2009)
Of all processes involved in carcinogenesis, local invasion and the formation of metastases are the clinically most relevant but the scientifically least well understood at their molecular level. Recent experimental progress has identified that tumour hypoxia not only induces tumour angiogenesis, but also modulates the expression of several genes that have been implicated in tumour invasion and metastasis. Here we developed an in vivo model to understand a number of molecular pathways and cellular mechanisms for tumour invasion in hypoxia. For this purpose fertilized chicken eggs were incubated for 10 days in normoxic conditions. Subsequently colon carcinoma cells (SW-480) were placed on the chorioallantoic membrane. During the following 6 days the eggs were incubated either in normoxic conditions or in stepwise decreasing hypoxic conditions. SW-480 colon carcinoma cells did not invade the epithelial layer in normoxic conditions. In contrast an invasion through the epithelial layer in to the mesoderm was already seen after 3 days when incubated in hypoxic conditions. The chorioallantoic membrane assay described in this paper allows investigating tumour invasion and its cellular mechanisms under defined hypoxic conditions. © 2008 Arányi Lajos Foundation.
Created from Fastlane, Scopus look-up
Keywords: Chorioallantoic membrane; Hypoxia; Tumor progression; Tumour invasion

Identification of interleukin-1 and platelet-derived growth factor-B as major mitogens for the spindle cells of Kaposi's sarcoma: a combined in vitro and in vivo analysis. - Stürzl, Michael; Brandstetter, H; Zietz, Christian; Eisenburg, B; Raivich, G; Gearing, D P; Brockmeyer, Norbert H.; Hofschneider, Peter Hans (Oncogene, 1995)
By means of a combined in vitro and in vivo analysis we provide evidence that IL-1 beta and PDGF-B, but not OSM (oncostatin M) or IL-6, are major mitogens for the spindle cells of Kaposi's sarcoma (KS) in vivo. PDGF-B and IL-1 beta stimulated proliferation of cultivated KS spindle cells in vitro. Analysis of gene expression in vivo revealed that both factors as well as the PDGF beta-receptor are present in KS lesions. By contrast, IL-6 had no effect and OSM inhibited proliferation of cultivated KS spindle cells. Again, the effect of these factors on cultivated KS spindle cells in vitro was reflected by the gene expression observed in KS lesions in vivo. Neither the expression of IL-6 receptor nor of OSM could be detected in KS lesions by in situ hybridization. Moreover, in situ hybridization revealed an identical pattern of gene expression in cultivated KS spindle cells and KS spindle cells in vivo with respect to the above-mentioned cytokines [PDGF-B, IL-1 beta, IL-1 alpha, IL-6, OSM] and their receptors [PDGF beta-receptor, gp130, IL-6 receptor, leukemia inhibitory factor (LIF) receptor]. This further supported the suitability of cultivated KS spindle cells as an in vitro model in order to determine which cytokines may activate proliferation of KS spindle cells in vivo.

Identification of Predictive Markers for Response to Neoadjuvant Chemoradiation in Rectal Carcinomas by Proteomic Isotope Coded Protein Label (ICPL) Analysis - Croner, Roland S.; Sevim, Muezeyyen; Metodiev, Metodi V.; Jo, Peter; Ghadimi, Michael; Schellerer, Vera; Brunner, Michaela; Geppert, Carol-Immanuel; Rau, Tilman; Stürzl, Michael; Naschberger, Elisabeth; Matzel, Klaus E.; et al. (International Journal of Molecular Sciences, 2016)
Neoadjuvant chemoradiation (nCRT) is an established procedure in stage union internationale contre le cancer (UICC) II/III rectal carcinomas. Around 53% of the tumours present with good tumor regression after nCRT, and 8%-15% are complete responders. Reliable selection markers would allow the identification of poor or non-responders prior to therapy. Tumor biopsies were harvested from 20 patients with rectal carcinomas, and stored in liquid nitrogen prior to therapy after obtaining patients' informed consent (Erlangen-No.3784). Patients received standardized nCRT with 5-Fluoruracil (nCRT I) or 5-Fluoruracil ± Oxaliplatin (nCRT II) according to the CAO/ARO/AIO-04 protocol. After surgery, regression grading (Dworak) of the tumors was performed during histopathological examination of the specimens. Tumors were classified as poor (Dworak 1 + 2) or good (Dworak 3 + 4) responders. Laser capture microdissection (LCM) for tumor enrichment was performed on preoperative biopsies. Differences in expressed proteins between poor and good responders to nCRT I and II were identified by proteomic analysis (Isotope Coded Protein Label, ICPL(TM)) and selected markers were validated by immunohistochemistry. Tumors of 10 patients were classified as histopathologically poor (Dworak 1 or 2) and the other 10 tumor samples as histopathologically good (Dworak 3 or 4) responders to nCRT after surgery. Sufficient material in good quality was harvested for ICPL analysis by LCM from all biopsies. We identified 140 differentially regulated proteins regarding the selection criteria and the response to nCRT. Fourteen of these proteins were synchronously up-regulated at least 1.5-fold after nCRT I or nCRT II (e.g., FLNB, TKT, PKM2, SERINB1, IGHG2). Thirty-five proteins showed a complete reciprocal regulation (up or down) after nCRT I or nCRT II and the rest was regulated either according to nCRT I or II. The protein expression of regulated proteins such as PLEC1, TKT, HADHA and TAGLN was validated successfully by immunohistochemistry. ICPL is a valid method to identify differentially expressed proteins in rectal carcinoma tissue between poor vs. good responders to nCRT. The identified protein markers may act as selection criteria for nCRT in the future, but our preliminary findings must be reproduced and validated in a prospective cohort.
EVALuna2:6749

IFN-γ and TNF-α-induced GBP-1 inhibits epithelial cell proliferation through suppression of β-catenin/TCF signaling - Capaldo, C. T.; Beeman, N.; Hilgarth, R. S.; Nava, Porfirio; Louis, N. A.; Naschberger, Elisabeth; Stürzl, Michael; Parkos, C. A.; Nusrat, A. (Mucosal Immunology, 2012)
Proinflammatory cytokines induce guanylate-binding protein 1 (GBP-1) protein expression in intestinal epithelial tissues. GBP-1 has been described as influencing a number of cellular processes important for epithelial homeostasis, including cell proliferation. However, many questions remain as to the role of GBP-1 in intestinal mucosal homeostasis. We therefore sought to investigate the function of proinflammatory cytokine-induced GBP-1 during intestinal epithelial cell proliferation. Through the use of complementary GBP-1 overexpression and small interfering RNA-mediated knockdown studies, we now show that GBP-1 acts to inhibit pro-mitogenic β-catenin/T cell factor (TCF) signaling. Interestingly, proinflammatory cytokine-induced GBP-1 was found to be a potent suppressor of β-catenin protein levels and β-catenin serine 552 phosphorylation. Neither glycogen synthase kinase 3β nor proteasomal inhibition alleviated GBP-1-mediated suppression of cell proliferation or β-catenin/TCF signaling, indicating a non-canonical mechanism of β-catenin inhibition. Together, these data show that cytokine-induced GBP-1 retards cell proliferation by forming a negative feedback loop that suppresses β-catenin/TCF signaling. © 2012 Society for Mucosal Immunology.
Created from Fastlane, Scopus look-up

IFN-γ-driven intratumoral microenvironment exhibits superior prognostic effect compared with an IFN-α-driven microenvironment in patients with colon carcinoma - Grenz, Sandra; Naschberger, Elisabeth; Merkel, Susanne; Britzen-Laurent, Nathalie; Schaal, Ute; Konrad, Andreas; Aigner, Michael; Rau, Tilman; Hartmann, Arndt; Croner, Roland S.; Hohenberger, Werner; Stürzl, Michael (American Journal of Pathology, 2013)
Interferon (IFN)-α and IFN-γ are cytokines with potent immunomodulating and anti-tumor activities. It is unknown which of the two IFNs may be more potent in the regulation of an anti-tumorigenic response in colorectal carcinoma or whether both cytokines cooperate. We, therefore, established human myxovirus resistance protein A and human guanylate-binding protein-1 as markers for the differential detection of IFN-α- and IFN-γ-driven tumor micromilieus, respectively. In vitro studies with different cultures of tumor cells from colorectal carcinoma and stroma cells showed that the expression of myxovirus resistance protein A was exclusively induced by IFN-α, whereas guanylate-binding protein-1 was strongly induced by IFN-γ and only weakly by IFN-α. This expression pattern was used to distinguish cell activation caused by the two cytokines in a clinical cohort of patients with colon carcinoma (n = 378). Patients with primary tumors expressing only guanylate-binding protein-1 exhibited the highest cancer-specific 5-year survival (94.0%, P = 0.006) compared with those expressing both factors (90.3%, P = 0.006), myxovirus resistance protein A alone (83.5%, P = 0.096), or none (72.8%). Our study describes a successful proof-of-principle approach that complex cytokine interaction networks can be dissected in human tissues and demonstrates that an IFN-γ-driven tumor microenvironment exhibits a superior prognostic effect compared with an IFN-α-driven tumor microenvironment in colon carcinoma. © 2013 American Society for Investigative Pathology.
Created from Fastlane, Scopus look-up

IFN-γ drives inflammatory bowel disease pathogenesis through VE-cadherin-directed vascular barrier disruption - Langer, Victoria; Vivi, Eugenia; Regensburger, Daniela; Winkler, Thomas; Waldner, Maximilian; Rath, Timo; Schmid, Benjamin; Skottke, Lisa; Lee, Somin; Jeon, Noo Li; Wohlfahrt, Thomas; Kramer, Viktoria; et al. (Journal of Clinical Investigation, 2019)
Inflammatory bowel disease (IBD) is a chronic inflammatory disorder with rising incidence. Diseased tissues are heavily vascularized. Surprisingly, the pathogenic impact of the vasculature in IBD and the underlying regulatory mechanisms remain largely unknown. IFN-γ is a major cytokine in IBD pathogenesis, but in the context of the disease, it is almost exclusively its immune-modulatory and epithelial cell-directed functions that have been considered. Recent studies by our group demonstrated that IFN-γ also exerts potent effects on blood vessels. Based on these considerations, we analyzed the vessel-directed pathogenic functions of IFN-γ and found that it drives IBD pathogenesis through vascular barrier disruption. Specifically, we show that inhibition of the IFN-γ response in vessels by endothelial-specific knockout of IFN-γ receptor 2 ameliorates experimentally induced colitis in mice. IFN-γ acts pathogenic by causing a breakdown of the vascular barrier through disruption of the adherens junction protein VE-cadherin. Notably, intestinal vascular barrier dysfunction was also confirmed in human IBD patients, supporting the clinical relevance of our findings. Treatment with imatinib restored VE-cadherin/adherens junctions, inhibited vascular permeability, and significantly reduced colonic inflammation in experimental colitis. Our findings inaugurate the pathogenic impact of IFN-γ-mediated intestinal vessel activation in IBD and open new avenues for vascular-directed treatment of this disease.

IFN-γ-response mediator GBP-1 represses human cell proliferation by inhibiting the Hippo signaling transcription factor TEAD - Unterer, Bea; Wiesmann, Veit; Gunasekaran, Mekala; Sticht, Heinrich; Tenkerian, Clara; Behrens, Jürgen; Leone, Marina; Engel, Felix; Britzen-Laurent, Nathalie; Naschberger, Elisabeth; Wittenberg, Thomas; Stürzl, Michael (Biochemical Journal, 2018)
Interferon-gamma (IFN-γ) is a pleiotropic cytokine that exerts important functions in inflammation, infectious diseases, and cancer. The large GTPase human guanylate-binding protein 1 (GBP-1) is among the most strongly IFN-γ-induced cellular proteins. Previously, it has been shown that GBP-1 mediates manifold cellular responses to IFN-γ including the inhibition of proliferation, spreading, migration, and invasion and through this exerts anti-tumorigenic activity. However, the mechanisms of GBP-1 anti-tumorigenic activities remain poorly understood. Here, we elucidated the molecular mechanism of the human GBP-1-mediated suppression of proliferation by demonstrating for the first time a cross-talk between the anti-tumorigenic IFN-γ and Hippo pathways. The α9-helix of GBP-1 was found to be sufficient to inhibit proliferation. Protein-binding and molecular modeling studies revealed that the α9-helix binds to the DNA-binding domain of the Hippo signaling transcription factor TEA domain protein (TEAD) mediated by the 376VDHLFQK382 sequence at the N-terminus of the GBP-1-α9-helix. Mutation of this sequence resulted in abrogation of both TEAD interaction and suppression of proliferation. Further on, the interaction caused inhibition of TEAD transcriptional activity associated with the down-regulation of TEAD-target genes. In agreement with these results, IFN-γ treatment of the cells also impaired TEAD activity, and this effect was abrogated by siRNA-mediated inhibition of GBP-1 expression. Altogether, this demonstrated that the α9-helix is the proliferation inhibitory domain of GBP-1, which acts independent of the GTPase activity through the inhibition of the Hippo transcription factor TEAD in mediating the anti-proliferative cell response to IFN-γ.
EVALuna2:34818

IL-3 orchestrates ulcerative colitis pathogenesis by controlling the development and the recruitment of splenic reservoir neutrophils - Benard, Alan; Mittelstädt, Anke; Klösch, Bettina; Glanz, Karolina; Müller, Jan; Schoen, Janina; Nüse, Björn; Brunner, Maximilian; Naschberger, Elisabeth; Stürzl, Michael; Mattner, Jochen; Munoz, Luis Enrique; et al. (Cell Reports, 2023)
Inflammatory bowel diseases (IBDs) are a global health issue with an increasing incidence. Although the pathogenesis of IBDs has been investigated intensively, the etiology of IBDs remains enigmatic. Here, we report that interleukin-3 (Il-3)-deficient mice are more susceptible and exhibit increased intestinal inflammation during the early stage of experimental colitis. IL-3 is locally expressed in the colon by cells harboring a mesenchymal stem cell phenotype and protects by promoting the early recruitment of splenic neutrophils with high microbicidal capability into the colon. Mechanistically, IL-3-dependent neutrophil recruitment involves CCL5+ PD-1high LAG-3high T cells, STAT5, and CCL20 and is sustained by extramedullary splenic hematopoiesis. During acute colitis, Il-3−/− show, however, increased resistance to the disease as well as reduced intestinal inflammation. Altogether, this study deepens our understanding of IBD pathogenesis, identifies IL-3 as an orchestrator of intestinal inflammation, and reveals the spleen as an emergency reservoir for neutrophils during colonic inflammation.
CRIS-Team Scopus Importer:2023-06-23
Keywords: CCL5; colitis; CP: Immunology; interleukin-3; neutrophils; spleen

Impact of selective anti-BMP9 treatment on tumor cells and tumor angiogenesis - Brand, Verena; Lehmann, Christian; Umkehrer, Christian; Bissinger, Stefan; Thier, Martina; De Wouters, Mariana; Raemsch, Romi; Jucknischke, Ute; Haas, Alexander; Breuer, Sebastian; Birzele, Fabian; Racek, Tomas; et al. (Molecular Oncology, 2016)
The role of bone morphogenic protein 9 (BMP9) signaling in angiogenesis has been controversial, with a number of studies showing that it acts either as a pro-angiogenic or, conversely, as an anti-angiogenic factor in a context-dependent manner. Notably, BMP9 was also reported to function in both pro- or anti-tumorigenic roles during tumor progression. It has therefore remained unclear, whether selective BMP9 inhibition is a useful target for antibody therapy of cancer. To shed light on these questions, we characterized BMP9 expression in plasma of patients with different cancer indications and found elevated levels of pro-domains and precursor BMP9 with a strong response in renal cell carcinoma (RCC). These studies prompted us to evaluate the potential of selective anti-BMP9 cancer therapy in RCC. We generated a novel monoclonal therapeutic antibody candidate, mAb BMP9-0093, that selectively targets all different BMP9 variants but does not bind to the closest homolog BMP10. In vitro, mAb BMP9-0093 treatment inhibited signaling, endothelin-1 (ET-1) production and spreading of endothelial cells and restored BMP9-induced decrease in pericyte migration and attachment. Furthermore, BMP9-mediated epithelial-mesenchymal transition of renal cell carcinoma cells was reversed by mAb BMP9-0093 treatment in vitro. In vivo, mAb BMP9-0093 showed significant anti-tumor activity that was associated with an increase in apoptosis as well as a decrease in tumor cell proliferation and ET-1 release. Furthermore, mAb BMP9-0093 induced mural cell coverage of endothelial cells, which was corroborated by a reduction in vascular permeability, demonstrated by a diminished penetration of omalizumab-Alexa 647 into tumor tissue. Our findings provide new evidence for a better understanding of BMP9 contribution in tumor progression and angiogenesis that may result in the development of effective targeted therapeutic interventions.
EVALuna2:15267

Increased expression of guanylate binding protein-1 in lesional skin of patients with cutaneous lupus erythematosus - Naschberger, Elisabeth; Wenzel, Joerg; Kretz, Cosima C.; Herrmann, Martin; Stürzl, Michael; Kuhn, Annegret (Experimental Dermatology, 2011)
The large GTPase human guanylate binding protein-1 (GBP-1) is a key mediator of angiostatic effects of inflammation and is induced by interferon (IFN)-α and IFN-γ in endothelial cells (ECs). The aim of this study was to investigate whether GBP-1 is a marker of skin lesions in patients with cutaneous lupus erythematosus (CLE). Western blotting revealed that GBP-1 was in vitro induced by IFN-α and -γ in primary keratinocytes obtained from healthy controls. Moreover, we found that this protein was expressed by keratinocytes and ECs in primary and ultraviolet (UV)-induced skin lesions from patients with various subtypes of CLE, when compared to non-lesional skin. No GBP-1 expression was noted in skin biopsy specimens 24 or 72h after UV irradiation prior to lesion formation in patients with CLE or in healthy control specimens with or without UV irradiation. Initial findings suggest that GBP-1 is not expressed in other skin diseases with different inflammatory aetiology, such as atopic dermatitis. We conclude that GBP-1 expression is closely associated with skin lesions in patients with CLE, suggesting a contribution of GBP-1 in the pathogenesis of this disease. © 2011 John Wiley & Sons A/S.
Created from Fastlane, Scopus look-up
Keywords: Guanylate binding protein; Inflammation; Interferon; Lupus erythematosus; Skin; UV light

Induction of apoptosis in circulating angiogenic cells by microparticles. - Distler, Jörg; Akhmetshina, Alfiya; Dees, Clara; Juengel, Astrid; Stürzl, Michael; Gay, Steffen; Pisetsky, David S.; Schett, Georg; Distler, Oliver (Arthritis & Rheumatism-Arthritis Care & Research, 2011)
Systemic sclerosis (SSc) is an autoimmune disease marked by aberrant activation and apoptosis of endothelial cells (ECs) and decreased numbers of circulating angiogenic cells (CACs). The aim of this study was to analyze whether microparticles might link pathologic activation and apoptosis of ECs with reduced numbers of CACs. Apoptosis was quantified by staining for annexin V and measurement of caspase 3 activity. The uptake of microparticles by CACs was determined by fluorescence-activated cell sorting and by fluorescence microscopy. Tritiated arachidonic acid and phosphatidylinositol 3,5-bisphosphate were used to demonstrate the transfer of arachidonic acid and highlight the role of the acid sphingomyelinase in microparticle-induced apoptosis of endothelial progenitor cells. Microparticles derived from activated or apoptotic ECs, the expression of which is strongly increased in the blood of patients with SSc, induce apoptosis in CACs in a dose-dependent manner. Microparticles, which are rich in arachidonic acid, are phagocytosed by CACs. Inhibition of phagocytosis prevents the induction of apoptosis in CACs by microparticles. Microparticles can transport arachidonic acid from ECs to CACs, and purified arachidonic acid mimics the proapoptotic effects of microparticles. Arachidonic acid activates the acid sphingomyelinase, and inhibition of acid sphingomyelinase prevents microparticle-induced apoptosis of CACs. Thus, phagocytosis of microparticles might stimulate the activity of acid sphingomyelinase and activate the apoptotic machinery. The induction of apoptosis in CACs by microparticles derived from ECs provides a novel link between aberrant activation or apoptosis of ECs, decreased numbers of CACs, and impaired formation of new vessels in SSc. OBJECTIVE METHODS RESULTS CONCLUSION

Infection with human immunodeficiency virus-1 increases expression of vascular endothelial cell growth factor in T cells: implications for acquired immunodeficiency syndrome-associated vasculopathy. - Ascherl, Gudrun; Hohenadl, Christine; Schatz, Octavian; Shumay, Elena; Bogner, J.; Tschachler, Erwin; Monini, Paolo; Ensoli, Barbara; Stürzl, Michael; et al. (Blood, 1999)
Alterations in the vascular system and the onset of angioproliferative lesions such as Kaposi's sarcoma (KS) are common traits of human immunodeficiency virus-1 (HIV-1)-infected patients. To investigate possible factors involved in acquired immunodeficiency syndrome (AIDS)-associated vasculopathy and vascular malfunction, expression of vascular endothelial cell growth factor-A (VEGF-A) was analyzed in HUT 78 T lymphocytes upon infection with HIV-1. VEGF-A was found to be increased in supernatants from infected cells as compared with uninfected cells. In addition, VEGF-A mRNA expression and protein secretion were significantly increased in HUT 78 cells incubated with conditioned medium (CM) derived from HIV-1 chronically infected HUT 78 cells (HIV-TCM) as compared with CM from uninfected cells (TCM). Increase of VEGF-A production in T cells was promoted by inflammatory cytokines (IC) present in HIV-TCM, including tumor necrosis factor alpha (TNFalpha), interferon gamma (IFNgamma), interleukin-1beta (IL-1beta), and IL-6. These IC that have been shown to be increased in sera of HIV-1-infected patients and to be increased by HIV-1 infection or cell activation in these individuals as well as HIV-TCM also increased VEGF-A expression in primary T lymphocytes. Consistent with this, VEGF-A concentrations were found to be higher in sera of HIV-1-infected patients with (mean, 357.1 +/- 197.9 pg/mL) and without KS (mean, 256.7 +/- 137.5 pg/mL) as compared with uninfected individuals (mean, 188.6 +/- 91.7 pg/mL). These data suggest that increased secretion of VEGF-A by T lymphocytes of HIV-1-infected individuals may induce vascular leakage and stimulate proliferation of vascular endothelial cells, which are hallmarks of AIDS-associated vasculopathy and especially of KS development.

Inflammatory cytokines synergize with the HIV-1 Tat protein to promote angiogenesis and Kaposi's sarcoma via induction of basic fibroblast growth factor and the alpha v beta 3 integrin. - Barillari, Giovanni; Sgadari, Cecilia; Palladino, Clelia; Gendelman, R; Caputo, Antonella; Morris, C B; Nair, B. C.; Markham, P; Nel, A; Stürzl, Michael; Ensoli, Barbara (Journal of Immunology, 1999)
The Tat protein of HIV-1, a transactivator of viral gene expression, is released by acutely infected T cells and, in this form, exerts angiogenic activities. These have linked the protein to the pathogenesis of Kaposi's sarcoma (KS), a vascular tumor frequent and aggressive in HIV-1-infected individuals (AIDS-KS). In this study, we show that a combination of the same inflammatory cytokines increased in KS lesions, namely IL-1 beta, TNF-alpha, and IFN-gamma, synergizes with Tat to promote in nude mice the development of angioproliferative KS-like lesions that are not observed with each factor alone. Inflammatory cytokines induce the tissue expression of both basic fibroblast growth factor (bFGF) and vascular endothelial growth factor (VEGF), two angiogenic molecules highly produced in primary KS lesions. However, bFGF, but not VEGF, synergizes with Tat in vivo and induces endothelial cells to migrate, to adhere, and to grow in response to Tat in vitro. Tat angiogenic effects correlate with the expression of the alpha v beta 3 integrin that is induced by bFGF and binds the arginine-glycine-aspartic acid (RGD) region of Tat. In contrast, no correlation is observed with the expression of alpha v beta 5, which is promoted by VEGF and binds Tat basic region. Finally, KS lesion formation induced by bFGF and Tat in nude mice is blocked by antagonists of RGD-binding integrins. Because alpha v beta 3 is an RGD-binding integrin that is highly expressed in primary KS lesions, where it colocalizes with extracellular Tat on vessels and spindle cells, these results suggest that alpha v beta 3 competitors may represent a new strategy for the treatment of AIDS-KS.

Inhibition of cGAS DNA Sensing by a Herpesvirus Virion Protein - Wu, Jian-Jun; Li, Wenwei; Shao, Yaming; Avey, Denis; Fu, Bishi; Gillen, Joseph; Hand, Travis; Ma, Siming; Liu, Xia; Miley, Wendell; Konrad, Andreas; Neipel, Frank; et al. (Cell Host & Microbe, 2015)
Invading viral DNA can be recognized by the host cytosolic DNA sensor, cyclic GMP-AMP (cGAMP) synthase (cGAS), resulting in production of the second messenger cGAMP, which directs the adaptor protein STING to stimulate production of type I interferons (IFNs). Although several DNA viruses are sensed by cGAS, viral strategies targeting cGAS are virtually unknown. We report here that Kaposi's sarcoma-associated herpesvirus (KSHV) ORF52, an abundant gammaherpesvirus-specific tegument protein, subverts cytosolic DNA sensing by directly inhibiting cGAS enzymatic activity through a mechanism involving both cGAS binding and DNA binding. Moreover, ORF52 homologs in other gammaherpesviruses also inhibit cGAS activity and similarly bind cGAS and DNA, suggesting conserved inhibitory mechanisms. Furthermore, KSHV infection evokes cGAS-dependent responses that can limit the infection, and an ORF52 null mutant exhibits increased cGAS signaling. Our findings reveal a mechanism through which gammaherpesviruses antagonize host cGAS DNA sensing.
EVALuna2:8258

Inhibition of integrin αvβ6 sparks T-cell antitumor response and enhances immune checkpoint blockade therapy in colorectal cancer - Busenhart, Philipp; Montalban-Arques, Ana; Katkeviciute, Egle; Morsy, Yasser; Van Passen, Chiara; Hering, Larissa; Atrott, Kirstin; Lang, Silvia; Garzon, Jesus Francisco Glaus; Naschberger, Elisabeth; Hartmann, Arndt; Rogler, Gerhard; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Background Integrin αvβ6 is a heterodimeric cell surface protein whose cellular expression is determined by the availability of the integrin β6 subunit (ITGB6). It is expressed at very low levels in most organs during tissue homeostasis but shows highly upregulated expression during the process of tumorigenesis in many cancers of epithelial origin. Notably, enhanced expression of integrin αvβ6 is associated with aggressive disease and poor prognosis in numerous carcinoma entities. Integrin αvβ6 is one of the major physiological activators of transforming growth factor-β (TGF-β), which has been shown to inhibit the antitumor T-cell response and cause resistance to immunotherapy in mouse models of colorectal and mammary cancer. In this study, we investigated the effect of ITGB6 expression and antibody-mediated integrin αvβ6 inhibition on the tumor immune response in colorectal cancer. Methods Using orthotopic and heterotopic tumor cell injection, we assessed the effect of ITGB6 on tumor growth and tumor immune response in wild type mice, mice with defective TGF-β signaling, and mice treated with anti-integrin αvβ6 antibodies. To examine the effect of ITGB6 in human colorectal cancer, we analyzed RNAseq data from the colon adenocarcinoma dataset of The Cancer Genome Atlas (TCGA-COAD). Results We demonstrate that expression of ITGB6 is an immune evasion strategy in colorectal cancer, causing inhibition of the antitumor immune response and resistance to immune checkpoint blockade therapy by activating latent TGF-β. Antibody-mediated inhibition of integrin αvβ6 sparked a potent cytotoxic T-cell response and overcame resistance to programmed cell death protein 1 (PD-1) blockade therapy in ITGB6 expressing tumors, provoking a drastic increase in anti-PD-1 treatment efficacy. Further, we show that the majority of tumors in patients with colorectal cancer express sufficient ITGB6 to provoke inhibition of the cytotoxic T-cell response, indicating that most patients could benefit from integrin αvβ6 blockade therapy. Conclusions These findings propose inhibition of integrin αvβ6 as a promising new therapy for colorectal cancer, which blocks tumor-promoting TGF-β activation, prevents tumor exclusion of cytotoxic T-cells and enhances the efficacy of immune checkpoint blockade therapy.
CRIS-Team Scopus Importer:2022-02-25
Keywords: CD8-positive T-lymphocytes; cytotoxicity; drug evaluation; immunologic; immunotherapy; preclinical; tumor microenvironment

Interesting image. Tc-99m sestamibi SPECT/CT as a new tool for monitoring perfusion and viability of buried perforator based free flaps in breast reconstruction after breast cancer. - Dragu, Adrian; Linke, Rainer; Kuwert, Torsten; Unglaub, Frank; Kneser, Ulrich; Stürzl, Michael; Horch, Raymund E.; Bach, Alexander D. (Clinical Nuclear Medicine, 2010)

Interferon-alpha prevents apoptosis of endothelial cells after short-term exposure but induces replicative senescence after continuous stimulation. - Pammer, Johannes; Reinisch, Christine; Birner, Peter; Pogoda, Kristin; Stürzl, Michael; Tschachler, Erwin (Laboratory Investigation, 2006)
Although the antiangiogenic activity of type I interferons (IFN) is well known, the mechanism by which it occurs is unclear. In the present study, we have investigated effects of short-term and long-term IFN-alpha exposure on different types of endothelial cells (EC). Short-term IFN-alpha treatment resulted in a distinct reduction of apoptosis of serum and growth factor starved HUVEC and HDMEC. This was accompanied by a strong upregulation of the IFN inducible guanylate binding protein-1 (GBP-1) whereas no consistent regulation of several known antiapoptotic proteins was evident. Stable transfection of HUVEC with an expression vector for GBP-1 mimicked the protective effect of IFN-alpha, suggesting that GBP-1 may contribute to the inhibition of apoptosis. When IFN-alpha, together with serum and EC growth factors, was present continuously a decrease of population doublings by more than 40% was observed in both HDMEC and HCAEC. In addition, the cells displayed a senescent phenotype significantly earlier than control cells and showed an increased adherence for monocytes. Our findings suggest that the antiangiogenic effect of IFN-alpha is mediated by inducing EC senescence rather than EC apoptosis. Furthermore IFN-alpha released in chronic inflammatory conditions might contribute via its prosenescent activity to the pathogenesis of atherosclerosis.

Interferon Gamma Counteracts the Angiogenic Switch and Induces Vascular Permeability in Dextran Sulfate Sodium Colitis in Mice - Haep, Lisa; Britzen-Laurent, Nathalie; Weber, Thomas G.; Naschberger, Elisabeth; Schäfer, Amrei; Kremmer, Elisabeth; Försch, Sebastian; Scheuer, Werner; Wirtz, Stefan; Waldner, Maximilian; Stürzl, Michael; Vieth, Michael (Inflammatory Bowel Diseases, 2015)
Interferon (IFN)-? is a central pathogenesis factor in inflammatory bowel disease (IBD) with pleiotropic effects on many different cell types. However, as yet, the immune modulatory functions of IFN-? in IBD have been predominantly investigated. Based on previous studies showing that IFN-? acts antiangiogenic in colorectal carcinoma, we investigated the effects of IFN-? on the vascular system in IBD.Colon tissues of patients with IBD and dextran sulfate sodium-induced colitis in mice were subjected to immunohistochemistry, quantitative real-time polymerase chain reactions, and in situ hybridization to quantify cell activation, angiogenesis, and immune responses. Vascular structure and permeability in mice were analyzed by ultramicroscopy and in vivo confocal laser endomicroscopy.We showed a significantly increased blood vessel density in IBD and dextran sulfate sodium colitis. In mice, this was associated with a disorganized blood vessel structure and profound vascular leakage. As compared with genes associated with angiogenesis, genes associated with inflammatory cell activation including IFN-? were more strongly upregulated in colitis tissues. IFN-? exerted direct effects on endothelial cells in IBD tissues in vivo, as indicated by the expression of IFN-?-induced guanylate binding protein 1 (GBP-1). Neutralization of IFN-? in the acute dextran sulfate sodium colitis model demonstrated that this cytokine exerts endogenous angiostatic activity in IBD and contributes to increased vascular permeability.The dissection of the pleiotropic activities of IFN-? in IBD provides new insights to the pathological functions of this cytokine and may be of high relevance for the optimization of combination therapy approaches.
EVALuna2:1969

Interferon-gamma triggers an anti-tumorigenic chain reaction in the tumor vessels of colorectal carcinoma - Stürzl, Michael; Langer, Victoria; Regensburger, Daniela; Tenkerian, Clara; Klingler, Annika; Waldner, Maximilian; Becker, Christoph; Meniel, Valerie; Grützmann, Robert; Geppert, Carol-Immanuel; Britzen-Laurent, Nathalie; Naschberger, Elisabeth (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

Interferon-α counteracts the angiogenic switch and reduces tumor cell proliferation in a spontaneous model of prostatic cancer - Persano, Luca; Moserle, Lidia; Esposito, Giovanni; Bronte, Vincenzo; Barbieri, Vito; Iafrate, Massimo; Gardiman, Marina P.; Larghero, Patrizia; Pfeffer, Ulrich; Naschberger, Elisabeth; Stürzl, Michael; Indraccolo, Stefano; et al. (Carcinogenesis, 2009)
Interferon (IFN)-α is a cytokine with marked therapeutic activity in transplantable tumor models, that is in part due to angiogenesis inhibition. Aim of this study was to investigate the effects of IFN-α during the early phases of tumor development in the transgenic adenocarcinoma of the mouse prostate (TRAMP) model. To provide sustained IFN-α production, TRAMP mice were injected intraperitoneally with lentiviral vectors. IFN-α administration resulted in rapid and protracted upregulation of IFN-α-regulated genes associated with antiangiogenic and antiproliferative functions in the prostate of TRAMP mice, including guanylate-binding protein 1 (GBP-1), IFI204 and CXCL10-11. These transcriptional changes were accompanied by effects on the tumor vasculature, including significant reduction of intraductal microvessel density and increased pericyte coverage, and marked reduction of tumor cell proliferation, without induction of tumor necrosis. Intriguingly, GBP-1 and myxovirus resistance A, two IFN-regulated proteins, were found expressed in ∼40% of human prostate cancer samples analyzed, suggesting expression of endogenous IFN-α. Overall, these findings demonstrate that IFN-α is able to counteract the angiogenic switch and impairs tumor cell proliferation in preinvasive lesions. Since the angiogenic switch also marks progression of human prostatic cancer, these results highlight the potential of angiogenesis inhibitors for the development of chemoprevention strategies in high-risk individuals. © The Author 2009. Published by Oxford University Press. All rights reserved.
Created from Fastlane, Scopus look-up

Interferon γ-Induced human guanylate binding protein 1 inhibits mammary tumor growth in mice - Lipnik, Karoline; Naschberger, Elisabeth; Britzen-Laurent, Nathalie; Kodajova, Petra; Petznek, Helga; Rungaldier, Stefanie; Astigiano, Simonetta; Ferrini, Silvano; Stürzl, Michael; Hohenadl, Christine (Molecular Medicine, 2010)
Interferon γ (IFN-γ) has recently been implicated in cancer immunosurveillance. Among the most abundant proteins induced by IFN-γ are guanylate binding proteins (GBPs), which belong to the superfamily of large GTPases and are widely expressed in various species. Here, we investigated whether the well-known human GBP-1 (hGBP-1), which has been shown to exert antiangio-genic activities and was described as a prognostic marker in colorectal carcinomas, may contribute to an IFN-γ-mediated tumor defense. To this end, an IFN-independent, inducible hGBP-1 expression system was established in murine mammary carcinoma (TS/A) cells, which were then transplanted into syngeneic immune-competent Balb/c mice. Animals carrying TS/A cells that had been given doxycycline for induction of hGBP-1 expression revealed a significantly reduced tumor growth compared with mock-treated mice. Immunohistochemical analysis of the respective tumors demonstrated a tightly regulated, high-level expression of hGBP-1. No signs of an enhanced immunosurveillance were observed by investigating the number of infiltrating B and T cells. However, hemoglobin levels as well as the number of proliferating tumor cells were shown to be significantly reduced in hGBP-1-expressing tumors. This finding corresponded to reduced amounts of vascular endothelial growth factor A (VEGF-A) released by hGBP-1-expressing TS/A cells in vitro and reduced VEGF-A protein levels in the corresponding mammary tumors in vivo. The results suggest that hGBP-1 may contribute to IFN-γ-mediated antitumorigenic activities by inhibiting paracrine effects of tumor cells on angiogenesis. Consequently, owing to these activities GBPs might be considered as potent members in an innate, IFN-γ-induced antitumoral defense system. © 2010 The Feinstein Institute for Medical Research.
Created from Fastlane, Scopus look-up

Interplay of GTPases and Cytoskeleton in Cellular Barrier Defects during Gut Inflammation - Lopez Posadas, Rocío; Stürzl, Michael; Atreya, Imke; Neurath, Markus; Britzen-Laurent, Nathalie (Frontiers in Immunology, 2017)
An essential role of the intestine is to build and maintain a barrier preventing the luminal gut microbiota from invading the host. This involves two coordinated physical and immunological barriers formed by single layers of intestinal epithelial and endothelial cells, which avoid the activation of local immune responses or the systemic dissemination of microbial agents, and preserve tissue homeostasis. Accordingly, alterations of epithelial and endothelial barrier functions have been associated with gut inflammation, for example during inflammatory bowel disease (IBD). The discriminative control of nutriment uptake and sealing toward potentially pathological microorganisms requires a profound regulation of para- and transcellular permeability. On the subcellular level, the cytoskeleton exerts key regulatory functions in the maintenance of cellular barriers. Increased epithelial/endothelial permeability occurs primarily as a result of a reorganization of cytoskeletal-junctional complexes. Pro-inflammatory mediators such as cytokines can induce cytoskeletal rearrangements, causing inflammation-dependent defects in gut barrier function. In this context, small GTPases of the Rho family and large GTPases from the Dynamin superfamily appear as major cellular switches regulating the interaction between intercellular junctions and actomyosin complexes, and in turn cytoskeleton plasticity. Strikingly, some of these proteins, such as RhoA or guanylate-binding protein-1 (GBP-1) have been associated with gut inflammation and IBD. In this review, we will summarize the role of small and large GTPases for cytoskeleton plasticity and epithelial/endothelial barrier in the context of gut inflammation.
EVALuna2:15286

Intracellular localization map of human herpesvirus 8 proteins. - Sander, Gaby; Konrad, Andreas; Thurau, Mathias; Wies, Effi; Leubert, Rene; Kremmer, Elisabeth; Dinkel, Holger; Schulz, Thomas; Neipel, Frank; Stürzl, Michael (Journal of Virology, 2008)
Human herpesvirus 8 (HHV-8) is the etiological agent of Kaposi's sarcoma. We present a localization map of 85 HHV-8-encoded proteins in mammalian cells. Viral open reading frames were cloned with a Myc tag in expression plasmids, confirmed by full-length sequencing, and expressed in HeLa cells. Protein localizations were analyzed by immunofluorescence microscopy. Fifty-one percent of all proteins were localized in the cytoplasm, 22% were in the nucleus, and 27% were found in both compartments. Surprisingly, we detected viral FLIP (v-FLIP) in the nucleus and in the cytoplasm, whereas cellular FLIPs are generally localized exclusively in the cytoplasm. This suggested that v-FLIP may exert additional or alternative functions compared to cellular FLIPs. In addition, it has been shown recently that the K10 protein can bind to at least 15 different HHV-8 proteins. We noticed that K10 and only five of its 15 putative binding factors were localized in the nucleus when the proteins were expressed in HeLa cells individually. Interestingly, in coexpression experiments K10 colocalized with 87% (13 of 15) of its putative binding partners. Colocalization was induced by translocation of either K10 alone or both proteins. These results indicate active intracellular translocation processes in virus-infected cells. Specifically in this framework, the localization map may provide a useful reference to further elucidate the function of HHV-8-encoded genes in human diseases.

Intracellular trafficking of guanylate-binding proteins is regulated by heterodimerization in a hierarchical manner - Britzen-Laurent, Nathalie; Bauer, Michael; Berton, Valeria; Fischer, Nicole; Syguda, Adrian; Reipschlaeger, Simone; Naschberger, Elisabeth; Herrmann, Christian; Stürzl, Michael (PLoS ONE, 2010)
Guanylate-binding proteins (GBPs) belong to the dynamin family of large GTPases and represent the major IFN-c-induced proteins. Here we systematically investigated the mechanisms regulating the subcellular localization of GBPs. Three GBPs (GBP-1, GBP-2 and GBP-5) carry a C-terminal CaaX-prenylation signal, which is typical for small GTPases of the Ras family, and increases the membrane affinity of proteins. In this study, we demonstrated that GBP-1, GBP-2 and GBP-5 are prenylated in vivo and that prenylation is required for the membrane association of GBP-1, GBP-2 and GBP-5. Using coimmunoprecipitation, yeast-two-hybrid analysis and fluorescence complementation assays, we showed for the first time that GBPs are able to homodimerize in vivo and that the membrane association of GBPs is regulated by dimerization similarly to dynamin. Interestingly, GBPs could also heterodimerize. This resulted in hierarchical positioning effects on the intracellular localization of the proteins. Specifically, GBP-1 recruited GBP-5 and GBP-2 into its own cellular compartment and GBP-5 repositioned GBP-2. In addition, GBP-1, GBP-2 and GBP-5 were able to redirect non-prenylated GBPs to their compartment in a prenylation-dependent manner. Overall, these findings prove in vivo the ability of GBPs to dimerize, indicate that heterodimerization regulates sub-cellular localization of GBPs and underscore putative membrane-associated functions of this family of proteins. © 2010 Britzen-Laurent et al.
Created from Fastlane, Scopus look-up

Inverse relation of Fas-ligand and tumor-infiltrating lymphocytes in angiosarcoma: indications of apoptotic tumor counterattack. - Zietz, Christian; Rumpler, Ulrich; Stürzl, Michael; Löhrs, Udo (American Journal of Pathology, 2001)
Fas and Fas-L regulate immune responses through the induction of cell death. Fas-L is commonly expressed in activated immune cells and in the endothelium. In the latter it contributes to the inhibition of transvascular cell migration by the induction of apoptosis in Fas-bearing lymphocytes. Here we investigated whether the Fas/Fas-L system may regulate lymphocyte invasion into angiosarcomas. Fas and Fas-L expression was quantitatively determined in different grade angiosarcomas (n = 40) and related to the number of extravasated tumor-infiltrating lymphocytes (TILs). Fas expression was detected in < 50% of the cases. In positive tumors both the number of Fas-positive cells and the staining intensity were highly variable and did not correlate with the number of TILs, the mean time of survival, and the histopathological tumor grade. By contrast, Fas-L expression was detected in >70% of the cases and the relative numbers of Fas-L-positive cells correlated inversely with the numbers of CD3- and CD8-positive TILs (P < or = 0.004). The survival times of patients with high Fas-L-expressing angiosarcomas were significantly reduced as compared to patients with low Fas-L-expressing tumors. Our results show that angiosarcomas with low Fas-L expression are characterized by numerous TILs, whereas sarcomas with high Fas-L expression show significantly reduced numbers of TILs. These results suggest that the Fas/Fas-L system may repress TIL invasion into angiosarcoma and by this may contribute to the evasion of the anti-tumor immune surveillance of angiosarcoma in the course of an apoptotic tumor counterattack mechanism.

Investigating Intestinal Barrier Breakdown in Living Organoids - Bardenbacher, Marco; Ruder, Barbara; Britzen-Laurent, Nathalie; Naschberger, Elisabeth; Becker, Christoph; Palmisano, Ralf; Stürzl, Michael; Tripal, Philipp (Journal of Visualized Experiments, 2020)
Organoids and three-dimensional (3D) cell cultures allow the investigation of complex biological mechanisms and regulations in vitro, which previously was not possible in classical cell culture monolayers. Moreover, monolayer cell cultures are good in vitro model systems but do not represent the complex cellular differentiation processes and functions that rely on 3D structure. This has so far only been possible in animal experiments, which are laborious, time consuming, and hard to assess by optical techniques. Here we describe an assay to quantitatively determine the barrier integrity over time in living small intestinal mouse organoids. To validate our model, we applied interferon gamma (IFN-gamma) as a positive control for barrier destruction and organoids derived from IFN-gamma receptor 2 knock out mice as a negative control. The assay allowed us to determine the impact of IFN-gamma on the intestinal barrier integrity and the IFN-gamma induced degradation of the tight junction proteins claudin-2, -7, and -15. This assay could also be used to investigate the impact of chemical compounds, proteins, toxins, bacteria, or patient-derived probes on the intestinal barrier integrity.
CRIS-Team WoS Importer:2020-04-17

IRAK-M Expression in Tumor Cells Supports Colorectal Cancer Progression through Reduction of Antimicrobial Defense and Stabilization of STAT3 - Kesselring, Rebecca; Glaesner, Joachim; Hiergeist, Andreas; Naschberger, Elisabeth; Neumann, Helmut; Brunner, Stefan M.; Wege, Anja K.; Seebauer, Caroline; Koehl, Gudrun; Merkl, Susanne; Croner, Roland S.; Hackl, Christina; et al. (Cancer Cell, 2016)
Colorectal cancer (CRC) is associated with loss of epithelial barrier integrity, which facilitates the interaction of the immunological microenvironment with the luminal microbiome, eliciting tumor-supportive inflammation. An important regulator of intestinal inflammatory responses is IRAK-M, a negative regulator of TLR signaling. Here we investigate the compartment-specific impact of IRAK-M on colorectal carcinogenesis using a mouse model. We demonstrate that IRAK-M is expressed in tumor cells due to combined TLR and Wnt activation. Tumor cell-intrinsic IRAK-M is responsible for regulation of microbial colonization of tumors and STAT3 protein stability in tumor cells, leading to tumor cell proliferation. IRAK-M expression in human CRCs is associated with poor prognosis. These results suggest that IRAK-M may be a potential therapeutic target for CRC treatment.
EVALuna2:2089

Isolation of Endothelial Cells from Human Tumors - Naschberger, Elisabeth; Schellerer, Vera; Rau, Tilman T.; Croner, Roland S.; Stürzl, Michael (Cancer Cell Culture, 2011)
Antiangiogenic drugs have been used successfully for the treatment of colorectal cancer (CRC) and several other tumor types. Until recently, viable tumor endothelial cells (TEC) and normal endothelial cells of uninvolved colon tissue (NEC) from the same patient have not been available to optimize treatment strategies in vitro. Here, we describe a protocol for the isolation of TEC and NEC. These cells were isolated at a very high purity via magnetic cell sorting of tissue samples obtained from surgical specimens of patients suffering from CRC. Isolated TEC and NEC expressed CD31, CD105, VE-cadherin, VCAM-1, ICAM-1, and E-selectin, formed capillaries in basal membrane extract, and were able to take up acetylated LDL. They were negative for podoplanin, CD45, CD68, and CK-20, indicating blood vessel endothelial lineage. Expression of vWF was more pronounced in NEC cultures, whereas vWF was absent or only slightly expressed in all TEC cultures in vitro. Lower intracellular concentrations of vWF were also detected in TEC as compared to NEC at the tissue level. The latter finding demonstrated that differential features of TEC and NEC in vivo arc stably perpetuated in culture. The isolated endothelial cell cultures may provide a useful in vitro model system to elucidate epigenetic effects on angiogenesis in cancer and to optimize antiangiogenic therapy.
Created from Fastlane, WoS look-up

Isolation of Human Endothelial Cells from Normal Colon and Colorectal Carcinoma - An Improved Protocol - Naschberger, Elisabeth; Regensburger, Daniela; Tenkerian, Clara; Langheinrich, Melanie; Engel, Felix; Geppert, Carol-Immanuel; Hartmann, Arndt; Grützmann, Robert; Schellerer, Vera; Stürzl, Michael (Journal of Visualized Experiments, 2018)
Primary cells isolated from human carcinomas are valuable tools to identify pathogenic mechanisms contributing to disease development and progression. In particular, endothelial cells (EC) constituting the inner surface of vessels, directly participate in oxygen delivery, nutrient supply, and removal of waste products to and from tumors, and are thereby prominently involved in the constitution of the tumor microenvironment (TME). Tumor endothelial cells (TECs) can be used as cellular biosensors of the intratumoral microenvironment established by communication between tumor and stromal cells. TECs also serve as targets of therapy. Accordingly, in culture these cells allow studies on mechanisms of response or resistance to anti-angiogenic treatment. Recently, it was found that TECs isolated from human colorectal carcinoma (CRC) exhibit memory-like effects based on the specific TME they were derived from. Moreover, these TECs actively contribute to the establishment of a specific TME by the secretion of different factors. For example, TECs in a prognostically favorable Th1-TME secrete the anti-angiogenic tumor-suppressive factor secreted protein, acidic and rich in cysteine-like 1 (SPARCL1). SPARCL1 regulates vessel homeostasis and inhibits tumor cell proliferation and migration. Hence, cultures of pure, viable TECs isolated from human solid tumors are a valuable tool for functional studies on the role of the vascular system in tumorigenesis. Here, a new up-to-date protocol for the isolation of primary EC from the normal colon as well as CRC is described. The technique is based on mechanical and enzymatic tissue digestion, immunolabeling, and fluorescence activated cell sorting (FACS)-sorting of triple-positive cells (CD31, VE-cadherin, CD105). With this protocol, viable TEC or normal endothelial cell (NEC) cultures could be isolated from colon tissues with a success rate of 62.12% when subjected to FACS-sorting (41 pure EC cultures from 66 tissue samples). Accordingly, this protocol provides a robust approach to isolate human EC cultures from normal colon and CRC.
EVALuna2:34267

IT infrastructure components to support clinical care and translational research projects in a comprehensive cancer center - Prokosch, Hans-Ulrich; Ries, Markus; Beyer, Alexander; Schwenk, Martin; Seggewies, Christof; Köpcke, Felix; Mate, Sebastian; Martin, Marcus; Bärthlein, Barbara; Beckmann, Matthias; Stürzl, Michael; Croner, Roland; et al. (User Centred Networked Health Care, 2011)
This paper presents the concept of an integrated IT infrastructure framework established at the comprehensive cancer center at the University Hospital Erlangen. The framework is based on the single source concept where data from the electronic medical record are reused for clinical and translational research projects. The applicability of the approach is illustrated by two case studies from colon cancer and prostate cancer research projects. © 2011 European Federation for Medical Informatics. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2011.tech.IMMD.infome.itinfr
Keywords: Cancer documentation; Center; Comprehensive cancer; IT infrastructure framework; Single source concept; Translational research

Kaposi's sarcoma: a review of gene expression and ultrastructure of KS spindle cells in vivo. - Stürzl, Michael; Brandstetter, Heinz; Roth, W K (Aids Research and Human Retroviruses, 1992)
The ultrastructural features and the gene expression pattern of Kaposi's sarcoma (KS) spindle cells in vivo suggest that KS is a tumor of the mixed cell type. The expression pattern of cytokines and cytokine receptors in the tumor lesion, together with the results obtained from in vitro characterization of KS-derived cells, provide evidence that paracrine mechanisms of growth factor action are important for the maintenance of KS. The reports on virus infection of KS cells suggest an indirect role of virus infection in the induction of KS, most likely mediated by immunostimulation and subsequent production of cytokines.

Kaposi's sarcoma-associated herpesvirus gH/gL: glycoprotein export and interaction with cellular receptors. - Hahn, Alexander; Birkmann, Alexander; Wies, Effi; Dorer, Dominik; Mahr, Kerstin; Stürzl, Michael; Titgemeyer, Fritz; Neipel, Frank (Journal of Virology, 2009)
The attachment, entry, and fusion of Kaposi's sarcoma-associated herpesvirus (KSHV) with target cells are mediated by complex machinery containing, among others, viral glycoprotein H (gH) and its alleged chaperone, gL. We observed that KSHV gH, in contrast to its homologues in several other herpesviruses, is transported to the cytoplasm membrane independently from gL, but not vice versa. Mutational analysis revealed that the N terminus of gH is sufficient for gL interaction. However, the entire extracellular part of gH is required for efficient gL secretion. The soluble ectodomain of gH was sufficient to interact with the surfaces of potential target cells in a heparin-dependent manner, and binding was further enhanced by coexpression of gL. Surface plasmon resonance revealed a remarkably high affinity of gH for glycosaminoglycans. Heparan sulfate (HS) proteoglycans of the syndecan family act as cellular receptors for the gH/gL complex. They promoted KSHV infection, and expression of gH/gL on target cells inhibited subsequent KSHV infection. Whereas gH alone was able to bind to HS, we observed that only the gH/gL complex adhered to heparan sulfate-negative cells at lamellipodium-like structures.

Kaposi's sarcoma-associated herpesvirus serology in Europe and Uganda: multicentre study with multiple and novel assays. - Schatz, Octavian; Monini, Paolo; Bugarini, Roberto; Neipel, Frank; Schulz, Thomas F.; Andreoni, Massimo; Erb, Peter; Eggers, Maren; Haas, Jürgen; Buttò, Stefano; Lukwiya, Matthew; Bogner, Johannes R.; et al. (Journal of Medical Virology, 2001)
A multicentre study was undertaken to define novel assays with increased inter-assay concordance, sensitivity, specificity and predictive value for serological diagnosis of human herpesvirus type 8 (HHV-8) infection. A total of 562 sera from European and Ugandan human immunodeficiency virus (HIV)-infected or uninfected individuals with or without Kaposi's sarcoma (KS) and blood donors were examined under code by 18 different assays in seven European laboratories. Sera from KS patients and all non-KS sera found positive by at least 70%, 80%, or 90% of the assays were considered "true positive." The validity of the assays was then evaluated by univariate logistic regression analysis. Two immunofluorescence assays (IFA) for detection of antibodies against HHV-8 lytic (Rlyt) or latent (LLANA) antigens and two enzyme-linked-immunosorbent assays (ELISA) (M2, EK8.1) for detection of antibodies against HHV-8 structural proteins were found to be highly concordant, specific, and sensitive, with odds ratios that indicated a high predictive value. When used together, the two IFA (Rlyt-LLANA) showed the best combination of sensitivity (89.1%) and specificity (94.9%). The performance of these assays indicate that they may be used for the clinical management of individuals at risk of developing HHV-8 associated tumours such as allograft recipients.

Kaposi's sarcoma associated herpesvirus tegument protein ORF75 is essential for viral lytic replication and plays a critical role in the antagonization of ND10-instituted intrinsic immunity - Full, Florian; Jungnickl, Doris; Reuter, Nina; Bogner, Elke; Brulois, Kevin; Scholz, Brigitte; Stürzl, Michael; Myoung, Jinjong; Jung, Jae U.; Stamminger, Thomas; Enßer, Armin (PLoS Pathogens, 2014)
Nuclear domain 10 (ND10) components are restriction factors that inhibit herpesviral replication. Effector proteins of different herpesviruses can antagonize this restriction by a variety of strategies, including degradation or relocalization of ND10 proteins. We investigated the interplay of Kaposi's Sarcoma-Associated Herpesvirus (KSHV) infection and cellular defense by nuclear domain 10 (ND10) components. Knock-down experiments in primary human cells show that KSHV-infection is restricted by the ND10 components PML and Sp100, but not by ATRX. After KSHV infection, ATRX is efficiently depleted and Daxx is dispersed from ND10, indicating that these two ND10 components can be antagonized by KSHV. We then identified the ORF75 tegument protein of KSHV as the viral factor that induces the disappearance of ATRX and relocalization of Daxx. ORF75 belongs to a viral protein family (viral FGARATs) that has homologous proteins in all gamma-herpesviruses. Isolated expression of ORF75 in primary cells induces a relocalization of PML and dispersal of Sp100, indicating that this viral effector protein is able to influence multiple ND10 components. Moreover, by constructing a KSHV mutant harboring a stop codon at the beginning of ORF75, we could demonstrate that ORF75 is absolutely essential for viral replication and the initiation of viral immediate-early gene expression. Using recombinant viruses either carrying Flag- or YFP-tagged variants of ORF75, we could further corroborate the role of ORF75 in the antagonization of ND10-mediated intrinsic immunity, and show that it is independent of the PML antagonist vIRF3. Members of the viral FGARAT family target different ND10 components, suggesting that the ND10 targets of viral FGARAT proteins have diversified during evolution. We assume that overcoming ND10 intrinsic defense constitutes a critical event in the replication of all herpesviruses; on the other hand, restriction of herpesviral replication by ND10 components may also promote latency as the default outcome of infection.
EVALuna2:8222

Kaposi's sarcoma-derived cell line SLK is not of endothelial origin, but is a contaminant from a known renal carcinoma cell line. - Stürzl, Michael; Gaus, Dominika; Dirks, Wilhelm G.; Ganem, Don; Jochmann, Ramona (International Journal of Cancer, 2013)
Kaposi's sarcoma (KS) is an endothelial cell-derived tumor. Investigations of the molecular mechanisms of KS pathogenesis and the identification of drugs for treatment of KS depend critically on valid cell-culture models. Two major immortalized cell lines are available for KS research. Recently, the KS cell line KS Y-1 has been shown to be cross-contaminated with the T24 urinary bladder cancer cell line (ATCC HTB-4). Here, we show by short tandem repeat profiling that the second KS cell line, SLK, is indistinguishable from the clear-cell renal-cell carcinoma cell line Caki-1. Immunocytochemical detection of cytokeratin expression confirmed the epithelial-cell origin of SLK cells. Our findings indicate that SLK cells are not of endothelial origin and should not be used in future studies as a model for KS-derived endothelial tumor cells. We suggest that in the future, more attention needs to be paid to the authenticity of cells in lines derived from human tissues.

Ketos: Clinical decision support and machine learning as a service – A training and deployment platform based on Docker, OMOP-CDM, and FHIR Web Services - Gründner, Julian; Schwachhofer, Thorsten; Sippl, Phillip; Wolf, Nicolas; Erpenbeck, Marcel; Gulden, Christian; Kapsner, Lorenz A.; Zierk, Jakob; Mate, Sebastian; Stürzl, Michael; Croner, Roland; Prokosch, Hans-Ulrich; et al. (PLoS ONE, 2019)
Background and objective To take full advantage of decision support, machine learning, and patient-level prediction models, it is important that models are not only created, but also deployed in a clinical setting. The KETOS platform demonstrated in this work implements a tool for researchers allowing them to perform statistical analyses and deploy resulting models in a secure environment. Methods The proposed system uses Docker virtualization to provide researchers with reproducible data analysis and development environments, accessible via Jupyter Notebook, to perform statistical analysis and develop, train and deploy models based on standardized input data. The platform is built in a modular fashion and interfaces with web services using the Health Level 7 (HL7) Fast Healthcare Interoperability Resources (FHIR) standard to access patient data. In our prototypical implementation we use an OMOP common data model (OMOP-CDM) database. The architecture supports the entire research lifecycle from creating a data analysis environment, retrieving data, and training to final deployment in a hospital setting. Results We evaluated the platform by establishing and deploying an analysis and end user application for hemoglobin reference intervals within the University Hospital Erlangen. To demonstrate the potential of the system to deploy arbitrary models, we loaded a colorectal cancer dataset into an OMOP database and built machine learning models to predict patient outcomes and made them available via a web service. We demonstrated both the integration with FHIR as well as an example end user application. Finally, we integrated the platform with the open source DataSHIELD architecture to allow for distributed privacy preserving data analysis and training across networks of hospitals. Conclusion The KETOS platform takes a novel approach to data analysis, training and deploying decision support models in a hospital or healthcare setting. It does so in a secure and privacy-preserving manner, combining the flexibility of Docker virtualization with the advantages of standardized vocabularies, a widely applied database schema (OMOP-CDM), and a standardized way to exchange medical data (FHIR).
CRIS-Team Scopus Importer:2019-10-11

Lack of inhibitory effects of the anti-fibrotic drug imatinib on endothelial cell functions in vitro and in vivo. - Venalis, Paulius; Maurer, Britta; Akhmetshina, Alfiya; Busch, Nicole; Dees, Clara; Stürzl, Michael; Zwerina, Jochen; Juengel, Astrid; Gay, Steffen; Schett, Georg; Distler, Oliver; Distler, Jörg (Journal of Cellular and Molecular Medicine, 2009)
Systemic sclerosis (SSc) is a systemic autoimmune disease that is characterized by microangiopathy with progressive loss of capillaries and tissue fibrosis. Imatinib exerts potent anti-fibrotic effects and is currently evaluated in clinical trials. The aim of the present study was to exclude that the anti-fibrotic effects of imatinib are complicated by inhibitory effects on endothelial cell functions, which might augment vascular disease in SSc. Endothelial cells and mice were treated with pharmacologically relevant concentrations of imatinib. The expression of markers of vascular activation was assessed with real-time PCR. Proliferation was analysed with the cell counting experiments and the MTT assay. Apoptosis was quantified with caspase 3 assays, annexin V in vitro and with TUNEL staining in vivo. Migration was studied with scratch and transwell assays. Tube forming was investigated with the matrigel assay. Imatinib did not alter the expression of markers of vascular activation. Imatinib did not increase the percentage of annexin V positive cells or the activity of caspase 3. No reduction in proliferation or metabolic activity of endothelial cells was observed. Imatinib did not affect migration of endothelial cells and did not reduce the formation of capillary tubes. Consistent with the in vitro data, no difference in the number of apoptotic endothelial cells was observed in vivo in mice treated with imatinib. Imatinib does not inhibit activation, viability, proliferation, migration or tube forming of endothelial cells in vitro and in vivo. Thus, treatment with imatinib might not augment further endothelial cell damage in SSc.

Liposomal doxorubicin in the treatment of AIDS-associated Kaposi's sarcoma: clinical, histological and cell biological evaluation. - Stürzl, Michael; Zietz, Christian; Eisenburg, B; Goebel, F D; Gillitzer, R; Hofschneider, Peter Hans; Bogner, J. R. (RES VIROLOGY, 1994)
AIDS-associated Kaposi's sarcoma (KS) in eight patients was treated with the systemic application of liposomal doxorubicin (20 mg/m2 per cycle). After six cycles of treatment a significant regression of KS was observed in all patients. Tumour volume was reduced from 556 +/- 635 mm3 before therapy to 42 +/- 134 mm3 after therapy as determined by ultrasonography of selected tumours. Histological examination revealed a reduction of tumour-like structures and the absence of KS spindle cells in involved areas after therapy. In vitro experiments with KS-derived cell cultures, which most likely represent the KS spindle cells, suggested that liposomal doxorubicin may cause regression of KS via two different mechanisms: (i) by highly specific inhibition of KS spindle cell proliferation and (ii) by induction of monocyte chemoattractant protein-1 expression in KS spindle cells, which may result in increased recruitment of phagocytic cells (monocytes/macrophages) into the lesions. A cooperative action of both mechanisms may explain the high efficacy of liposomal doxorubicin in the treatment of AIDS-KS.
Keywords: AIDS; Kaposi's sarcoma; Doxorubicin; Liposome Therapy; Spindle cells; Monocyte chemoattractant protein-1

Loss of IFN-gamma pathway gene expression in tumor cells as mechanism of immune escape of colorectal carcinoma - Britzen-Laurent, Nathalie; Straube, Julia; Waldner, Maximilian; Becker, Christoph; Croner, Roland; Pilarsky, Christian; Merkel, Susanne; Stürzl, Michael (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

Malignant progression of invasive tumour cells seen in hypoxia present an accumulation of β-catenin in the nucleus at the tumour front - Demir, Resit; Dimmler, Arno; Naschberger, Elisabeth; Demir, Ilknur; Papadopoulos, Thomas; Melling, Nathaniel; Stürzl, Michael; Hohenberger, Werner (Experimental and Molecular Pathology, 2009)
Of all processes involved in tumour progression, local invasion and formation of metastases are the clinically most relevant but the scientifically least well understood at their molecular level. The loss of cell adhesion, then tumour cell migration with changes in the cytoskeleton, invasion and metastatic dissemination are the steps of the "metastatic cascade". The E-cadherin-catenin complex plays a key role in cell adhesion thus building the first step in malignant progression. In many epithelial cancers, E-cadherin is lost concomitantly with tumour progression. Thus β-catenin dissociates in the cytoplasm and accumulates in the nucleus as a transcription factor. Recent experimental progress has identified that tumour hypoxia not only induces tumour angiogenesis, but also modulates malignant progression to initiate tumour invasion and metastasis. It was hypothesised that hypoxia within tumours causes dysfunction of the E-cadherin-catenin complex with an accumulation of β-catenin in the nucleus and produces an invasive phenotype of tumour cells. For this purpose fertilized chicken eggs were incubated for ten days in normoxic conditions. Subsequently colon carcinoma cells (SW-480) were placed on the chorioallantoic membrane. During the following six days the eggs were incubated either in normoxic conditions or in stepwise decreasing hypoxic conditions. SW-480 colon carcinoma cells did not invade the epithelial layer in normoxic conditions. β-catenin was membrane bound or in the cytoplasm. The nuclei were regularly omitted. In contrast, an invasion through the epithelial layer into the mesoderm was already seen after three days when incubated in hypoxic conditions. β-catenin was membrane bound in non-invasive regions of the tumour nodule but there was an accumulation of β-catenin in the nucleus in the invasive tumour front. Hypoxia seems to be responsible for accumulation of β-catenin in the nucleus which is accompanied by a more invasive phenotype of tumour cells at the tumour front. © 2009 Elsevier Inc. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Beta-Catenin; Chorioallantoic membrane; Hypoxia; Malignant progression

Maternal HIV type 1 infection suppresses MMP-1 expression in endothelial cells of uninfected newborns: Non viral vertical transmission of HIV type 1-related effects - Naschberger, Elisabeth; Stürzl, Michael; et al. (Aids Research and Human Retroviruses, 2005)
HIV-1 infection is associated with vascular alterations. This is accompanied by an increased risk of cardiovascular diseases and Kaposi's sarcoma, an endothelial cell-derived tumor. We investigated the impact of maternal HIV-1 infection on phenotype and gene expression of endothelial cells in newborns. For this reason endothelial precursor cells and differentiated endothelial cells were isolated from cord blood as well as from umbilical veins and arteries of noninfected infants born to HIV-1-infected (H-group) and noninfected (N-group) mothers. No apparent differences in proliferation, capillary formation, and expression of endothelial cell markers were detected in these cells. Interestingly, the expression of matrix metalloproteinase was repressed significantly (χ2 analysis, p < 0.002) and consistently at the RNA, the protein, and the secretory levels in the H-group as compared to the N-group. Neither treatment with zidovudine (AZT), mutations in the matrix metalloproteinase-1 (MMP-1) promoter, nor epigenetic changes in the promoter methylation pattern were responsible for the repression of MMP-1 expression in H-group endothelial cells. The reduced MMP-1 expression may contribute to the impaired cardiac function that has been observed in children of HIV-1-infected women. Most interestingly, our findings indicate that HIV-1-related effects can be transferred from mother to child in the absence of HIV-1 transmission. © Mary Ann Liebert, Inc.
Created from Fastlane, Scopus look-up

Matricellular Protein SPARCL1 Regulates Blood Vessel Integrity and Antagonizes Inflammatory Bowel Disease - Regensburger, Daniela; Tenkerian, Clara; Pürzer, Victoria; Schmid, Benjamin; Wohlfahrt, Thomas; Stolzer, Iris; Lopez Posadas, Rocío; Günther, Claudia; Waldner, Maximilian; Becker, Christoph; Sticht, Heinrich; Petter, Katja; et al. (Inflammatory Bowel Diseases, 2021)
Background The understanding of vascular plasticity is key to defining the role of blood vessels in physiologic and pathogenic processes. In the present study, the impact of the vascular quiescence marker SPARCL1 on angiogenesis, capillary morphogenesis, and vessel integrity was evaluated. Methods Angiogenesis was studied using the metatarsal test, an ex vivo model of sprouting angiogenesis. In addition, acute and chronic dextran sodium sulfate colitis models with SPARCL1 knockout mice were applied. Results This approach indicated that SPARCL1 inhibits angiogenesis and supports vessel morphogenesis and integrity. Evidence was provided that SPARCL1-mediated stabilization of vessel integrity counteracts vessel permeability and inflammation in acute and chronic dextran sodium sulfate colitis models. Structure-function analyses of purified SPARCL1 identified the acidic domain of the protein necessary for its anti-angiogenic activity. Conclusions Our findings inaugurate SPARCL1 as a blood vessel–derived anti-angiogenic molecule required for vessel morphogenesis and integrity. SPARCL1 opens new perspectives as a vascular marker of susceptibility to colitis and as a therapeutic molecule to support blood vessel stability in this disease. <br
Keywords: angiogenesis; blood vessel; DSS colitis; endothelial cell; inflammatory bowel disease; permeability; SPARCL1

Matricellular protein SPARCL1 regulates tumor microenvironment-dependent endothelial cell heterogeneity in colorectal carcinoma - Naschberger, Elisabeth; Liebl, Andrea; Schellerer, Vera; Schütz, Manuela; Britzen-Laurent, Nathalie; Kölbel, Patrick; Schaal, Ute; Haep, Lisa; Regensburger, Daniela; Wittmann, Thomas; Klein-Hitpass, Ludger; Rau, Tilman; et al. (Journal of Clinical Investigation, 2016)
Different tumor microenvironments (TMEs) induce stromal cell plasticity that affects tumorigenesis. The impact of TME-dependent heterogeneity of tumor endothelial cells (TECs) on tumorigenesis is unclear. Here, we isolated pure TECs from human colorectal carcinomas (CRCs) that exhibited TMEs with either improved (Th1-TME CRCs) or worse clinical prognosis (control-TME CRCs). Transcriptome analyses identified markedly different gene clusters that reflected the tumorigenic and angiogenic activities of the respective TMEs. The gene encoding the matricellular protein SPARCL1 was most strongly upregulated in Th1-TME TECs. It was also highly expressed in ECs in healthy colon tissues and Th1-TME CRCs but low in control-TME CRCs. In vitro, SPARCL1 expression was induced in confluent, quiescent ECs and functionally contributed to EC quiescence by inhibiting proliferation, migration, and sprouting, whereas siRNA-mediated knockdown increased sprouting. In human CRC tissues and mouse models, vessels with SPARCL1 expression were larger and more densely covered by mural cells. SPARCL1 secretion from quiescent ECs inhibited mural cell migration, which likely led to stabilized mural cell coverage of mature vessels. Together, these findings demonstrate TME-dependent intertumoral TEC heterogeneity in CRC. They further indicate that TEC heterogeneity is regulated by SPARCL1, which promotes the cell quiescence and vessel homeostasis contributing to the favorable prognoses associated with Th1-TME CRCs.
EVALuna2:6838

Mbd2 enables tumourigenesis within the intestine while preventing tumour-promoting inflammation - May, Stephanie; Owen, Heather; Phesse, Toby J.; Greenow, Kirsty R.; Jones, Gareth-Rhys; Blackwood, Adam; Cook, Peter C.; Towers, Christopher; Gallimore, Awen M.; Williams, Geraint T.; Stürzl, Michael; Britzen-Laurent, Nathalie; et al. (Journal of Pathology, 2018)
Epigenetic regulation plays a key role in the link between inflammation and cancer. Here we examine Mbd2, which mediates epigenetic transcriptional silencing by binding to methylated DNA. In separate studies the Mbd2-/- mouse has been shown (1) to be resistant to intestinal tumourigenesis and (2) to have an enhanced inflammatory/immune response, observations that are inconsistent with the links between inflammation and cancer. To clarify its role in tumourigenesis and inflammation, we used constitutive and conditional models of Mbd2 deletion to explore its epithelial and non-epithelial roles in the intestine. Using a conditional model, we found that suppression of intestinal tumourigenesis is due primarily to the absence of Mbd2 within the epithelia. Next, we demonstrated, using the DSS colitis model, that non-epithelial roles of Mbd2 are key in preventing the transition from acute to tumour-promoting chronic inflammation. Combining models revealed that prior to inflammation the altered Mbd2-/- immune response plays a role in intestinal tumour suppression. However, following inflammation the intestine converts from tumour suppressive to tumour promoting. To summarise, in the intestine the normal function of Mbd2 is exploited by cancer cells to enable tumourigenesis, while in the immune system it plays a key role in preventing tumour-enabling inflammation. Which role is dominant depends on the inflammation status of the intestine. As environmental interactions within the intestine can alter DNA methylation patterns, we propose that Mbd2 plays a key role in determining whether these interactions are anti- or pro-tumourigenic and this makes it a useful new epigenetic model for inflammation-associated carcinogenesis. © 2018 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.
EVALuna2:210709

Mechanism of GTPase-activity-induced self-assembly of human guanylate binding protein 1. - Voepel, Tobias; Syguda, Adrian; Britzen-Laurent, Nathalie; Kunzelmann, Simone; Luedemann, Maik-Borris; Dovengerds, Christine; Stürzl, Michael; Herrmann, Christian (Journal of Molecular Biology, 2010)
Human guanylate binding protein 1 (hGBP1) belongs to the dynamin superfamily of large GTPases (LGs). In the course of GTP hydrolysis, the protein undergoes structural changes leading to self-assembly of the protein, which is a characteristic property of all family members. For self-assembly, the protein employs two distinct interaction sites, one of which is located within the LG domain of the protein located at the N-terminus, and the second is located in the C-terminal alpha-helical domain. Here, we identify intramolecular contacts between the LG domain and the helical part of hGBP1, which relay nucleotide-dependent structural changes from the N-terminus to the C-terminus and thereby mediate tetramer formation of the protein through a second contact site at the C-terminus. Furthermore, we demonstrate the impact of this intramolecular communication on the enzymatic activity of hGBP1 and on its cellular localization.

Mechanism of paclitaxel activity in Kaposi's sarcoma. - Sgadari, Cecilia; Toschi, Elena; Palladino, Clelia; Barillari, Giovanni; Carlei, Davide; Cereseto, Anna; Ciccolella, Cristiana; Yarchoan, Robert; Monini, Paolo; Stürzl, Michael; Ensoli, Barbara (Journal of Immunology, 2000)
Kaposi's sarcoma (KS) is an angioproliferative disease characterized by proliferation of spindle-shaped cells predominantly of endothelial cell origin, neoangiogenesis, inflammatory cell infiltration, and edema. At least in early stage, KS behaves as a reactive lesion sustained by the action of inflammatory cytokines and growth factors, has a polyclonal nature, and can regress. However, in time it can become monoclonal, especially in the nodular stage, evolving into a true sarcoma, likely in association with the increased expression of antiapoptotic oncogenes. We have recently demonstrated by immunohistochemical analysis that Bcl-2, a proto-oncogene known to prolong cellular viability and to antagonize apoptosis, is highly expressed in spindle cells and vessels of both AIDS-KS and classical KS lesions and that its expression increases with lesion stage. Paclitaxel, a microtubule-stabilizing drug known to inhibit Bcl-2 antiapoptotic activity and to be highly effective in the treatment of certain neoplasms, has recently been found to be active also in patients with advanced HIV-associated KS. In this report we investigated the mechanism(s) of paclitaxel activity in KS. By using a model of experimental KS induced by the inoculation of KS-derived spindle cells in nude mice and primary cultures of KS spindle cells, we found that paclitaxel promotes regression of KS lesions in vivo and that it blocks the growth, migration, and invasion of KS cells in vitro. Furthermore, paclitaxel treatment promoted apoptosis and down-regulated Bcl-2 protein expression in KS cells in vitro and in KS-like lesions in mice. Our results suggest that paclitaxel interferes with KS by down-regulating Bcl-2 antiapoptotic effect.

Melanocytes as an emerging key player in niche regulation of limbal stem cells - Schlötzer-Schrehardt, Ursula; Polisetti, Naresh; Zenkel, Matthias; Naschberger, Elisabeth; Heger, Lukas; Dudziak, Diana; Stürzl, Michael; Kruse, Friedrich (2018)
EVALuna2:34738

MiR-122, the regulator of the immune privileged liver - Gefen, Maytal; Layani, Shanny; Klahr, Emma; Hindi, Mor; Rosenberg, Nofar; Abramovitch, Rinat; Nachmansson, Nathalie; Yehezkel, Adi; Peled, Amnon; Rachmilewitz, Jacob; Abraham, Michal; Berger, Michael; et al. (JOURNAL OF HEPATOLOGY, 2022)
CRIS-Team WoS Importer:2022-08-12

MiRNA-21 Expression Decreases from Primary Tumors to Liver Metastases in Colorectal Carcinoma - Feiersinger, Fabian; Nolte, Elke; Wach, Sven; Rau, Tilman; Vassos, Nikolaos; Geppert, Carol-Immanuel; Konrad, Andreas; Merkel, Susanne; Taubert, Helge; Stürzl, Michael; Croner, Roland S. (PLoS ONE, 2016)
Metastasis is the major cause of death in colorectal cancer patients. Expression of certain miRNAs in the primary tumors has been shown to be associated with progression of colorectal cancer and the initiation of metastasis. In this study, we compared miRNA expression in primary colorectal cancer and corresponding liver metastases in order to get an idea of the oncogenic importance of the miRNAs in established metastases.We analyzed the expression of miRNA-21, miRNA-31 and miRNA-373 in corresponding formalin-fixed paraffin-embedded (FFPE) tissue samples of primary colorectal cancer, liver metastasis and healthy tissues of 29 patients by quantitative real-time PCR.All three miRNAs were significantly up-regulated in the primary tumor tissues as compared to healthy colon mucosa of the respective patients (p < 0.01). MiRNA-21 and miRNA-31 were also higher expressed in liver metastases as compared to healthy liver tissues (p < 0.01). No significant difference of expression of miRNA-31 and miRNA-373 was observed between primary tumors and metastases. Of note, miRNA-21 expression was significantly reduced in liver metastases as compared to the primary colorectal tumors (p < 0.01).In the context of previous studies demonstrating increased miRNA-21 expression in metastatic primary tumors, our findings raise the question whether miRNA-21 might be involved in the initiation but not in the perpetuation and growth of metastases.
EVALuna2:6831

Modulation of the extrinsic cell death signaling pathway by viral Flip induces acute-death mediated liver failure - Bittel, Miriam; Kremer, Andreas; Stürzl, Michael; Wirtz, Stefan; Stolzer, Iris; Neurath, Markus; Ballon, Gianna; Günther, Claudia (Cell Death & Disease, 2019)
During viral infections viruses express molecules that interfere with the host-cell death machinery and thus inhibit cell death responses. For example the viral FLIP (vFLIP) encoded by Kaposi’s sarcoma-associated herpesvirus interacts and inhibits the central cell death effector, Caspase-8. In order to analyze the impact of anti-apoptotic viral proteins, like vFlip, on liver physiology in vivo, mice expressing vFlip constitutively in hepatocytes (vFlipAlbCre+) were generated. Transgenic expression of vFlip caused severe liver tissue injury accompanied by massive hepatocellular necrosis and inflammation that finally culminated in early postnatal death of mice. On a molecular level, hepatocellular death was mediated by RIPK1-MLKL necroptosis driven by an autocrine TNF production. The loss of hepatocytes was accompanied by impaired bile acid production and disruption of the bile duct structure with impact on the liver-gut axis. Notably, embryonic development and tissue homeostasis were unaffected by vFlip expression. In summary our data uncovered that transgenic expression of vFlip can cause severe liver injury in mice, culminating in multiple organ insufficiency and death. These results demonstrate that viral cell death regulatory molecules exhibit different facets of activities beyond the inhibition of cell death that may merit more sophisticated in vitro and in vivo analysis.
CRIS-Team Scopus Importer:2019-12-03

Molecular characterization of peripheral arterial disease in proximal extremity arteries - Croner, Roland S.; Balzer, Klaus; Schellerer, Vera; Mueller, Volker; Schlabrakowsi, Anne; Stürzl, Michael; Naschberger, Elisabeth; Lang, Werner (Journal of Surgical Research, 2012)
Purpose: Although risk factors for atherosclerosis in peripheral arterial disease (PAD) are well defined, the underlying mechanisms are poorly understood and no medication exists for causal therapy. Molecular pathways that could be targeted have not been identified so far. To address this issue, we compared the molecular profiles of healthy versus PAD proximal femoral arteries. Methods: Gene expression profiles from proximal femoral arteries of patients with PAD (Fontaine stage IIb-IV; n = 20) and femoral arteries from healthy controls (CO) (n = 3) were compared by microarray technology. We evaluated all samples by histopathology and performed microdissection on the CO tissue before molecular analysis. We analyzed genes regarding their cellular localization, molecular function, and risk factors such as hypercholesterolemia, smoking, and diabetes. We used a selected panel of genes for polymerase chain reaction validation of microarray results and compared the data with previously published studies. Results: Most genes overexpressed in PAD versus CO were located in the cytoplasm, membrane, and nucleus. Functionally, they had binding activity to nucleotides, cytoskeletal proteins, and transcription factors. They were mainly involved in immune regulation (e.g., interleukin-8, chemokine ligand 18, and allograft-inflammatory factor-1) (P < 0.01). Down-regulated genes in PAD versus CO were located in the extracellular region. They had transporter and G-protein receptor activity. They were associated with signaling, cell growth, and tissue formation (e.g., myosin VB, marker for differentiated aortic smooth muscle, myosin 11) (P < 0.01). Polymerase chain reaction successfully validated the expression of the differences among 10 selected genes (e.g., chemokine ligand 18, common leukocyte antigen, killer cell lectin-like receptor subfamily B, member 1, and interleukin-8). Conclusions: Genes enrolled in immune regulation and inflammatory response were identified as key players in PAD. Various membrane-bound molecules with binding activity are hereunder. Identification of such molecules may elucidate relevant players that act as candidates for therapeutic targets or prognostic markers in the future. © 2012 Elsevier Inc. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Artheriosclerosis; Microarray; Molecular marker; Peripheral arterial disease

Molecularly characterised xenograft tumour mouse models: valuable tools for evaluation of new therapeutic strategies for secondary liver cancers. - Mischek, Daniela; Steinborn, Ralf; Petznek, Helga; Bichler, Christoph; Zatloukal, Kurt; Stürzl, Michael; Guenzburg, Walter H.; Hohenadl, Christine (Journal of Biomedicine and Biotechnology, 2009)
To develop and evaluate new therapeutic strategies for the treatment of human cancers, well-characterised preclinical model systems are a prerequisite. To this aim, we have established xenotransplantation mouse models and corresponding cell cultures from surgically obtained secondary human liver tumours. Established xenograft tumours were patho- and immunohistologically characterised, and expression levels of cancer-relevant genes were quantified in paired original and xenograft tumours and the derivative cell cultures applying RT-PCR-based array technology. Most of the characteristic morphological and immunohistochemical features of the original tumours were shown to be maintained. No differences were found concerning expression of genes involved in cell cycle regulation and oncogenesis. Interestingly, cytokine and matrix metalloproteinase encoding genes appeared to be expressed differentially. Thus, the established models are closely reflecting pathohistological and molecular characteristics of the selected human tumours and may therefore provide useful tools for preclinical analyses of new antitumour strategies in vivo.

Molecular mechanisms of lymphatic metastasis in solid tumors of the gastrointestinal tract. - Langheinrich, Melanie; Schellerer, Vera; Perrakis, Aristotelis; Lohmüller, Clemens; Schildberg, Claus; Naschberger, Elisabeth; Stürzl, Michael; Hohenberger, Werner; Croner, Roland S. (International Journal of Clinical and Experimental Pathology, 2012)
Tumor cell dissemination from the primary tumor site to distant organs is one of the characteristic properties of malignant tumors and represents a crucial step in the progression of disease. Although the pattern of spread may vary in different types of carcinomas, dissemination via the lymphatic system represents a common event in metastasis. The extent of lymph node metastasis is one of the major determinants for the prognosis of patients with gastrointestinal carcinomas and guides the therapeutically management. During the last decades, significant attention has been given to the molecular mechanisms that control lymphatic metastasis. The process of lymphangiogenesis has come into the focus. Lymphangiogenesis, the formation of newly lymphatics, comprises a series of complex cellular events and is controlled by a balance between pro- and anti-lymphangiogenic signals. This article will briefly describe the lymphatic system and then provide an overview of the molecular players involved in tumor lymphangiogenesis.

Molecular signature for lymphatic metastasis in colorectal carcinomas. - Croner, Roland S.; Förtsch, Thomas; Brueckl, Wolfgang M.; Roedel, Franz; Roedel, Claus; Papadopoulos, Thomas; Brabletz, Thomas; Kirchner, Thomas; Sachs, Martin; Behrens, Jürgen; Klein-Hitpass, Ludger; Stürzl, Michael; et al. (Annals of Surgery, 2008)
Fifty differently expressed genes between stage UICC I, II versus III CRC were identified respecting the selection criteria by allowing for multiple testing. The data validation by the independent clinical study confirmed our results. In comparison to MC, the genes were over- or underexpressed. They belong to various functional groups such as cellular adhesion, transporters, signaling, metabolism, protein synthesis, gene control, and immune system. Forty tumor samples of stage UICC I, II CRC, 40 samples of stage III CRC, and 25 biopsies of healthy mucosa (MC) were shock frozen in liquid nitrogen and underwent cryotomy after manual dissection for tumor tissue or MC enrichment. Isolated RNA was hybridized to GeneChips (HG-U133A, Affymetrix). Preprocessing of the microarray results was done by the robust multichip average method, and differentially expressed genes were selected by the maximum Wilcoxon statistic over 22,215 probe sets. The results were validated at an independent clinical study. Our large patient cohort and the data validation on an independent study identified 50 differentially expressed genes between CRC of different histopathologic stages. These findings indicate that molecular staging of CRC may be possible, which could help to guide individual CRC treatment before surgery. TNM-staging of colorectal carcinomas (CRC) relies on the histopathologic workup of the surgically removed specimen. If valid preoperative staging methods existed, patients could be selected for adequate individual therapy before surgery. Microarray techniques provide a promising tool to identify stage-specific molecular signatures on primary tumor biopsies. RESULTS MATERIAL AND METHODS CONCLUSION PURPOSE

Molecular staging of lymph node-negative colon carcinomas by one-step nucleic acid amplification (OSNA) results in upstaging of a quarter of patients in a prospective, European, multicentre study - Croner, R. S.; Geppert, Carol-Immanuel; Bader, F. G.; Nitsche, U.; Spaeth, C.; Rosenberg, R.; Zettl, A.; Matias-Guiu, Xavier; Tarragona, J.; Gueller, U.; Stürzl, Michael; Zuber, M. (British Journal of Cancer, 2014)
Background:Current histopathological staging procedures in colon carcinomas depend on midline division of the lymph nodes with one section of haematoxylin & eosin (H&E) staining only. By this method, tumour deposits outside this transection line may be missed and could lead to understaging of a high-risk group of stage UICC II cases, which recurs in 20% of cases. A new diagnostic semiautomated system, one-step nucleic acid amplification (OSNA), detects cytokeratin (CK) 19 mRNA in lymph node metastases and enables the investigation of the whole lymph node. The objective of this study was to assess whether histopathological pN0 patients can be upstaged to stage UICC III by OSNA.Methods:Lymph nodes from patients who were classified as lymph node negative after standard histopathology (single (H&E) slice) were subjected to OSNA. A result revealing a CK19 mRNA copy number >250, which makes sure to detect mainly macrometastases and not isolated tumour cells (ITC) or micrometastases only, was regarded as positive for lymph node metastases based on previous threshold investigations.Results:In total, 1594 pN0 lymph nodes from 103 colon carcinomas (median number of lymph nodes per patient: 14, range: 1-46) were analysed with OSNA. Out of 103 pN0 patients, 26 had OSNA-positive lymph nodes, resulting in an upstaging rate of 25.2%. Among these were 6/37 (16.2%) stage UICC I and 20/66 (30.3%) stage UICC II patients. Overall, 38 lymph nodes were OSNA positive: 19 patients had one, 3 had two, 3 had three, and 1 patient had four OSNA-positive lymph nodes.Conclusions:OSNA resulted in an upstaging of over 25% of initially histopathologically lymph node-negative patients. OSNA is a standardised, observer-independent technique, allowing the analysis of the whole lymph node. Therefore, sampling bias due to missing investigation of certain lymph node tissue can be avoided, which may lead to a more accurate staging.
EVALuna2:6584

Moonlighting chromatin: when DNA escapes nuclear control - Singh, Jeeshan; Boettcher, Michael; Dölling, Maximilian; Heuer, Annika; Hohberger, Bettina; Leppkes, Moritz; Naschberger, Elisabeth; Schapher, Mirco; Schauer, Christine; Schoen, Janina; Stürzl, Michael; Vitkov, Ljubomir; et al. (Cell Death and Differentiation, 2023)
Extracellular chromatin, for example in the form of neutrophil extracellular traps (NETs), is an important element that propels the pathological progression of a plethora of diseases. DNA drives the interferon system, serves as autoantigen, and forms the extracellular scaffold for proteins of the innate immune system. An insufficient clearance of extruded chromatin after the release of DNA from the nucleus into the extracellular milieu can perform a secret task of moonlighting in immune-inflammatory and occlusive disorders. Here, we discuss (I) the cellular events involved in the extracellular release of chromatin and NET formation, (II) the devastating consequence of a dysregulated NET formation, and (III) the imbalance between NET formation and clearance. We include the role of NET formation in the occlusion of vessels and ducts, in lung disease, in autoimmune diseases, in chronic oral disorders, in cancer, in the formation of adhesions, and in traumatic spinal cord injury. To develop effective therapies, it is of utmost importance to target pathways that cause decondensation of chromatin during exaggerated NET formation and aggregation. Alternatively, therapies that support the clearance of extracellular chromatin are conceivable. [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2023-02-17

Morphologic HIV demonstration in formalin embedded material–techniques, problems, results - Zietz, Christian; Speiser, B; Hell, W; Stürzl, Michael; Wolf, H; Roth, W K (Verhandlungen der Deutschen Gesellschaft für Pathologie, 1991)
Formalin-fixed, paraffin-embedded material of archival specimens is suitable for a morphological HIV-detection: Infected cells with HIV in the proliferative phase can be demonstrated with reliable results on tissue sections by immunohistological technics using new antibodies. In situ nucleic acid hybridisation technics can also show HIV in the expression phase on paraffin-embedded material, but often fail in demonstrating latently HIV-infected cells. The DNA-Polymerase chain reaction can detect latent Provirus in morphologically defined areas of paraffin sections even in autopsy material, i.e. lymphnodes and even eyes of patients with HIV-Infection, but requires precaution and control with respect to contamination.

Multiple interferon regulatory factor and NF-κB sites cooperate in mediating cell-type-and maturation-specific activation of the human CD83 promoter in dendritic cells - Stein, Marcello F.; Lang, Stefan; Winkler, Thomas; Deinzer, Anja; Erber, Sebastian; Nettelbeck, Dirk M.; Naschberger, Elisabeth; Jochmann, Ramona; Stürzl, Michael; Slany, Robert; Werner, Thomas; Steinkasserer, Alexander; et al. (Molecular and Cellular Biology, 2013)
CD83 is one of the best-known surface markers for fully mature dendritic cells (mature DCs), and its cell-type-and maturationspecific regulation makes the CD83 promoter an interesting tool for the genetic modulation of DCs. To determine the mechanisms regulating this DC-and maturation-specific CD83 expression, chromatin immunoprecipitation (ChIP)-on-chip microarray, biocomputational, reporter, electrophoretic mobility shift assay (EMSA), and ChIP analyses were performed. These studies led to the identification of a ternary transcriptional activation complex composed of an upstream regulatory element, a minimal promoter, and an enhancer, which have not been reported in this arrangement for any other gene so far. Notably, these DNA regions contain a complex framework of interferon regulatory factor (IRF)-and NF-κB transcription factor-binding sites mediating their arrangement. Mutation of any of the IRF-binding sites resulted in a significant loss of promoter activity, whereas overexpression of NF-κB transcription factors clearly enhanced transcription. We identified IRF-1, IRF-2, IRF-5, p50, p65, and cRel to be involved in regulating maturation-specific CD83 expression in DCs. Therefore, the characterization of this promoter complex not only contributes to the knowledge of DC-specific gene regulation but also suggests the involvement of a transcriptional module with binding sites separated into distinct regions in transcriptional activation as well as cell-type-and maturation-specific transcriptional targeting of DCs. © 2013, American Society for Microbiology.

Neutrophil extracellular traps drive epithelial‐mesenchymal transition of human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Straube, Julia; Tripal, Philipp; Schmid, Benjamin; Geppert, Carol-Immanuel; Hartmann, Arndt; Munoz, Luis Enrique; Schoen, Janina; Völkl, Simon; et al. (Journal of Pathology, 2021)
Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity, and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high-resolution stimulated emission depletion (STED) microscopy we showed that citrullinated histone H3 (H3cit) is sufficient to specifically detect citrullinated NETs in colon cancer tissues. Among other evidence this was supported by the close association of H3cit with de-condensed extracellular DNA, the hallmark of NETs. Extracellular DNA was reliably differentiated from nuclear condensed DNA by staining with an anti-DNA-antibody providing a novel and valuable tool to detect NETs in FFPE tissues. Using these markers, the clinical association of NETs has been investigated in a cohort of 85 patients with colon cancer. NETs were frequently detected (n = 37/n = 85, 44%) in colon cancer tissue sections and preferentially localized either only in the tumour centre or both, in the tumour centre and the invasive front. Of note, citrullinated NETs were significantly associated with high histopathologic tumour grades and lymph node metastasis. In vitro, purified NETs induced filopodia formation and cell motility in CRC cell lines. This was associated with increased expression of mesenchymal marker mRNAs (vimentin [VIM], fibronectin [FN1]) and epithelial- mesenchymal transition (EMT) promoting transcription factors (ZEB1 and Slug [SNAI2]) as well as decreased expression of the epithelial markers E-cadherin (CDH1) and EpCAM (EPCAM). These findings indicated that NETs activate an EMT-like process in CRC cells and may contribute to the metastatic progression of CRC.
Keywords: epithelial–mesenchymal transition (EMT); colorectal neoplasms; stimulated emission depletion (STED) microscopy; neutrophils; migration; extracellular traps

N-glycosylation Regulates Intrinsic IFN-γ Resistance in Colorectal Cancer: Implications for Immunotherapy - Krug, Julia; Rodrian, Gabriele; Petter, Katja; Yang, Hai; Khoziainova, Svetlana; Guo, Wei; Benard, Alan; Merkel, Susanne; Gellert, Susan; Maschauer, Simone; Spermann, Monika; Waldner, Maximilian; et al. (Gastroenterology, 2023)
Background & AIMS: Advanced colorectal carcinoma (CRC) is characterized by a high frequency of primary immune evasion and refractoriness to immunotherapy. Given the importance of interferon (IFN)-γ in CRC immunosurveillance, we investigated whether and how acquired IFN-γ resistance in tumor cells would promote tumor growth, and whether IFN-γ sensitivity could be restored. Methods: Spontaneous and colitis-associated CRC development was induced in mice with a specific IFN-γ pathway inhibition in intestinal epithelial cells. The influence of IFN-γ pathway gene status and expression on survival was assessed in patients with CRC. The mechanisms underlying IFN-γ resistance were investigated in CRC cell lines. Results: The conditional knockout of the IFN-γ receptor in intestinal epithelial cells enhanced spontaneous and colitis-associated colon tumorigenesis in mice, and the loss of IFN-γ receptor α (IFNγRα) expression by tumor cells predicted poor prognosis in patients with CRC. IFNγRα expression was repressed in human CRC cells through changes in N-glycosylation, which decreased protein stability via proteasome-dependent degradation, inhibiting IFNγR-signaling. Downregulation of the bisecting N-acetylglucosaminyltransferase III (MGAT3) expression was associated with IFN-γ resistance in all IFN-γ–resistant cells, and highly correlated with low IFNγRα expression in CRC tissues. Both ectopic and pharmacological reconstitution of MGAT3 expression with all-trans retinoic acid increased bisecting N-glycosylation, as well as IFNγRα protein stability and signaling. Conclusions: Together, our results demonstrated that tumor-associated changes in N-glycosylation destabilize IFNγRα, causing IFN-γ resistance in CRC. IFN-γ sensitivity could be reestablished through the increase in MGAT3 expression, notably via all-trans retinoic acid treatment, providing new prospects for the treatment of immune-resistant CRC.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Colon Cancer; IFNGR1; Immune Evasion

No NETs no TIME: Crosstalk between neutrophil extracellular traps and the tumor immune microenvironment - Fang, Qi; Stehr, Antonia; Naschberger, Elisabeth; Knopf, Jasmin; Herrmann, Martin; Stürzl, Michael (Frontiers in Immunology, 2022)
The tumor immune microenvironment (TIME) controls tumorigenesis. Neutrophils are important components of TIME and control tumor progression and therapy resistance. Neutrophil extracellular traps (NETs) ejected by activated neutrophils are net-like structures composed of decondensed extracellular chromatin filaments decorated with a plethora of granules as well as cytoplasmic proteins. Many of these harbour post translational modifications. Cancer cells reportedly trigger NET formation, and conversely, NETs alter the TIME and promote tumor cell proliferation and migration. The specific interactions between NETs and TIME and the respective effects on tumor progression are still elusive. In certain tumors, a CD4(+) T helper (Th) 2 cell-associated TIME induces NETs and exerts immunosuppressive functions via programmed death 1 (PD-1)/PD-L1, both associated with poorer prognosis. In other cases, NETs induce the proliferation of Th1 cells, associated with an improved prognosis in cancer. In addition, NETs can drive macrophage polarization and often rely on macrophages to promote cancer cell invasion and metastasis. In turn, macrophages can swiftly clear NETs in an immunologically silent manner. The aim of this review is to summarize the knowledge about the mutual interaction between NETs and TIME and its impact on tumor growth and therapy.
CRIS-Team WoS Importer:2023-01-27
Keywords: adaptive immunity; innate immunity; macrophages; cancer; immunotherapy; tumor microenvironment; neutrophil extracellular traps; neutrophils

Noninvasive Bioluminescence Imaging of AKT Kinase Activity in Subcutaneous and Orthotopic NSCLC Xenografts: Correlation of AKT Activity with Tumor Growth Kinetics - Suchowski, Karina; Poechinger, Thomas; Rehemtulla, Alnawaz; Stürzl, Michael; Scheuer, Werner (Neoplasia, 2017)
Aberrant signaling through the AKT kinase mediates oncogenic phenotypes including cell proliferation, survival, and therapeutic resistance. Here, we utilize a bioluminescence reporter for AKT kinase activity (BAR) to noninvasively assess the therapeutic efficacy of the EGFR inhibitor erlotinib in KRAS-mutated lung cancer therapy. A549 non-small cell lung cancer cell line, engineered to express BAR, enabled the evaluation of compounds targeting the EGFR/PI3K/AKT pathway in vitro as well as in mouse models. We found that erlotinib treatment of resistant A549 subcutaneous and orthotopic xenografts resulted in significant AKT inhibition as determined by an 8- to 13-fold (P < .0001) increase in reporter activity 3 hours after erlotinib (100 mg/kg) administration compared to the control. This was confirmed by a 25% (P < .0001) decrease in pAKT ex vivo and a decrease in tumor growth. Treatment of the orthotopic xenograft with varying doses of erlotinib (25, 50, and 100 mg/kg) revealed a dose- and time-dependent increase in reporter activity (10-, 12-, and 23-fold). Correspondingly, a decrease in phospho-AKT levels (0%, 16%, and 28%, respectively) and a decrease in the AKT dependent proliferation marker PCNA (0%, 50%, and 50%) were observed. We applied ?-CT imaging for noninvasive longitudinal quantification of lung tumor load which revealed a corresponding decrease in tumor growth in a dose-dependent manner. These findings demonstrate the utility of BAR to noninvasively monitor AKT activity in preclinical studies in response to AKT modulating agents. These results also demonstrate that BAR can be applied to study drug dosing, drug combinations, and treatment efficacy in orthotopic mouse lung tumor models.
EVALuna2:15309

Notch3 signalling promotes tumour growth in colorectal cancer - Serafin, Valentina; Persano, Luca; Moserle, Lidia; Esposito, Giovanni; Ghisi, Margherita; Curtarello, Matteo; Bonanno, Laura; Masiero, Massimo; Ribatti, Domenico; Stürzl, Michael; Naschberger, Elisabeth; Croner, Roland S.; et al. (Journal of Pathology, 2011)
Increased Notch1 activity has been observed in intestinal tumours, partially accomplished by β-catenin-mediated up-regulation of the Notch ligand Jagged-1. Whether further mechanisms of Notch activation exist and other Notch receptors might be involved is unclear. Microarray data indicated that Notch3 transcript levels are significantly up-regulated in primary and metastatic CRC samples compared to normal mucosa. Moreover, Notch3 protein was expressed at strong/moderate levels by 19.7% of 158 CRC samples analysed, and at weak levels by 51.2% of the samples. Intrigued by these findings, we sought to investigate whether Notch3 modulates oncogenic features of CRC cells. By exploiting xenografts of CRC cells with different tumourigenic properties in mice, we found that the aggressive phenotype was associated with altered expression of components of the Notch pathway, including Notch3, Delta-like 4 (DLL4), and Jagged-1 ligands. Stimulation with immobilized recombinant DLL4 or transduction with DLL4-expressing vectors dramatically increased Notch3 expression in CRC cells, associated with accelerated tumour growth. Forced expression of an active form of Notch3 mirrored the effects of DLL4 stimulation and increased tumour formation. Conversely, attenuation of Notch3 levels by shRNA resulted in perturbation of the cell cycle followed by reduction in cell proliferation, clonogenic capacity, and inhibition of tumour growth. Altogether, these findings indicate that Notch3 can modulate the tumourigenic properties of CRC cells and contributes to sustained Notch activity in DLL4-expressing tumours. Copyright © 2011 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
Created from Fastlane, Scopus look-up
Keywords: angiogenesis; colorectal cancer; DLL4; Notch3

Nuclear factor-κB motif and interferon-α-stimulated response element co-operate in the activation of guanylate-binding protein-1 expression by inflammatory cytokines in endothelial cells - Naschberger, Elisabeth; Stürzl, Michael; et al. (Biochemical Journal, 2004)
The large GTPase GBP-1 (guanylate-binding protein -1) is a major IFN-γ (interferon-γ)-induced protein with potent anti-angiogenic activity in endothelial cells. An ISRE (IFN-α-stimulated response element) is necessary and sufficient for the induction of GBP-1 expression by IFN-γ. Recently, we have shown that in vivo GBP-1 expression is strongly endothelial-cell-associated and is, in addition to IFN-γ, also activated by interleukin-1β and tumour necrosis factor-α, both in vitro and in vivo [Lubeseder-Martellato, Guenzi, Jörg, Töpolt, Naschberger, Kremmer, Zietz, Tschachler, Hutzler, Schwemmle et al. (2002) Am. J. Pathol. 161, 1749-1759; Guenzi, Töpolt, Cornali, Lubeseder-Martellato, Jörg, Matzen, Zietz, Kremmer, Nappi, Schwemmle et al. (2001) EMBO J. 20, 5568-5577]. In the present study, we identified a NF-κB (nuclear factor κB)-binding motif that, together with ISRE, is required for the induction of GBP-1 expression by interleukin-1β and tumour necrosis factor-α. Deactivation of the NF-κB motif reduced the additive effects of combinations of these cytokines with IFN-γ by more than 50%. Importantly, NF-κB p50 rather than p65 activated the GBP-1 promoter. The NF-κB motif and ISRE were detected in an almost identical spatial organization, as in the GBP-1 promoter, in the promoter regions of various inflammation-associated genes. Therefore both motifs may constitute a cooperative inflammatory cytokine response module that regulates GBP-1 expression. Our findings may open new perspectives for the use of NF-κB inhibitors to support angiogenesis in inflammatory diseases including ischaemia.
Created from Fastlane, Scopus look-up
Keywords: Guanylate-binding protein-1 (GBP-1); Human umbilical-vein endothelial cells (HUVEC); Inflammation; Interleukin-1; Nuclear factor κB (NF-κB); Tumour necrosis factor

Nucleotide-dependent farnesyl switch orchestrates polymerization and membrane binding of human guanylate-binding protein 1 - Shydlovskyi, Sergii; Zienert, Anke Y.; Ince, Semra; Dovengerds, Christine; Hohendahl, Annika; Dargazanli, Julia M.; Blum, Ailisa; Guenther, Saskia D.; Kladt, Nikolay; Stürzl, Michael; Schauss, Astrid C.; Kutsch, Miriam; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2017)
Dynamin-like proteins (DLPs) mediate various membrane fusion and fission processes within the cell, which often require the polymerization of DLPs. An IFN-inducible family of DLPs, the guanylate-binding proteins (GBPs), is involved in antimicrobial and antiviral responses within the cell. Human guanylate-binding protein 1 (hGBP1), the founding member of GBPs, is also engaged in the regulation of cell adhesion and migration. Here, we show how the GTPase cycle of farnesylated hGBP1 (hGBP1F) regulates its self-assembly and membrane interaction. Using vesicles of various sizes as a lipid bilayer model, we show GTP-dependent membrane binding of hGBP1F In addition, we demonstrate nucleotide-dependent tethering ability of hGBP1F Furthermore, we report nucleotide-dependent polymerization of hGBP1F, which competes with membrane binding of the protein. Our results show that hGBP1F acts as a nucleotide-controlled molecular switch by modulating the accessibility of its farnesyl moiety, which does not require any supportive proteins.
EVALuna2:15310

O-GlcNAc transferase inhibits KSHV propagation and modifies replication relevant viral proteins as detected by systematic O-GlcNAcylation analysis. - Jochmann, Ramona; Pfannstiel, Jens; Chudasama, Priya; Kühn, Elisabeth; Konrad, Andreas; Stürzl, Michael (Glycobiology, 2013)
O-GlcNAcylation is an inducible, highly dynamic and reversible post-translational modification, mediated by a unique enzyme named O-linked N-acetyl-d-glucosamine (O-GlcNAc) transferase (OGT). In response to nutrients, O-GlcNAc levels are differentially regulated on many cellular proteins involved in gene expression, translation, immune reactions, protein degradation, protein-protein interaction, apoptosis and signal transduction. In contrast to eukaryotic cells, little is known about the role of O-GlcNAcylation in the viral life cycle. Here, we show that the overexpression of the OGT reduces the replication efficiency of Kaposi's sarcoma-associated herpesvirus (KSHV) in a dose-dependent manner. In order to investigate the global impact of O-GlcNAcylation in the KSHV life cycle, we systematically analyzed the 85 annotated KSHV-encoded open reading frames for O-GlcNAc modification. For this purpose, an immunoprecipitation (IP) strategy with three different approaches was carried out and the O-GlcNAc signal of the identified proteins was properly controlled for specificity. Out of the 85 KSHV-encoded proteins, 18 proteins were found to be direct targets for O-GlcNAcylation. Selected proteins were further confirmed by mass spectrometry for O-GlcNAc modification. Correlation of the functional annotation and the O-GlcNAc status of KSHV proteins showed that the predominant targets were proteins involved in viral DNA synthesis and replication. These results indicate that O-GlcNAcylation plays a major role in the regulation of KSHV propagation.

O-linked N-acetylglucosaminylation of Sp1 inhibits the human immunodeficiency virus type 1 promoter - Jochmann, Ramona; Thurau, Mathias; Jung, Susan; Hofmann, Christian; Naschberger, Elisabeth; Kremmer, Elisabeth; Harrer, Thomas; Miller, Matthew; Schaft, Niels; Stürzl, Michael (Journal of Virology, 2009)
Human immunodeficiency virus type 1 (HIV-1) gene expression and replication are regulated by the promoter/enhancer located in the U3 region of the proviral 5′ long terminal repeat (LTR). The binding of cellular transcription factors to specific regulatory sites in the 5′ LTR is a key event in the replication cycle of HIV-1. Since transcriptional activity is regulated by the posttranslational modification of transcription factors with the monosaccharide O-linked N-acetyl-D-glucosamine (O-GlcNAc), we evaluated whether increased O-GlcNAcylation affects HIV-1 transcription. In the present study we demonstrate that treatment of HIV-1-infected lymphocytes with the O-GlcNAcylation-enhancing agent glucosamine (GlcN) repressed viral transcription in a dose-dependent manner. Overexpression of O-GlcNAc transferase (OGT), the sole known enzyme catalyzing the addition of O-GlcNAc to proteins, specifically inhibited the activity of the HIV-1 LTR promoter in different T-cell lines and in primary CD4+ T lymphocytes. Inhibition of HIV-1 LTR activity in infected T cells was most efficient (>95%) when OGT was recombinantly overexpressed prior to infection. O-GlcNAcylation of the transcription factor Sp1 and the presence of Sp1-binding sites in the LTR were found to be crucial for this inhibitory effect. From this study, we conclude that O-GlcNAcylation of Sp1 inhibits the activity of the HIV-1 LTR promoter. Modulation of Sp1 O-GlcNAcylation may play a role in the regulation of HIV-1 latency and activation and links viral replication to the glucose metabolism of the host cell. Hence, the establishment of a metabolic treatment might supplement the repertoire of antiretroviral therapies against AIDS. Copyright © 2009, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up

Oncogenesis in HIV-infection. - Albini, Adriana; Aluigi, M; Benelli, Roberto; Biberfeld, Peter; Blasig, C; Calabro, M; Calvo, F; Chieco-Bianchi, L; Corbellino, M; Del Mistro, A; Ekman, M; Favero, A; et al. (International Journal of Oncology, 1996)
The presence of human Kaposi's sarcoma associated herpesvirus-like sequences (KSHV) was examined in different epidemiological variants of Kaposi's sarcoma (KS) and in KS-derived cell cultures by polymerase chain reaction (PCR). KSHV DNA was present in all tumor biopsies of AIDS-associated KS (59 biopsies), endemic KS (26 biopsies; 21 African endemic KS, 5 Greek endemic KS), sporadic/classical KS (28 biopsies) and post-transplant/iatrogenic KS (6 of 7 biopsies). On the contrary, these sequences were only detected rarely in non-involved skin of KS patients (3 positive specimens of 12), in the peripheral blood mononuclear cells of HIV-infected patients (3 positive specimens of 54) and in lymphoma-biopsies (3 positive specimens of 47). Cell cultures derived from KS skin lesions were positive for KSHV DNA only in the first two passages. However, two longer-term positive cultures from a biopsy of a patient affected with sporadic KS and a biopsy of a patient affected with epidemic KS was identified. A strong association of KSHV with KS tissue was observed in all the different epidemiological variants of KS. Long-term positive KS-derived cell cultures will be an important tool to study the herpesvirus-like agent and to investigate its functional role in the initiation and progression of KS.

One Step Nucleic Acid Amplification (OSNA) - a new method for lymph node staging in colorectal carcinomas - Croner, Roland S.; Schellerer, Vera; Demund, Helene; Schildberg, Claus; Papadopulos, Thomas; Naschberger, Elisabeth; Stürzl, Michael; Matzel, Klaus E.; Hohenberger, Werner; Schlabrakowski, Anne (Journal of Translational Medicine, 2010)
Background: Accurate histopathological evaluation of resected lymph nodes (LN) is essential for the reliable staging of colorectal carcinomas (CRC). With conventional sectioning and staining techniques usually only parts of the LN are examined which might lead to incorrect tumor staging. A molecular method called OSNA (One Step Nucleic Acid Amplification) may be suitable to determine the metastatic status of the complete LN and therefore improve staging.Methods: OSNA is based on a short homogenisation step and subsequent automated amplification of cytokeratin 19 (CK19) mRNA directly from the sample lysate, with result available in 30-40 minutes. In this study 184 frozen LN from 184 patients with CRC were investigated by both OSNA and histology (Haematoxylin & Eosin staining and CK19 immunohistochemistry), with half of the LN used for each method. Samples with discordant results were further analysed by RT-PCR for CK19 and carcinoembryonic antigen (CEA).Results: The concordance rate between histology and OSNA was 95.7%. Three LN were histology+/OSNA- and 5 LN histology-/OSNA+. RT-PCR supported the OSNA result in 3 discordant cases, suggesting that metastases were exclusively located in either the tissue analysed by OSNA or the tissue used for histology. If these samples were excluded the concordance was 97.2%, the sensitivity 94.9%, and the specificity 97.9%. Three patients (3%) staged as UICC I or II by routine histopathology were upstaged as LN positive by OSNA. One of these patients developed distant metastases (DMS) during follow up.Conclusion: OSNA is a new and reliable method for molecular staging of lymphatic metastases in CRC and enables the examination of whole LN. It can be applied as a rapid diagnostic tool to estimate tumour involvement in LN during the staging of CRC. © 2010 Croner et al; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up

p21 Prevents the Exhaustion of CD4+ T Cells Within the Antitumor Immune Response Against Colorectal Cancer - Thoma, Oana-Maria; Naschberger, Elisabeth; Kubánková, Markéta; Larafa, Imen; Kramer, Viktoria; Menchicchi, Bianca; Merkel, Susanne; Britzen-Laurent, Nathalie; Jefremow, André; Grützmann, Robert; Koop, Kristina; Neufert, Clemens; et al. (Gastroenterology, 2024)
Background & Aims: T cells are crucial for the antitumor response against colorectal cancer (CRC). T-cell reactivity to CRC is nevertheless limited by T-cell exhaustion. However, molecular mechanisms regulating T-cell exhaustion are only poorly understood. Methods: We investigated the functional role of cyclin-dependent kinase 1a (Cdkn1a or p21) in cluster of differentiation (CD) 4+ T cells using murine CRC models. Furthermore, we evaluated the expression of p21 in patients with stage I to IV CRC. In vitro coculture models were used to understand the effector function of p21-deficient CD4+ T cells. Results: We observed that the activation of cell cycle regulator p21 is crucial for CD4+ T-cell cytotoxic function and that p21 deficiency in type 1 helper T cells (Th1) leads to increased tumor growth in murine CRC. Similarly, low p21 expression in CD4+ T cells infiltrated into tumors of CRC patients is associated with reduced cancer-related survival. In mouse models of CRC, p21-deficient Th1 cells show signs of exhaustion, where an accumulation of effector/effector memory T cells and CD27/CD28 loss are predominant. Immune reconstitution of tumor-bearing Rag1−/− mice using ex vivo-treated p21-deficient T cells with palbociclib, an inhibitor of cyclin-dependent kinase 4/6, restored cytotoxic function and prevented exhaustion of p21-deficient CD4+ T cells as a possible concept for future immunotherapy of human disease. Conclusions: Our data reveal the importance of p21 in controlling the cell cycle and preventing exhaustion of Th1 cells. Furthermore, we unveil the therapeutic potential of cyclin-dependent kinase inhibitors such as palbociclib to reduce T-cell exhaustion for future treatment of patients with colorectal cancer.
CRIS-Team Scopus Importer:2024-01-19
Keywords: CD4; Colorectal Cancer; p21; Palbociclib

Pathological function of neutrophil extracellular traps in human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Tripal, Philipp; Geppert, Carol-Immanuel; Merkel, Susanne; Herrmann, Martin; Stürzl, Michael (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Pathophysiological role of guanylate-binding proteins in gastrointestinal diseases - Britzen-Laurent, Nathalie; Herrmann, Christian; Naschberger, Elisabeth; Croner, Roland S.; Stürzl, Michael (World Journal of Gastroenterology, 2016)
Guanylate-binding proteins (GBPs) are interferon-stimulated factors involved in the defense against cellular pathogens and inflammation. These proteins, particularly GBP-1, the most prominent member of the family, have been established as reliable markers of interferon-?-activated cells in various diseases, including colorectal carcinoma (CRC) and inflammatory bowel diseases (IBDs). In CRC, GBP-1 expression is associated with a Th1-dominated angiostatic micromilieu and is correlated with a better outcome. Inhibition of tumor growth by GBP-1 is the result of its strong anti-angiogenic activity as well as its direct anti-tumorigenic effect on tumor cells. In IBD, GBP-1 mediates the anti-proliferative effects of interferon-? on intestinal epithelial cells. In addition, it plays a protective role on the mucosa by preventing cell apoptosis, by inhibiting angiogenesis and by regulating the T-cell receptor signaling. These functions rely to a large extent on the ability of GBP-1 to interact with and remodel the actin cytoskeleton.
EVALuna2:15238

Patients with COVID-19: in the dark-NETs of neutrophils - Ackermann, Maximilian; Anders, Hans-Joachim; Bilyy, Rostyslav; Bowlin, Gary L.; Daniel, Christoph; De Lorenzo, Rebecca; Egeblad, Mikala; Henneck, Timo; Hidalgo, Andres; Hoffmann, Markus; Hohberger, Bettina; Kanthi, Yogendra; et al. (Cell Death and Differentiation, 2021)
SARS-CoV-2 infection poses a major threat to the lungs and multiple other organs, occasionally causing death. Until effective vaccines are developed to curb the pandemic, it is paramount to define the mechanisms and develop protective therapies to prevent organ dysfunction in patients with COVID-19. Individuals that develop severe manifestations have signs of dysregulated innate and adaptive immune responses. Emerging evidence implicates neutrophils and the disbalance between neutrophil extracellular trap (NET) formation and degradation plays a central role in the pathophysiology of inflammation, coagulopathy, organ damage, and immunothrombosis that characterize severe cases of COVID-19. Here, we discuss the evidence supporting a role for NETs in COVID-19 manifestations and present putative mechanisms, by which NETs promote tissue injury and immunothrombosis. We present therapeutic strategies, which have been successful in the treatment of immunο-inflammatory disorders and which target dysregulated NET formation or degradation, as potential approaches that may benefit patients with severe COVID-19.
CRIS-Team Scopus Importer:2021-06-04

PCR-synthesized single-stranded DNA: a useful tool for 'hyb' and 'HAP' standardization for construction of subtraction libraries. - Stürzl, Michael; Roth, Willy Kurt (Trends in Genetics, 1990)

Permeability analyses and three dimensional imaging of interferon gamma-induced barrier disintegration in intestinal organoids - Bardenbacher, Marco; Ruder, Barbara; Britzen-Laurent, Nathalie; Schmid, Benjamin; Waldner, Maximilian; Naschberger, Elisabeth; Scharl, Michael; Mueller, Werner; Günther, Claudia; Becker, Christoph; Stürzl, Michael; Tripal, Philipp (Stem Cell Research, 2019)
The aberrant regulation of the epithelial barrier integrity is involved in many diseases of the digestive tract, including inflammatory bowel diseases and colorectal cancer. Intestinal epithelial cell organoid cultures provide new perspectives for analyses of the intestinal barrier in vitro. However, established methods of barrier function analyses from two dimensional cultures have to be adjusted to the analysis of three dimensional organoid structures. Here we describe the methodology for analysis of epithelial barrier function and molecular regulation in intestinal organoids. Barrier responses to interferon-y of intestinal organoids with and without epithelial cellspecific deletion of the interferon-y-receptor 2 gene were used as a model system. The established method allowed monitoring of the kinetics of interferon-y-induced permeability changes in living organoids. Proteolytic degradation and altered localization of the tight junction proteins claudin-2, -7, and - 15 was detected using confocal spinning disc microscopy with 3D reconstruction. Hessian analysis was used for quantification of relocalization of claudins. In summary, we provide a novel methodologic approach for quantitative analyses of intestinal epithelial barrier functions in the 3D organoid model.
CRIS-Team WoS Importer:2019-03-12

Predicting Clinical Outcomes in Colorectal Cancer Using Machine Learning - Gründner, Julian; Prokosch, Hans-Ulrich; Stürzl, Michael; Croner, Roland S.; Christoph, Jan; Toddenroth, Dennis (Studies in health technology and informatics, 2018)
Using gene markers and other patient features to predict clinical outcomes plays a vital role in enhancing clinical decision making and improving prognostic accuracy. This work uses a large set of colorectal cancer patient data to train predictive models using machine learning methods such as random forest, general linear model, and neural network for clinically relevant outcomes including disease free survival, survival, radio-chemotherapy response (RCT-R) and relapse. The most successful predictive models were created for dichotomous outcomes like relapse and RCT-R with accuracies of 0.71 and 0.70 on blinded test data respectively. The best prediction models regarding overall survival and disease-free survival had C-Index scores of 0.86 and 0.76 respectively. These models could be used in the future to aid a decision for or against chemotherapy and improve survival prognosis. We propose that future work should focus on creating reusable frameworks and infrastructure for training and delivering predictive models to physicians, so that they could be readily applied to other diseases in practice and be continuously developed integrating new data.
EVALuna2:209471

Predictive value of PD-L1 based on mRNA level in the treatment of stage IV melanoma with ipilimumab - Brueggemann, C.; Kirchberger, M. C.; Goldinger, S. M.; Weide, B.; Konrad, A.; Erdmann, M.; Schadendorf, D.; Croner, R. S.; Krahenbuhl, L.; Kaehler, K. C.; Hafner, C.; Leisgang, W.; et al. (Journal of Cancer Research and Clinical Oncology, 2017)
PD-L1 is established as a predictive marker for therapy of non-small cell lung cancer with pembrolizumab. Furthermore, PD-L1 positive melanoma has shown more favorable outcomes when treated with anti-PD1 antibodies and dacarbazine compared to PD-L1 negative melanoma. However, the role of PD-L1 expression with regard to response to checkpoint inhibition with anti-CTLA-4 is not clear, yet. In addition, the lack of standardization in the immunohistochemical assessment of PD-L1 makes the comparison of results difficult. In this study, we investigated the PD-L1 gene expression with a new fully automated technique via RT-PCR and correlated the findings with the response to the anti-CTLA-4 antibody ipilimumab.Within a retrospective multi-center trial, PD-L1 gene expression was evaluated in 78 melanoma patients in a total of 111 pre-treatment tumor samples from 6 skin cancer centers and analyzed with regard to response to ipilimumab. For meaningful statistical analysis, the cohort was enriched for responders with 30 responders and 48 non-responders. Gene expression was assessed by quantitative RT-PCR after extracting mRNA from formalin-fixed paraffin embedded tumor tissue and correlated with results from immunohistochemical (IHC) stainings.The evaluation of PD-L1 expression based on mRNA level is feasible. Correlation between PD-L1 expression as assessed by IHC and RT-PCR showed varying levels of concordance depending on the antibody employed. RT-PCR should be further investigated to measure PD-L1 expression, since it is a semi-quantitative method with observer-independent evaluation. With this approach, there was no statistical significant difference in the PD-L1 expression between responders and non-responders to the therapy with ipilimumab. The evaluation of PD-L1 expression based on mRNA level is feasible. Correlation between PD-L1 expression as assessed by IHC and RT-PCR showed varying levels of concordance depending on the antibody employed. RT-PCR should be further investigated to measure PD-L1 expression, since it is a semi-quantitative method with observer-independent evaluation. With this approach, there was no statistical significant difference in the PD-L1 expression between responders and non-responders to the therapy with ipilimumab.
EVALuna2:15289

Processing and secretion of guanylate binding protein-1 depend on inflammatory caspase activity - Naschberger, Elisabeth; Geissdorfer, Walter; Bogdan, Christian; Tripal, Philipp; Kremmer, Elisabeth; Stürzl, Michael; Britzen-Laurent, Nathalie (Journal of Cellular and Molecular Medicine, 2017)
Human guanylate binding protein-1 (GBP-1) belongs to the family of large GTPases. The expression of GBP-1 is inducible by inflammatory cytokines, and the protein is involved in inflammatory processes and host defence against cellular pathogens. GBP-1 is the first GTPase which was described to be secreted by eukaryotic cells. Here, we report that precipitation of GBP-1 with GMP-agarose from cell culture supernatants co-purified a 47-kD fragment of GBP-1 (p47-GBP-1) in addition to the 67-kD full-length form. MALDI-TOF sequencing revealed that p47-GBP-1 corresponds to the C-terminal helical part of GBP-1 and lacks most of the globular GTPase domain. In silico analyses of protease target sites, together with cleavage experiments in vitro and in vivo, showed that p67-GBP-1 is cleaved by the inflammatory caspases 1 and 5, leading to the formation of p47-GBP-1. Furthermore, the secretion of p47-GBP-1 was found to occur via a non-classical secretion pathway and to be dependent on caspase-1 activity but independent of inflammasome activation. Finally, we showed that p47-GBP-1 represents the predominant form of secreted GBP-1, both in cell culture supernatants and, in vivo, in the cerebrospinal fluid of patients with bacterial meningitis, indicating that it may represent the biologically active form of extracellular GBP-1. These findings confirm the involvement of caspase-1 in non-classical secretion mechanisms and open novel perspectives for the extracellular function of secreted GBP-1.
EVALuna2:7752

Prognostic value of β1 integrin expression in colorectal liver metastases. - Vassos, Nikolaos; Rau, Tilman; Merkel, Susanne; Feiersinger, Fabian; Geppert, Carol-Immanuel; Stürzl, Michael; Hohenberger, Werner; Croner, Roland S. (International Journal of Clinical and Experimental Pathology, 2014)
Integrins are cell surface adhesion molecules (CAM) that regulate via intercellular and cell-matrix signaling various cellular processes including wound healing, cell differentiation, division, growth, migration and metastatic dissemination. Although a correlation between carcinogenesis and changes in integrin expression, especially β1 integrin, has been reported, its role in colorectal liver metastases remains unclear. This study aimed to evaluate the expression of β1 integrin in colorectal liver metastases and to correlate the pattern of expression with clinicopathological features and to investigate the putative role of β1 integrin expression on survival of these patients. Formalin-fixed, paraffin-embedded (FFPE) tumor samples of 81 patients who were operated because of colorectal liver metastases without any neoadjuvant therapy were obtained and stained with hematoxylin and eosin (H & E). An immunohistochemical examination was performed using Dako, Peroxidase/DAB kit and a primary monoclonal β1 integrin (CD29, fibronectin receptor subunit beta; ab3167, Abcam plc). β1 integrin expression was evaluated according to the immunoreactive score of Remmele and Stegner and was related with clinicopathological features of prognostic significance and with disease-free and overall survival as well. Statistical analysis was performed using SPSS version 21.0. β1 integrin was overexpressed in tumor cells in 37 (48%) patients and in stromal cell in 27 (33%) patients. The β1 expression was not statistically correlated with clinicopathological features of the primary tumors but it was statistically correlated (p=0.03) with the histological grading of liver metastases. Kaplan-Meier survival analysis showed that there is a tendency but no statistically significant correlation in disease-free and overall survival. Considering that expression of β1 integrin in colorectal liver metastases remains controversial, specially its relation with survival of patients, we showed that the β1 expression represents a reliable prognostic factor regarding the grading of liver metastases of CRC and our findings imply that β1 integrin expression profiles may have further potential in identifying the stage of colorectal liver metastases and being a marker of prognosis in these patients. UNLABELLED METHODS RESULTS CONCLUSION

Protein tyrosine phosphatase nonreceptor type 2 controls colorectal cancer development - Katkeviciute, Egle; Hering, Larissa; Montalban-Arques, Ana; Busenhart, Philipp; Schwarzfischer, Marlene; Manzini, Roberto; Conde, Javier; Atrott, Kirstin; Lang, Silvia; Rogler, Gerhard; Naschberger, Elisabeth; Schellerer, Vera; et al. (Journal of Clinical Investigation, 2021)
Protein tyrosine phosphatase nonreceptor type 2 (PTPN2) recently emerged as a promising cancer immunotherapy target. We set out to investigate the functional role of PTPN2 in the pathogenesis of human colorectal carcinoma (CRC), as its role in immune-silent solid tumors is poorly understood. We demonstrate that in human CRC, increased PTPN2 expression and activity correlated with disease progression and decreased immune responses in tumor tissues. In particular, stage II and III tumors displayed enhanced PTPN2 protein expression in tumor-infiltrating T cells, and increased PTPN2 levels negatively correlated with expression of PD-1, CTLA4, STAT1, and granzyme A. In vivo, T cell- and DC-specific PTPN2 deletion reduced tumor burden in several CRC models by promoting CD44+ effector/memory T cells, as well as CD8+ T cell infiltration and cytotoxicity in the tumor. In direct relevance to CRC treatment, T cell-specific PTPN2 deletion potentiated anti-PD-1 efficacy and induced antitumor memory formation upon tumor rechallenge in vivo. Our data suggest a role for PTPN2 in suppressing antitumor immunity and promoting tumor development in patients with CRC. Our in vivo results identify PTPN2 as a key player in controlling the immunogenicity of CRC, with the strong potential to be exploited for cancer immunotherapy.
CRIS-Team Scopus Importer:2021-01-15

PU.1 controls fibroblast polarization and tissue fibrosis - Wohlfahrt, Thomas; Rauber, Simon; Uebe, Steffen; Luber, Markus; Soare, Alina; Ekici, Arif Bülent; Weber, Stefanie; Matei, Alexandru-Emil; Chen, Chih-Wei; Maier, Christiane; Karouzakis, Emmanuel; Kiener, Hans P.; et al. (Nature, 2019)
Fibroblasts are polymorphic cells with pleiotropic roles in organ morphogenesis, tissue homeostasis and immune responses. In fibrotic diseases, fibroblasts synthesize abundant amounts of extracellular matrix, which induces scarring and organ failure. By contrast, a hallmark feature of fibroblasts in arthritis is degradation of the extracellular matrix because of the release of metalloproteinases and degrading enzymes, and subsequent tissue destruction. The mechanisms that drive these functionally opposing pro-fibrotic and pro-inflammatory phenotypes of fibroblasts remain unknown. Here we identify the transcription factor PU.1 as an essential regulator of the pro-fibrotic gene expression program. The interplay between transcriptional and post-transcriptional mechanisms that normally control the expression of PU.1 expression is perturbed in various fibrotic diseases, resulting in the upregulation of PU.1, induction of fibrosis-associated gene sets and a phenotypic switch in extracellular matrix-producing pro-fibrotic fibroblasts. By contrast, pharmacological and genetic inactivation of PU.1 disrupts the fibrotic network and enables reprogramming of fibrotic fibroblasts into resting fibroblasts, leading to regression of fibrosis in several organs.
EVALuna2:35476

Quantitative proteome profiling of lymph node-positive vs. -negative colorectal carcinomas pinpoints MX1 as a marker for lymph node metastasis - Croner, Roland S.; Stürzl, Michael; Rau, Tilman; Metodieva, Gergana; Geppert, Carol-Immanuel; Naschberger, Elisabeth; Lausen, Berthold; Metodiev, Metodi V. (International Journal of Cancer, 2014)
We used high-resolution mass spectrometry to measure the abundance of more than 9,000 proteins in 19 individually dissected colorectal tumors representing lymph node metastatic (n = 10) and nonmetastatic (n = 9) phenotypes. Statistical analysis identified MX1 and several other proteins as overexpressed in lymph node-positive tumors. MX1, IGF1-R and IRF2BP1 showed significantly different expression in immunohistochemical validation (Wilcoxon test p = 0.007 for IGF1-R, p = 0.04 for IRF2BP1 and p = 0.02 for MX1 at the invasion front) in the validation cohort. Knockout of MX1 by siRNA in cell cultures and wound healing assays provided additional evidence for the involvement of this protein in tumor invasion. The collection of identified and quantified proteins to our knowledge is the largest tumor proteome dataset available at the present. The identified proteins can give insights into the mechanisms of lymphatic metastasis in colorectal carcinoma and may act as prognostic markers and therapeutic targets after further prospective validation.
EVALuna2:6585

Rapid qPCR-based quantitative immune cell phenotyping in mouse tissues - Huang, Jinghao; Demmler, Richard; Mohamed Abdou, Mariam; Thoma, Oana-Maria; Weigmann, Benno; Waldner, Maximilian; Stürzl, Michael; Naschberger, Elisabeth (Journal of Investigative Medicine, 2024)
The immune microenvironment plays an important role in the regulation of diseases. The characterization of the cellular composition of immune cell infiltrates in diseases and respective models is a major task in pathogenesis research and diagnostics. For the assessment of immune cell populations in tissues, fluorescence-activated cell sorting (FACS) or immunohistochemistry (IHC) are the two most common techniques presently applied, but they are cost intensive, laborious, and sometimes limited by the availability of suitable antibodies. Complementary rapid qPCR-based approaches exist for the human situation but are lacking for experimental mouse models. Accordingly, we developed a robust, rapid RT-qPCR-based approach to determine and quantify the abundance of prominent immune cell populations such as T cells, helper T (Th) cells, cytotoxic T cells, Th1 cells, B cells, and macrophages in mouse tissues. The results were independently validated by the gold standards IHC and FACS in corresponding tissues and showed high concordance.
CRIS-Team Scopus Importer:2023-12-22
Keywords: FACS; IHC; immune cell phenotyping; mouse tissue; RT-qPCR

Reactivation and persistence of human herpesvirus-8 infection in B cells and monocytes by Th-1 cytokines increased in Kaposi's sarcoma. - Monini, Paolo; Colombini, Sandra; Stürzl, Michael; Goletti, Delia; Cafaro, Aurelio; Sgadari, Cecilia; Buttò, Stefano; Franco, Marina; Leone, Patrizia; Fais, Stefano; Leone, Pasqualina; Melucci-Vigo, Gianna; et al. (Blood, 1999)
Patients with Kaposi's sarcoma (KS) have a human herpesvirus-8 (HHV-8) load higher than patients without KS and present a CD8(+) T-cell activation with production of Th1-type cytokines both in tissues and peripheral blood mononuclear cells (PBMC). Because in tissues of KS patients detection of inflammatory cytokines (IC) can precede detection of HHV-8 DNA and because signs of immunoactivation and/or dysregulation can precede KS development, we investigated the effect of IC on HHV-8 infection. To achieve this goal, PBMC and purified cell populations from 45 patients with KS and 45 patients at risk of KS were analyzed for HHV-8 DNA and/or gene expression and for cell survival, growth, and phenotype before or after culture with or without the IC increased in KS. The results indicate that PBMC that are polymerase chain reaction (PCR)-positive at day 0 generally loose the virus upon culture. However, the presence of IC maintains HHV-8 DNA load in cultured cells. In addition, IC increase viral load to detectable levels in PBMC from serologically positive patients that were PCR-negative before culture. gamma Interferon is sufficient for these effects, whereas tumor necrosis factor and interleukin-6 have little or no activity. The increase of HHV-8 DNA by IC is observed after short-term (7 days) or long-term (28 days) culture of the cells and occurs in one or both of the two circulating cell types that are infected in vivo: B cells and monocytes. In both cases it is associated with lytic gene expression, suggesting that virus reactivation is one of the most likely mechanisms for the effect of IC on virus load. However, IC have also effects on the cells target of HHV-8 infection, because they increase B-cell survival and induce the growth and differentiation of monocytes into KS-like spindle cells with markers of endothelial macrophages. Because cells with markers of endothelial macrophages are present in blood and lesions from KS patients and are infected by HHV-8, these data may explain the high HHV-8 load associated with KS development and suggest that infected monocytes may carry the virus to tissues, transmit the infection, or differentiate in loco in spindle cells with endothelial macrophage markers.

Reactivation and role of HHV-8 in Kaposi's sarcoma initiation. - Ensoli, Barbara; Stürzl, Michael; Monini, Paolo (Advances in Cancer Research, 2001)
Kaposi's sarcoma (KS) is an angioproliferative disease occurring in several clinical-epidemio-logic forms but all associated with infection by the human herpesvirus-8 (HHV-8). At least in early stages, KS is a reactive disease associated with a state of immune dysregulation characterized by CD8+ T-cell activation and production of Th1-type inflammatory cytokines (IC) that precedes lesion development. In fact, evidence indicates that IC can trigger lesion formation by inducing the activation of endothelial cells that leads to adhesion and tissue extravasation of lymphomonocytes, spindle cell formation, and angiogenesis, and HHV-8 reactivation that, in turn, leads to virus spread to all circulating cell types and virus dissemination into tissues. Due to virus escape mechanisms and deficient immune responses toward HHV-8, virus reactivation and spread are not controlled by the immune system but induce immune responses that may paradoxically exacerbate the reactive process. The virus is recruited into "activated" tissue sites where it finds an optimal environment for growth. In fact, viral load is very low in early lesions, whereas almost all spindle cells are infected in late-stage lesions. Although early KS is a reactive process of polyclonal nature that can regress, in time and in the presence of immunodeficiency, it can progress to a true sarcoma. This is likely due to the long-lasting expression of HHV-8 latency genes in spindle cells associated with the deregulated expression of oncogenes and oncosuppressor genes and, for AIDS-KS, with the effects of the HIV-1 Tat protein.

Reduced cytotoxicity by mutation of lysine 590 of Pseudomonas exotoxin can be restored in an optimized, lysine-free immunotoxin. - Ammon, Anna-Maria; Mellenthin, Lisa; Emmerich, C.; Naschberger, Elisabeth; Stürzl, Michael; Mackensen, Andreas; Müller, Fabian (Immunotherapy Advances, 2022)
Immunotoxins, which are fusion proteins of an antibody fragment and a fragment of a bacterial or a plant toxin, induce apoptosis in target cells by inhibition of protein synthesis. ADP-ribosylating toxins often have few lysine residues in their catalytic domain. As they are the target for ubiquitination, the low number of lysines possibly prevents ubiquitin-dependent degradation of the toxin in the cytosol. To reduce this potential degradation, we aimed to generate a lysine-free (noK), Pseudomonas exotoxin (PE)-based immunotoxin. The new generation 24 kDa PE, which lacks all but the furin-cleavage site of domain II, was mutated at lysine 590 (K590) and at K606 in a CD22-targeting immunotoxin and activity was determined against various B cell malignancies in vitro and in vivo. On average, K590 mutated to arginine (R) reduced cytotoxicity by 1.3-fold and K606R enhanced cytotoxicity by 1.3-fold compared to wild type (wt). Mutating K590 to histidine or deleting K590 did not prevent this loss in cytotoxicity. Neither stability nor internalization rate of K590R could explain reduced cytotoxicity. These results highlight the relevance of lysine 590 for PE intoxication. In line with in vitro results, the K606R mutant was more than 1.8-fold more active than the other variants in vivo suggesting that this single mutation may be beneficial when targeting CD22-positive malignancies. Finally, reduced cytotoxicity by K590R was compensated for by K606R and the resulting lysine-free variant achieved wt-like activity in vitro and in vivo. Thus, PE24-noK may represent a promising candidate for down-stream applications that would interfere with lysines.
EVALuna2:505954

Regression of apoptosis-resistant colorectal tumors by induction of necroptosis in mice - He, Gui-Wei; Günther, Claudia; Thonn, Veronika; Yu, Yu-Qiang; Martini, Eva; Buchen, Barbara; Neurath, Markus; Stürzl, Michael; Becker, Christoph (Journal of Experimental Medicine, 2017)
Cancer cells often acquire capabilities to evade cell death induced by current chemotherapeutic treatment approaches. Caspase-8, a central initiator of death receptor-mediated apoptosis, for example, is frequently inactivated in human cancers via multiple mechanisms such as mutation. Here, we show an approach to overcome cell death resistance in caspase-8-deficient colorectal cancer (CRC) by induction of necroptosis. In both a hereditary and a xenograft mouse model of caspase-8-deficient CRC, second mitochondria-derived activator of caspase (SMAC) mimetic treatment induced massive cell death and led to regression of tumors. We further demonstrate that receptor-interacting protein kinase 3 (RIP3), which is highly expressed in mouse models of CRC and in a subset of human CRC cell lines, is the deciding factor of cancer cell susceptibility to SMAC mimetic-induced necroptosis. Thus, our data implicate that it may be worthwhile to selectively evaluate the efficacy of SMAC mimetic treatment in CRC patients with caspase-8 deficiency in clinical trials for the development of more effective personalized therapy.
EVALuna2:15307

Reverse transfected cell microarrays in infectious disease research - Konrad, Andreas; Jochmann, Ramona; Kühn, Elisabeth; Naschberger, Elisabeth; Chudasama, Priya; Stürzl, Michael (Methods in Molecular Biology, 2011)
Several human pathogenic viruses encode large genomes with often more than 100 genes. Viral pathogenicity is determined by carefully orchestrated co-operative activities of several different viral genes which trigger the phenotypic functions of the infected cells. Systematic analyses of these complex interactions require high-throughput transfection technology. Here we have provided a laboratory manual for the reverse transfected cell microarray (RTCM; alternative name: cell chip) as a high-throughput transfection procedure, which has been successfully applied for the systematic analyses of single and combination effects of genes encoded by the human herpesvirus-8 on the NF-kappaB signal transduction pathway. In order to quantitatively determine the effects of viral genes in transfected cells, protocols for the use of GFP as an indicator gene and for indirect immunofluorescence staining of cellular target proteins have been included. RTCM provides a useful methodological approach to investigate systematically combination effects of viral genes on cellular functions.
Created from Fastlane, Scopus look-up
Keywords: Cell chip; High-throughput; Human herpesvirus-8; KSHV; Microarray; Transfection

Role of guanylate binding protein-1 in vascular defects associated with chronic inflammatory diseases - Hammon, Matthias; Herrmann, Martin; Bleiziffer, Oliver; Pryymachuk, Galyna; Andreoli, Laura; Munoz, Luis Enrique; Amann, Kerstin Ute; Mondini, Michele; Gariglio, Marisa; Airo, Paolo; Schellerer, Vera; Hatzopoulos, Antonis K.; et al. (Journal of Cellular and Molecular Medicine, 2011)
Rheumatic autoimmune disorders are characterized by a sustained pro-inflammatory microenvironment associated with impaired function of endothelial progenitor cells (EPC) and concomitant vascular defects. Guanylate binding protein-1 (GBP-1) is a marker and intracellular regulator of the inhibition of proliferation, migration and invasion of endothelial cells induced by several pro-inflammatory cytokines. In addition, GBP-1 is actively secreted by endothelial cells. In this study, significantly increased levels of GBP-1 were detected in the sera of patients with chronic inflammatory disorders. Accordingly we investigated the function of GBP-1 in EPC. Interestingly, stable expression of GBP-1 in T17b EPC induced premature differentiation of these cells, as indicated by a robust up-regulation of both Flk-1 and von Willebrand factor expression. In addition, GBP-1 inhibited the proliferation and migration of EPC in vitro. We confirmed that GBP-1 inhibited vessel-directed migration of EPC at the tissue level using the rat arterio-venous loop model as a novel quantitative in vivo migration assay. Overall, our findings indicate that GBP-1 contributes to vascular dysfunction in chronic inflammatory diseases by inhibiting EPC angiogenic activity via the induction of premature EPC differentiation. © 2011 The Authors Journal of Cellular and Molecular Medicine © 2011 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up
Keywords: Endothelial progenitor cells; Guanylate binding protein-1; Inflammation; Rheumatic autoimmune disorders; Rheumatoid arthritis; Systemic lupus erythematosus; Systemic sclerosis

Role of IFN-gamma-activation of distinct tumor and stromal cell populations in colorectal carcinoma pathogenesis - Britzen-Laurent, Nathalie; Guo, Wei; Langer, Victoria; Khoziainova, Svetlana; Weisenburger, Thomas; Winkler, Thomas; Straube, Julia; Waldner, Maximilian; Becker, Christoph; Naschberger, Elisabeth; Skottke, Lisa; Tripal, Philipp; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22

"Run-off" synthesis and application of defined single-stranded DNA hybridization probes. - Stürzl, Michael; Roth, Willy Kurt (Analytical Biochemistry, 1990)
A simple and efficient method for synthesizing radioactively labeled single-stranded DNA hybridization probes with Thermus aquaticus (Taq) DNA polymerase is described. This is done in a "run-off" polymerization with repeated cycles of denaturation, annealing, and extension. It leads to high yields of a single-stranded DNA of defined length (up to 5000 nt), which is labeled to a high specific activity (1.3 x 10(8) cpm/micrograms DNA). These hybridization probes are equally sensitive as nick-translated DNA probes, but strand specific. This was tested by slot blot hybridization with in vitro-transcribed target RNAs and by Northern blotting. The use of single-stranded DNA hybridization probes combines the benefits of DNA stability and single-strand RNA probes.

Serum concentrations of fibroblast growth factor 2 are increased in HIV type 1-infected patients and inversely related to survival probability. - Ascherl, Gudrun; Sgadari, Cecilia; Bugarini, Roberto; Bogner, Johannes; Schatz, Octavian; Ensoli, Barbara; Stürzl, Michael (Aids Research and Human Retroviruses, 2001)
HIV-1-infected patients develop a generalized vasculopathy that is clinically most evident as Kaposi's sarcoma (KS), a multifocally appearing endothelial cell-derived tumor. Fibroblast growth factor 2 (FGF-2) is a potent autocrine and paracrine mitogen of endothelial cells and has been implicated in the cell proliferation and angiogenesis observed in KS. Here we determined by ELISA the FGF-2 serum concentrations in different clinical groups of HIV-1-infected patients. AIDS-KS patients (n = 53) and HIV-1-infected patients without KS (n = 39) revealed significantly increased FGF-2 serum concentrations (median, 4.5 and 4.6 pg/ml, respectively), as compared with the healthy control group (n = 22; median, 2.2 pg/ml; p < 0.01). FGF-2 concentrations were highest in untreated HIV-1-infected patients (median, 8.6 pg/ml) and were significantly decreased in patients undergoing antiretroviral therapy (AZT-median, 4.5 pg/ml; HAART-median, 2.5 pg/ml; p < 0.01). In addition, FGF-2 serum concentrations above 5.2 pg/ml were associated with a statistically significant higher risk of death in HIV-1-infected patients. Multivariate analysis showed that this effect is independent of CD4 levels, localization of KS (cutaneous or visceral), AIDS-defining opportunistic diseases, and therapy. Circulating FGF-2 may contribute to AIDS-associated vasculopathy and may be a sensitive and easily accessible surrogate marker to determine the survival time of HIV-1-infected patients and the efficacy of antiretroviral therapy.

SMYD2 targets RIPK1 and restricts TNF-induced apoptosis and necroptosis to support colon tumor growth - Yu, Yidong; Thonn, Veronika; Patankar, Jay; Thoma, Oana-Maria; Waldner, Maximilian; Zielinska, Marta; Bao, Lili; Gonzalez Acera, Miguel; Wallmueller, Stefan; Engel, Felix; Stürzl, Michael; Neurath, Markus; et al. (Cell Death & Disease, 2022)
SMYD2 is a histone methyltransferase, which methylates both histone H3K4 as well as a number of non-histone proteins. Dysregulation of SMYD2 has been associated with several diseases including cancer. In the present study, we investigated whether and how SMYD2 might contribute to colorectal cancer. Increased expression levels of SMYD2 were detected in human and murine colon tumor tissues compared to tumor-free tissues. SMYD2 deficiency in colonic tumor cells strongly decreased tumor growth in two independent experimental cancer models. On a molecular level, SMYD2 deficiency sensitized colonic tumor cells to TNF-induced apoptosis and necroptosis without affecting cell proliferation. Moreover, we found that SMYD2 targeted RIPK1 and inhibited the phosphorylation of RIPK1. Finally, in a translational approach, pharmacological inhibition of SMYD2 attenuated colonic tumor growth. Collectively, our data show that SMYD2 is crucial for colon tumor growth and inhibits TNF-induced apoptosis and necroptosis.
CRIS-Team WoS Importer:2022-01-21

Soluble intercellular adhesion molecule-1 is a prognostic marker in colorectal carcinoma - Schellerer, Vera; Langheinrich, Melanie C.; Zver, Veronika; Grützmann, Robert; Stürzl, Michael; Gefeller, Olaf; Naschberger, Elisabeth; Merkel, Susanne (International Journal of Colorectal Disease, 2019)
PurposeSerological tumor markers are routinely used to monitor tumor onset and progression. In colorectal carcinoma (CRC), the carcinoembryonic antigen (CEA) is roughly elevated in 50% of patients at initial diagnosis. Soluble ICAM-1 (sICAM-1) is elevated in different cancers. The aim of this study was to evaluate the prognostic relevance of sICAM-1 combined with CEA in patients with CRC.MethodsIn blood samples of 297 CRC patients, sICAM-1 was determined by ELISA and CEA by microparticle enzyme immunoassay the day before oncologic resection. Separation in patients with sICAM-1(high) and sICAM-1(low) was performed by minimum p value approach; separation in CEA normal and elevated was performed according to the established diagnostic cutoff. Clinical data were obtained from the prospective collected data from the Erlangen Registry for Colorectal Carcinomas.ResultsCancer-related 5-year survival rate of patients with sICAM-1(low) (<290ng/ml, n=208) was significantly increased (83.4%) as compared to that of patients with sICAM-1(high) (290ng/ml, n=89) (66.2%; p<0.001). Patients with normal CEA concentrations (n=199; 90.8%) showed a significantly (p<0.001) improved cancer-related 5-year survival rate compared to patients with elevated CEA concentrations (n=98; 52.1%). Moreover, high sICAM-1 was an independent risk factor (hazard ratio 1.6) in multivariate analysis. Of note, increased sICAM-1 levels, either within normal or within elevated CEA, allowed to identify high-risk subgroups, both for overall (p<0.001) and cancer-related survival (p<0.001).ConclusionApplication of a novel risk score combining CEA/sICAM-1 serum concentrations allows the identification of high-risk groups for poor survival in CRC patients.
CRIS-Team WoS Importer:2019-02-21

SPARCL1 is an angiocrine inhibitor of tumorigenesis in colorectal carcinoma - Tenkerian, Clara; Regensburger, Daniela; Langer, Victoria; Klingler, Anika; Borau, Anne; Sticht, Heinrich; Ramming, Andreas; Wohlfahrt, Thomas; Schmid, Benjamin; Meniel, Valerie; Grützmann, Robert; Britzen-Laurent, Nathalie; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-15

Spatial Single Cell Profiling Using Imaging Mass Cytometry: Inflammatory Versus Penetrating Crohn's Disease - Lehmann, Malte; Weixler, Benjamin; Elezkurtaj, Sefer; Loddenkemper, Christopher; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; et al. (Journal of Crohns & Colitis, 2024)
Background and Aims: Fistula formation is a major complication in Crohn's disease [CD] and the role of the immune cell compartment remains to be elucidated. Thus, we compared the immune cell compartment of CD fistula to inflammatory CD colitis using imaging mass cytometry [IMC] and immunofluorescence. Methods: A 36-marker panel including structural, functional, and lineage markers for use in IMC was established. This panel was applied to analyse paraffin-embedded CD fistula tract [n = 11], CD colitis [n = 10], and colon samples from non-inflamed controls [n = 12]. Computational methods for cell segmentation, dimensionality reduction, and cell type clustering were used to define cell populations for cell frequency, marker distribution, and spatial neighbourhood analysis. Multiplex immunofluorescence was used for higher resolution spatial analysis. Results: Analysis of cell frequencies in CD fistulas compared to CD colitis and control colonic samples revealed a significant increase in neutrophils, effector cytotoxic T cells, and inflammatory macrophages in CD fistula samples, whereas regulatory T cells were decreased. Neutrophils in CD fistula expressed significantly more matrix metalloproteinase 9 [MMP9], correlating with extracellular matrix remodelling. Neighbourhood analysis revealed a strong association between MMP9+ neutrophils and effector cytotoxic T cells in both CD fistulas and colitis. Conclusions: This study presents the first highly multiplexed single cell analysis of the immune cell compartment of CD fistulas and their spatial context. It links immune cell dynamics, particularly MMP9+ neutrophils, to extracellular matrix remodelling in CD fistulas, offering insights into the complex network of cellular interactions and potential therapeutic targets for CD complications.
CRIS-Team Scopus Importer:2024-09-13
Keywords: fistula; imaging mass cytometry; Penetrating Crohn's disease

Species-, organ- and cell-type-dependent expression of SPARCL1 in human and mouse tissues. - Klingler, Anika; Regensburger, Daniela; Tenkerian, Clara; Britzen-Laurent, Nathalie; Hartmann, Arndt; Stürzl, Michael; Naschberger, Elisabeth (PLoS ONE, 2020)
SPARCL1 is a matricellular protein with anti-adhesive, anti-proliferative and anti-tumorigenic functions and is frequently downregulated in tumors such as colorectal carcinoma or non-small cell lung cancer. Studies have identified SPARCL1 as an angiocrine tumor suppressor secreted by tumor vessel endothelial cells, thereby exerting inhibitory activity on angiogenesis and tumor growth, in colorectal carcinoma. It is unknown whether SPARCL1 may exert these homeostatic functions in all organs and in other species. Therefore, SPARCL1 expression was comparatively analysed between humans and mice in a systematic manner. Murine Sparcl1 (mSparcl1) is most strongly expressed in the lung; expressed at an intermediate level in most organs, including the large intestine; and absent in the liver. In human tissues, SPARCL1 (hSPARCL1) was detected in all organs, with the strongest expression in the stomach, large intestine and lung, mostly consistent with the murine expression pattern. A striking difference between human and murine tissues was the absence of mSparcl1 expression in murine livers, while human livers showed moderate expression. Furthermore, mSparcl1 was predominantly associated with mural cells, whereas hSPARCL1 was detected in both mural and endothelial cells. Human SPARCL1 expression was downregulated in different carcinomas, including lung and colon cancers. In conclusion, this study revealed species-, organ- and cell-type-dependent expression of SPARCL1, suggesting that its function may not be similar between humans and mice.

Structural proteins of Kaposi's sarcoma-associated herpesvirus antagonize p53-mediated apoptosis - Chudasama, Priya; Konrad, A.; Jochmann, R.; Lausen, Berthold; Holz, Patrick; Naschberger, Elisabeth; Neipel, Frank; Britzen-Laurent, Nathalie; Stürzl, Michael (Oncogene, 2015)
The tumor suppressor p53 is a central regulatory molecule of apoptosis and is commonly mutated in tumors. Kaposi's sarcoma-associated herpesvirus (KSHV)-related malignancies express wild-type p53. Accordingly, KSHV encodes proteins that counteract the cell death-inducing effects of p53. Here, the effects of all KSHV genes on the p53 signaling pathway were systematically analyzed using the reversely transfected cell microarray technology. With this approach we detected eight KSHV-encoded genes with potent p53 inhibiting activity in addition to the previously described inhibitory effects of KSHV genes ORF50, K10 and K10.5. Interestingly, the three most potent newly identified inhibitors were KSHV structural proteins, namely ORF22 (glycoprotein H), ORF25 (major capsid protein) and ORF64 (tegument protein). Validation of these results with a classical transfection approach showed that these proteins inhibited p53 signaling in a dose-dependent manner and that this effect could be reversed by small interfering RNA-mediated knockdown of the respective viral gene. All three genes inhibited p53-mediated apoptosis in response to Nutlin-3 treatment in non-infected and KSHV-infected cells. Addressing putative mechanisms, we could show that these proteins could also inhibit the transactivation of the promoters of apoptotic mediators of p53 such as BAX and PIG3. Altogether, we demonstrate for the first time that structural proteins of KSHV can counteract p53-induced apoptosis. These proteins are expressed in the late lytic phase of the viral life cycle and are incorporated into the KSHV virion. Accordingly, these genes may inhibit cell death in the productive and in the early entrance phase of KSHV infection.
EVALuna2:8221

T17b murine embryonal endothelial progenitor cells can be induced towards both proliferation and differentiation in a fibrin matrix - Bleiziffer, Oliver; Horch, Raymund E.; Hammon, Matthias; Arkudas, Andreas; Naschberger, Elisabeth; Rath, Subha; Pryymachuk, Galyna; Beier, Justus; Hatzopoulos, Antonis K.; Stürzl, Michael; Kneser, Ulrich (Journal of Cellular and Molecular Medicine, 2009)
Endothelial progenitor cells (EPC) may enhance blood vessel formation in a variety of clinical settings such as ischaemia and tumour angiogenesis as well as in tissue-engineered matrices. In the present study, we cultured a murine endothelial progenitor cell line, T17b, in vitro in cell culture as well as in an FDA-approved fibrin matrix and investigated cell proliferation, differentiation and secretion patterns of the angiogenic growth factor VEGF under hypoxia and differentiation. We show that T17b EPC remain viable for at least 8 days in the fibrin matrix where they proliferate and form clusters including lumen-like structures. Proliferation in fibrin clots overlayed with basal medium (BM) was confirmed morphologically and immunohistochemically by positive Ki67 staining, indicating mitotic activity. Significant cell proliferation and Ki-67 expression were absent when cells were incubated with dibutyryl-cAMP and retinoic acid (RA). Incubation with dibutyryl-cAMP and RA stimulated the expression of the EPC differentiation markers von Willebrand Factor (vWF) and VEGF receptor 2 (VEGFR-2), indicating successful differentiation in the fibrin clot. EPC differentiation induced by dibutyryl-cAMP and RA was confirmed in 2-D chamber slide cultures by positive vWF immunostaining, which was absent in BM controls. EPC chamber slides also displayed positive vWF staining when exposed to hypoxia under BM conditions, indicating EPC activation and differentiation could also be induced by hypoxia. Taken together, T17b EPC secrete increased levels of VEGF when submitted to either hypoxia or differentiation and can be differentiated into mature endothelial cells not only in cell and matrigel cultures but also in a fibrin matrix that is FDA approved for clinical application. © 2009 Foundation for Cellular and Molecular Medicine/Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Embryonal endothelial progenitor cells; Tissue engineering

Tetramerization of human guanylate-binding protein 1 is mediated by coiled-coil formation of the C-terminal α-helices - Syguda, Adrian; Bauer, Michael; Benscheid, Utz; Ostler, Nicole; Naschberger, Elisabeth; Ince, Semra; Stürzl, Michael; Herrmann, Christian (Febs Journal, 2012)
The human guanylate-binding protein 1 (hGBP1) is a large GTP-binding protein belonging to the dynamin family, a common feature of which is nucleotide-dependent assembly to homotypic oligomers. Assembly leads to stimulation of GTPase activity, which, in the case of dynamin, is responsible for scission of vesicles from membranes. By yeast two-hybrid and biochemical experiments we addressed intermolecular interactions between all subdomains of hGBP1 and identified the C-terminal subdomain, α12/13, as a new interaction site for self-assembly. α12/13 represents a stable subdomain of hGBP1, as shown by CD spectroscopy. In addition to contacts between GTPase domains leading to dimer formation, the interaction between two α12/13 subdomains, in the course of GTP hydrolysis, results in tetramer formation of the protein. With the help of CD spectroscopy we showed coiled-coil formation of two α12/13 subdomains and concentration-dependent measurements allow estimating a value for the dissociation constant of 7.3 μm. We suggest GTP hydrolysis-driven release of the α12/13 subdomain, making it available for coiled-coil formation. Furthermore, we can demonstrate the biological relevance of hGBP1 tetramer formation in living cells by chemical cross-link experiments. © 2012 FEBS.
Created from Fastlane, Scopus look-up
Keywords: aluminum fluoride; dynamin; protein dimer; protein-protein association; self-assembly

The clinical value of von Willebrand factor in colorectal carcinomas. - Schellerer, Vera; Müller-Bergh, Larissa; Merkel, Susanne; Zimmermann, Robert; Weiss, Dominik R.; Schlabrakowski, Anne; Naschberger, Elisabeth; Stürzl, Michael; Hohenberger, Werner; Croner, Roland S. (American Journal of Translational Research, 2011)
To identify the value of von Willebrand factor (vWF) as a clinical marker in colorectal carcinoma (CRC). Plasma levels of vWF were measured in 79 patients with UICC Stage I-IV CRC at time of operation and correlated with TNM categories, levels of the carcinoembryonic antigen (CEA), blood groups (BG) and 19 controls (CO). CO included cancer-free patients without bacterial or viral infections. For tissue analysis paraffin embedded tumour and mucosa sections of operation specimens were stained immunohistochemically for vWF and compared to vWF plasma levels as well as to TNM categories. VWF plasma levels in CRC patients were significantly dependent on blood groups (p=0.012) and elevated compared to the normal ranges as well as to controls (BG 0: p=0.668, BG A/AB/B: p=0.020). CRC-Patients over 60 years of age presented with significantly higher vWF levels than patients below 60 years (BG 0: p=0.005; BG A/AB/B: p=0.035). There was no correlation of vWF plasma levels and UICC stages in CRC. Patients with elevated vWF plasma levels also presented with elevated CEA levels, but significance was missing (p=0.080). VWF concentration within the tumour tissue was independent of concentration within normal mucosa, blood groups, histopathological characteristics and did not correlate with plasma vWF levels. VWF plasma levels are elevated in CRC patients, but not in a stage dependent manner. Besides the tumour at least blood groups and age mainly influence plasma vWF levels. In our opinion vWF as a routinely used clinical marker in CRC cannot be recommended. BACKGROUND METHODS RESULTS CONCLUSION

The contribution of systems biology and reverse genetics to the understanding of Kaposi's sarcoma-associated herpesvirus pathogenesis in endothelial cells. - Stürzl, Michael; Konrad, Andreas; Alkharsah, Khaled R.; Jochmann, Ramona; Thurau, Mathias; Marquardt, Gaby; Schulz, Thomas F. (Thrombosis and Haemostasis, 2009)
Kaposi's sarcoma-associated herpesvirus (KSHV)/human herpesvirus-8 is the causative agent of the endothelial cell-derived tumour Kaposi's sarcoma. Herpesviruses possess large complex genomes which provide many options to regulate cellular physiology during the viral life cycle and in the course of tumourigenicity. Novel techniques of systems biology and reverse genetics are increasingly applied to dissect the complex interaction of KSHV with endothelial cells. This review will outline novel results and pitfalls of these technologies in the elucidation of KSHV pathogenicity.

The Ebola virus glycoprotein and HIV-1 Vpu employ different strategies to counteract the antiviral factor tetherin. - Kühl, Annika; Banning, Carina; Marzi, Andrea; Votteler, Jörg; Steffen, Imke; Bertram, Stephanie; Glowacka, Ilona; Konrad, Andreas; Stürzl, Michael; Guo, Ju-Tao; Schubert, Ulrich; Feldmann, Heinz; et al. (Journal of Infectious Diseases, 2011)
The antiviral protein tetherin/BST2/CD317/HM1.24 restricts cellular egress of human immunodeficiency virus (HIV) and of particles mimicking the Ebola virus (EBOV), a hemorrhagic fever virus. The HIV-1 viral protein U (Vpu) and the EBOV-glycoprotein (EBOV-GP) both inhibit tetherin. Here, we compared tetherin counteraction by EBOV-GP and Vpu. We found that EBOV-GP but not Vpu counteracted tetherin from different primate species, indicating that EBOV-GP and Vpu target tetherin differentially. Tetherin interacted with the GP2 subunit of EBOV-GP, which might encode the determinants for tetherin counteraction. Vpu reduced cell surface expression of tetherin while EBOV-GP did not, suggesting that both proteins employ different mechanisms to counteract tetherin. Finally, Marburg virus (MARV)-GP also inhibited tetherin and downregulated tetherin in a cell type-dependent fashion, indicating that tetherin antagonism depends on the cellular source of tetherin. Collectively, our results indicate that EBOV-GP counteracts tetherin by a novel mechanism and that tetherin inhibition is conserved between EBOV-GP and MARV-GP.

The ephrin receptor tyrosine kinase A2 is a cellular receptor for Kaposi's sarcoma-associated herpesvirus - Hahn, Alexander; Kaufmann, Johanna K.; Wies, Effi; Naschberger, Elisabeth; Panteleev-Ivlev, Julia; Schmidt, Katharina; Holzer, Angela; Schmidt, Martin; Chen, Jin; Koenig, Simone; Enßer, Armin; Myoung, Jinjong; et al. (Nature Medicine, 2012)
Kaposi's sarcoma-associated herpesvirus (KSHV) is the causative agent of Kaposi's sarcoma, a highly vascularized tumor originating from lymphatic endothelial cells, and of at least two different B cell malignancies. A dimeric complex formed by the envelope glycoproteins H and L (gH-gL) is required for entry of herpesviruses into host cells. We show that the ephrin receptor tyrosine kinase A2 (EphA2) is a cellular receptor for KSHV gH-gL. EphA2 co-precipitated with both gH-gL and KSHV virions. Infection of human epithelial cells with a GFP-expressing recombinant KSHV strain, as measured by FACS analysis, was increased upon overexpression of EphA2. Antibodies against EphA2 and siRNAs directed against EphA2 inhibited infection of endothelial cells. Pretreatment of KSHV with soluble EphA2 resulted in inhibition of KSHV infection by up to 90%. This marked reduction of KSHV infection was seen with all the different epithelial and endothelial cells used in this study. Similarly, pretreating epithelial or endothelial cells with the soluble EphA2 ligand ephrinA4 impaired KSHV infection. Deletion of the gene encoding EphA2 essentially abolished KSHV infection of mouse endothelial cells. Binding of gH-gL to EphA2 triggered EphA2 phosphorylation and endocytosis, a major pathway of KSHV entry. Quantitative RT-PCR and in situ histochemistry revealed a close correlation between KSHV infection and EphA2 expression both in cultured cells derived from human Kaposi's sarcoma lesions or unaffected human lymphatic endothelium, and in situ in Kaposi's sarcoma specimens, respectively. Taken together, our results identify EphA2, a tyrosine kinase with known functions in neovascularization and oncogenesis, as an entry receptor for KSHV. © 2012 Nature America, Inc. All rights reserved.
Created from Fastlane, Scopus look-up

The guanylate binding protein-1 GTPase controls the invasive and angiogenic capability of endothelial cells through inhibition of MMP-1 expression - Naschberger, Elisabeth; Stürzl, Michael; et al. (EMBO Journal, 2003)
Expression of the large GTPase guanylate binding protein-1 (GBP-1) is induced by inflammatory cytokines (ICs) in endothelial cells (ECs), and the helical domain of the molecule mediates the repression of EC proliferation by ICs. Here we show that the expression of GBP-1 and of the matrix metalloproteinase-1 (MMP-1) are inversely related in vitro and in vivo, and that GBP-1 selectively inhibits the expression of MMP-1 in ECs, but not the expression of other proteases. The GTPase activity of GBP-1 was necessary for this effect, which inhibited invasiveness and tube-forming capability of ECs in three-dimensional collagen-I matrices. A GTPase-deficient mutant (D184N-GBP-1) operated as a transdominant inhibitor of wild-type GBP-1 and rescued MMP-1 expression in the presence of ICs. Expression of D184N-GBP-1, as well as paracrine supplementation of MMP-1, restored the tube-forming capability of ECs in the presence of wild-type GBP-1. The latter finding indicated that the inhibition of capillary formation is specifically due to the repression of MMP-1 expression by GBP-1, and is not affected by the anti-proliferative activity of the helical domain of GBP-1. These findings substantiate the role of GBP-1 as a major regulator of the anti-angiogenic response of ECs to ICs.
Created from Fastlane, Scopus look-up
Keywords: Angiogenesis; Collagenase; Inflammation; Invasion; MMP

The helical domain of GBP-1 mediates the inhibition of endothelial cell proliferation by inflammatory cytokines. - Guenzi, Eric; Töpolt, Kristin; Cornali, Emmanuelle; Lubeseder‐Martellato, Clara; Jörg, Anita; Matzen, Kathrin; Zietz, Christian; Kremmer, Elisabeth; Nappi, Filomena; Schwemmle, Martin; Hohenadl, Christine; Barillari, Giovanni; et al. (EMBO Journal, 2001)
Inflammatory cytokines (IC) activate endothelial cell adhesiveness for monocytes and inhibit endothelial cell growth. Here we report the identification of the human guanylate binding protein-1 (GBP-1) as the key and specific mediator of the anti-proliferative effect of IC on endothelial cells. GBP-1 expression was induced by IC, downregulated by angiogenic growth factors, and inversely related to cell proliferation both in vitro in microvascular and macrovascular endothelial cells and in vivo in vessel endothelial cells of Kaposi's sarcoma. Experimental modulation of GBP-1 expression demonstrated that GBP-1 mediates selectively the anti-proliferative effect of IC, without affecting endothelial cell adhesiveness for monocytes. GBP-1 anti-proliferative activity did not affect ERK-1/2 activation, occurred in the absence of apoptosis, was found to be independent of the GTPase activity and isoprenylation of the molecule, but was specifically mediated by the C-terminal helical domain of the protein. These results define GBP-1 as an important tool for dissection of the complex activity of IC on endothelial cells, and detection and specific modulation of the IC-activated non-proliferating phenotype of endothelial cells in vascular diseases.

The large GTPase AtGBPL3 links nuclear envelope formation and morphogenesis to transcriptional repression - Reimann, Theresa; Müdsam, Christina; Schachtler, Christina; Ince, Semra; Sticht, Heinrich; Herrmann, Christian; Stürzl, Michael; Kost, Benedikt (Nature Plants, 2023)
Guanylate binding proteins (GBPs) are prominent regulators of immunity not known to be required for nuclear envelope formation and morphogenesis. Here we identify the Arabidopsis GBP orthologue AtGBPL3 as a lamina component with essential functions in mitotic nuclear envelope reformation, nuclear morphogenesis and transcriptional repression during interphase. AtGBPL3 is preferentially expressed in mitotically active root tips, accumulates at the nuclear envelope and interacts with centromeric chromatin as well as with lamina components transcriptionally repressing pericentromeric chromatin. Reduced expression of AtGBPL3 or associated lamina components similarly altered nuclear morphology and caused overlapping transcriptional deregulation. Investigating the dynamics of AtGBPL3-GFP and other nuclear markers during mitosis (1) revealed that AtGBPL3 accumulation on the surface of daughter nuclei precedes nuclear envelope reformation and (2) uncovered defects in this process in roots of AtGBPL3 mutants, which cause programmed cell death and impair growth. AtGBPL3 functions established by these observations are unique among dynamin-family large GTPases.
CRIS-Team WoS Importer:2023-05-26

The Molecular Mechanism of Polymer Formation of Farnesylated Human Guanylate-binding Protein 1 - Sistemich, Linda; Kutsch, Miriam; Hämisch, Benjamin; Zhang, Ping; Shydlovskyi, Sergii; Britzen-Laurent, Nathalie; Stürzl, Michael; Huber, Klaus; Herrmann, Christian (Journal of Molecular Biology, 2020)
The human guanylate-binding protein 1 (hGBP1) belongs to the dynamin superfamily proteins and represents a key player in the innate immune response. Farnesylation at the C-terminus is required for hGBP1’s activity against microbial pathogens, as well as for its antiproliferative and antitumor activity. The farnesylated hGBP1 (hGBP1fn) retains many characteristics of the extensively studied nonfarnesylated protein and gains additional abilities like binding to lipid membranes and formation of hGBP1fn polymers. These polymers are believed to serve as a protein depot, making the enzyme immediately available to fight the invasion of intracellular pathogens. Here we study the molecular mechanism of hGBP1 polymer formation as it is a crucial state of this enzyme, allowing for a rapid response demanded by the biological function. We employ Förster resonance energy transfer in order to trace intra and intermolecular distance changes of protein domains. Light scattering techniques yield deep insights into the changes in size and shape. The GTP hydrolysis driven cycling between a closed, farnesyl moiety hidden state and an opened, farnesyl moiety exposed state represents the first phase, preparing the molecule for polymerization. Within the second phase of polymer growth, opened hGBP1 molecules can be incorporated in the growing polymer where the opened structure is stabilized, similar to a surfactant molecule in a micelle, pointing the farnesyl moieties into the hydrophobic center and positioning the head groups at the periphery of the polymer. We contribute the molecular mechanism of polymer formation, paving the ground for a detailed understanding of hGBP1 function.
CRIS-Team Scopus Importer:2020-03-17
Keywords: dimer; GBPs; lag phase; large GTPase; polymerization

The Tat protein of human immunodeficiency virus type-1 promotes vascular cell growth and locomotion by engaging the alpha5beta1 and alphavbeta3 integrins and by mobilizing sequestered basic fibroblast growth factor. - Barillari, Giovanni; Sgadari, Cecilia; Fiorelli, V; Samaniego, F; Colombini, S; Manzari, Vittorio; Modesti, A; Nair, B. C.; Cafaro, Aurelio; Stürzl, Michael; Ensoli, Barbara (Blood, 1999)
The Tat protein of human immunodeficiency virus type-1 (HIV-1) has been shown to be released during acute infection of T cells by HIV-1 and to promote angiogenesis and Kaposi's sarcoma (KS) development in infected individuals. In this study, we investigated the molecular mechanisms responsible for the angiogenic effects of Tat. The results shown herein indicate that two different Tat domains cooperate to induce these effects by different pathways. The arginine-glycine-aspartic acid (RGD) sequence present at the carboxyterminal of Tat mediates vascular cell migration and invasion by binding to the alpha5beta1 and alphavbeta3 integrins. This interaction also provides endothelial cells with the adhesion signal they require to grow in response to mitogens. At the same time, the Tat basic sequence retrieves into a soluble form extracellular basic fibroblast growth factor (bFGF) bound to heparan sulfate proteoglycans by competing for heparin-binding sites. This soluble bFGF mediates Tat-induced vascular cell growth. These effects resemble those of extracellular matrix proteins, suggesting that Tat enhances angiogenesis and promotes KS progression by a molecular mimicry of these molecules.

The viral interferon-regulatory factor-3 is required for the survival of KSHV-infected primary effusion lymphoma cells. - Wies, Effi; Mori, Yasuko; Hahn, Alexander; Kremmer, Elisabeth; Stürzl, Michael; Fleckenstein, Bernhard; Neipel, Frank (Blood, 2008)
Human herpesvirus-8 (HHV-8), also known as Kaposi sarcoma-associated herpesvirus (KSHV), is etiologically linked to primary effusion lymphoma (PEL). At least 10 KSHV-encoded proteins with potential roles in KSHV-associated neoplasia have been identified. However, with few exceptions, these putative oncogenes were analyzed in heterologous systems only using overexpression of single genes. Thus, the pathogenetic relevance of most of these putative oncogenes remains essentially unclear. We used RNA interference (RNAi) to knock down the expression of several KSHV genes in cultured PEL cells carrying the KSHV genome. The viral interferon-regulatory factor-3 (vIRF-3) was found to be required for proliferation and survival of cultured PEL cells. Knock-down of vIRF-3 expression by various RNAi approaches unequivocally resulted in reduced proliferation and increased activity of caspase-3 and/or caspase-7. Thus, vIRF-3 can be seen as a bona fide oncogene of KSHV-associated lymphoma. Surprisingly, although the related Epstein-Barr virus (EBV) is usually sufficient to immortalize human B lymphocytes, silencing of vIRF-3 reduced the viability of both EBV(-) and EBV(+) PEL cells. This suggests that KSHV is the driving force in the pathogenesis of PEL.

Transcriptional activation of endogenous retroviral sequences in human epidermal keratinocytes by UVB irradiation. - Hohenadl, Christine; Germaier, Herbert; Walchner, Monika; Hagenhofer, Manuela; Herrmann, Martin; Stürzl, Michael; Kind, Peter; Hehlmann, Ruediger; Erfle, Volker; Leib-Mösch, Christine (Journal of Investigative Dermatology, 1999)
Ultraviolet radiation is a pathogenic factor in various diseases, e. g., autoimmune disorders such as lupus erythematosus. On the other hand, endogenous retroviruses are discussed as etiologic agents in lupus erythematosus. Therefore, we investigated the influence of ultraviolet irradiation on expression of human endogenous retroviral sequences and human endogenous retroviral sequence promoter-driven transcription of cellular genes using human epidermal keratinocytes as a model system. First, conserved sequences of endogenous retroviral pol genes were amplified from cellular mRNA by reverse transcriptase polymerase chain reaction with degenerate oligonucleotide primers. Polymerase chain reaction products were hybridized in a reverse dot blot hybridization assay to a representative number of distinct cloned human endogenous retroviral pol fragments. Using this method, we could show that irradiation with 30 mJ per cm2 ultraviolet B activates transcription of various endogenous retroviral pol sequences in primary epidermal keratinocytes as well as in a spontaneously immortalized keratinocyte cell line (HaCaT). Interestingly, some of these sequences were found to be closely related to pol sequences of human endogenous retroviral sequences which have been shown to be expressed in autoimmune patients. Analysis of human endogenous retroviral pol expression in vivo using skin biopsies of lupus erythematosus patients revealed similar activation patterns. In a second approach, ultraviolet B- induced chimeric transcripts were isolated which are initiated by human endogenous retroviral promoters and proceed into cellular sequences using a newly established modified differential display polymerase chain reaction technique. The activation of human endogenous retroviral sequence transcription by ultraviolet B may contribute to the pathogenesis of lupus erythematosus, where inappropriate antigenic presentation of ultraviolet B-induced viral and cellular proteins could stimulate autoantibody production.
Keywords: autoantigens; differential display polymerase chain reaction; lupus erythematosus; reverse dot blot hybridization

Transcription pattern of human herpesvirus 8 open reading frame K3 in primary effusion lymphoma and Kaposi's sarcoma. - Rimessi, Paola; Bonaccorsi, Angela; Stürzl, Michael; Fabris, Marina; Brocca-Cofano, Egidio; Caputo, Antonella; Melucci-Vigo, Gianna; Falchi, Mario; Cafaro, Aurelio; Cassai, Enzo; Ensoli, Barbara; Monini, Paolo (Journal of Virology, 2001)
Human herpesvirus 8 (HHV-8) is found in immunoblastic B cells of patients with multicentric Castleman's disease (MCD) and, predominantly in a latent form, in primary effusion lymphoma (PEL) cells and Kaposi's sarcoma (KS) spindle cells. Recent studies have shown that upon reactivation, HHV-8 expresses factors that downregulate major histocompatibility class I proteins and coactivation molecules and that may enable productively infected cells to escape cytotoxic T lymphocytes and natural killer cell responses. One of these viral factors is encoded by open reading frame (ORF) K3. Here we show that in PEL cells, ORF K3 is expressed through viral transcripts that are induced very early upon virus reactivation, including bicistronic RNA molecules containing coding sequences from viral ORFs K3 and 70. Specifically, we found that a bicistronic transcript was expressed in the absence of de novo protein synthesis, thereby identifying a novel HHV-8 immediate-early gene product. Several features of the RNA molecules encoding the K3 product, including multiple transcriptional start sites, multiple donor splicing sites, and potential alternative ATG usage, suggest that there exists a finely tuned modulation of ORF K3 expression. By contrast, ORF K3 transcripts are not detected in the majority of cells present in KS lesions that are latently infected by the virus, suggesting that there are other, as-yet-unknown mechanisms of immune evasion for infected KS spindle cells. Nevertheless, because HHV-8 viremia precedes the development of KS lesions and is associated with the recrudescence of MCD symptoms, the prompt expression of ORF K3 in productively infected circulating cells may be important for virus pathogenesis. Thus, molecules targeting host or viral factors that activate ORF K3 expression or inactivate the biological functions of the K3 product should be exploited for the prevention or treatment of HHV-8-associated diseases in at-risk individuals.

Tumor-associated fibroblasts isolated from colorectal cancer tissues exhibit increased ICAM-1 expression and affinity for monocytes - Schellerer, Vera; Langheinrich, Melanie; Hohenberger, Werner; Croner, Roland S.; Merkel, Susanne; Rau, Tilman; Stürzl, Michael; Naschberger, Elisabeth (Oncology Reports, 2014)
Progression of colorectal cancer (CRC) is strongly associated with inflammation and other desmoplastic reactions in the tumor cell-surrounding tissue. We successfully isolated fibroblasts from the desmoplastic stroma of human CRC specimens and uninvolved colon tissue of patients treated surgically for CRC and investigated potential functional capacities. All of the isolated fibroblasts were vimentin-positive and CK-20/CD45-negative confirming the fibroblast phenotype. Differential expression patterns were detected between tumor-associated fibroblasts (TAFs) and normal tissue-associated fibroblasts (NAFs) regarding intercellular adhesion molecule-1 (ICAM-1) expression. In 11 of 12 TAF cultures, basal ICAM-1 expression was increased as compared to corresponding NAF cultures (p=0.001). After stimulation of the cultures with interleukin-1?, 8 of the 12 TAF cultures presented higher ICAM-1 levels when compared with the level in the corresponding NAF cultures (p=0.001). Moreover, the adhesive capacity of these cultures for U937 was increased in 8 out of 10 unstimulated and in 10 out of 10 stimulated cultures when TAFs and NAFs were compared. In corresponding tumor tissue sections from the same patients, the amount of ICAM-1-positive fibroblasts was significantly higher than that in the corresponding normal colon mucosa, indicating a tumor-specific effect that was maintained in the isolated cultures. These results indicate that fibroblasts from CRC tissue exhibit an increased affinity for monocytic cells. This increased intercellular interaction may contribute to elongated residence times of monocytes in CRC tissue. Therefore, these isolated fibroblasts are a useful tool for further functional investigation of desmoplastic tissue reactions in CRC.
EVALuna2:6524

Tumor microenvironment-dependent epigenetic imprinting in the vasculature predicts colon cancer outcome - Naschberger, Elisabeth; Fuchs, Maximilian; Dickel, Nicholas; Kunz, Meik; Popp, Bernt; Anchang, Charles Gwellem; Demmler, Richard; Lyu, Yanmin; Uebe, Steffen; Ekici, Arif Bülent; Geppert, Carol-Immanuel; Hartmann, Arndt; et al. (Cancer Communications, 2023)
CRIS-Team Scopus Importer:2023-10-27

Two Years of tranSMART in a University Hospital for Translational Research and Education - Christoph, Jan; Knell, Christian; Naschberger, Elisabeth; Stürzl, Michael; Maier, Christian; Prokosch, Hans-Ulrich; Sedlmayr, Martin (Studies in health technology and informatics, 2017)
For translational research, software platforms such as tranSMART with an integrated view of both clinical and omics data have gained more and more attention in the last years.We wanted to examine the success and failures of tranSMART in the fields of translational research and education by looking at the examples of six use cases at our hospital. We wanted to point out suitable scenarios and user groups as well as still existing challenges and limitations.We sum up the experience we made with our use cases with a focus on lessons learned.tranSMART was successfully established by a bottom-up approach at our university hospital and has been running for more than two years now. It has been used in four translational research projects as well as in education in the context of lectures and bachelor/master theses.tranSMART can be a very useful tool for translational research and education. But it should be used with both care and statistical knowledge to avoid wrong conclusions. Some technical constraints, especially for data modeling, still limit many applications. Version control and data provenance are remaining challenges.
EVALuna2:187

Two years of tranSMART in a university hospital for translational research and education - Christoph, Jan; Knell, Christian; Naschberger, Elisabeth; Stürzl, Michael; Maier, Christian; Prokosch, Hans-Ulrich; Sedlmayr, Martin (Health informatics meets eHealth: Digital insight information-driven health & care; proceedings of the 11th eHealth2017 Conference, 2017)
UnivIS-Import:2018-09-11:Pub.2017.tech.IMMD.infome.twoyea
Keywords: Biomedical research; Medical education; Research personnel; Translational medical research

Unique features of different members of the human guanylate-binding protein family - Tripal, Philipp; Bauer, Michael; Naschberger, Elisabeth; Mörtinger, Thomas; Hohenadl, Christine; Cornali, Emmanuelle; Thurau, Mathias; Stürzl, Michael (Journal of Interferon and Cytokine Research, 2007)
Guanylate-binding proteins (GBPs) are the most abundant cellular proteins expressed in response to interferon-γ (IFN-γ), with seven highly homologous members in humans, termed HuGBP-1 to HuGBP-7. To date, differential features that may indicate differential functions of these proteins have not been described. Here, we investigated the expression and subcellular localization of the different HuGBPs in endothelial cells (EC). IFN-γ, tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β) induced the expression of HuGBP-1, HuGBP-2, and HuGBP-3 at similar high levels. In contrast, expression of HuGBP-4 and HuGBP-5 was robustly induced only by IFN-γ and not by TNF-α and IL-1β. Expression of HuGBP-6 and HuGBP-7 was not detected in EC under the various conditions examined. Investigating subcellular localization of the EC-expressed HuGBPs, HuGBP-1, HuGBP-3, and HuGBP-5 were exclusively detected in the cytoplasm, whereas HuGBP-2 and HuGBP-4 displayed a nucleocytoplasmic distribution. Treatment of the cells with IFN-γ and aluminum fluoride caused rapid enrichment of HuGBP-1 and HuGBP-2 in the Golgi apparatus, as demonstrated by time-lapse microscopy and fluorescence analyses of GFP-tagged HuGBPs. HuGBP-3 and HuGBP-4 were never detected in the Golgi apparatus, whereas HuGBP-5 was constitutively enriched in this cytosolic compartment, irrespective of stimulation. These results assign a characteristic pattern of expression and subcellular localization to each of the HuGBPs, indicating for the first time that these proteins may have different cellular functions. © Mary Ann Liebert, Inc.
Created from Fastlane, Scopus look-up

Usability and Suitability of the Omics-Integrating Analysis Platform tranSMART for Translational Research and Education - Christoph, Jan; Knell, Christian; Boßerhoff, Anja Katrin; Naschberger, Elisabeth; Stürzl, Michael; Rübner, Matthias; Seuß, Hannes; Ruh, Manuel; Prokosch, Hans-Ulrich; Sedlmayr, Brita (Applied Clinical Informatics, 2017)
Platforms like tranSMART assist researchers in analyzing clinical and corresponding omics data. Usability is an important, yet often overlooked, factor affecting the adoption and meaningful use. Analyses on the specific needs of translational researchers and considerations about the application of such platforms for education are rare. The aim of this study was to test whether tranSMART can be used in education and how well medical students and professional researchers can handle it; to identify which kind of translational researchers-in terms of skills, experienced limitations, and available data-can take advantage of tranSMART; and to evaluate the usability and to generate recommendations for improvements. An online-based test has been done by medical students (N = 109) and researchers (N = 26). The test comprised 13 tasks in the context of four typical research scenarios based on experimental and clinical data. A web questionnaire was provided to identify both the needs and the conditions of research as well as to evaluate the system's usability based on the "System Usability Scale" (SUS). Students and researchers were able to handle tranSMART well and coped with most scenarios: cohort identification, data exploration, hypothesis generation, and hypothesis validation were answered with a rate of correctness between 82 and 100%. Of the total, 72.2% of the teaching researchers considered tranSMART suitable for their lessons and 84.6% of the researchers considered the platform useful for their daily work; 65.4% of the researchers named the nonavailability of a platform like tranSMART as a restriction on their research. The usability was rated "acceptable" with a SUS of 70.8. tranSMART is potentially suitable for education purposes and fits most of the needs of translational researchers. Improvements are needed on the presentation of analysis results and on the guidance of users through the analysis, especially to ensure the compliance of the analysis with the requirements of statistical testing.
EVALuna2:195

Validation of the reliability of computational O-GlcNAc prediction - Jochmann, Ramona; Holz, Patrick; Sticht, Heinrich; Stürzl, Michael (Biochimica Et Biophysica Acta-Proteins and Proteomics, 2014)
O-GlcNAcylation is an inducible, highly dynamic and reversible posttranslational modification, which regulates numerous cellular processes such as gene expression, translation, immune reactions, protein degradation, protein-protein interaction, apoptosis, and signal transduction. In contrast to N-linked glycosylation, O-GlcNAcylation does not display a strict amino acid consensus sequence, although serine or threonine residues flanked by proline and valine are preferred sites of O-GlcNAcylation. Based on this information, computational prediction tools of O-GlcNAc sites have been developed. Here, we retrospectively assessed the performance of two available O-GlcNAc prediction programs YinOYang 1.2 server and OGlcNAcScan by comparing their predictions for recently discovered experimentally validated O-GlcNAc sites. Both prediction programs efficiently identified O-GlcNAc sites situated in an environment resembling the consensus sequence P-P-V-[ST]-T-A. However, both prediction programs revealed numerous false negative O-GlcNAc predictions when the site of modification was located in an amino acid sequence differing from the known consensus sequence. By searching for a common sequence motif, we found that O-GlcNAcylation of nucleocytoplasmic proteins preferably occurs at serine and threonine residues flanked downstream by proline and valine and upstream by one to two alanines followed by a stretch of serine and threonine residues. However, O-GlcNAcylation of proteins located in the mitochondria or in the secretory lumen occurs at different sites and does not follow a distinct consensus sequence. Thus, our study indicates the limitations of the presently available computational prediction methods for O-GlcNAc sites and suggests that experimental validation is mandatory. Continuously update and further development of available databases will be the key to improve the performance of O-GlcNAc site prediction.
EVALuna2:15154

Vascular occlusion by neutrophil extracellular traps in COVID-19 - Leppkes, Moritz; Knopf, Jasmin; Naschberger, Elisabeth; Lindemann, Aylin; Singh, Jeeshan; Herrmann, Irmgard; Stürzl, Michael; Staats, Léonie; Mahajan, Aparna; Kremer, Anita; Amann, Kerstin Ute; Evert, Katja; et al. (EBioMedicine, 2020)
Background: Coronavirus induced disease 2019 (COVID-19) can be complicated by severe organ damage leading to dysfunction of the lungs and other organs. The processes that trigger organ damage in COVID-19 are incompletely understood. Methods: Samples were donated from hospitalized patients. Sera, plasma, and autopsy-derived tissue sections were examined employing flow cytometry, enzyme-linked immunosorbent assays, and immunohistochemistry. Patient findings: Here, we show that severe COVID-19 is characterized by a highly pronounced formation of neutrophil extracellular traps (NETs) inside the micro-vessels. Intravascular aggregation of NETs leads to rapid occlusion of the affected vessels, disturbed microcirculation, and organ damage. In severe COVID-19, neutrophil granulocytes are strongly activated and adopt a so-called low-density phenotype, prone to spontaneously form NETs. In accordance, markers indicating NET turnover are consistently increased in COVID-19 and linked to disease severity. Histopathology of the lungs and other organs from COVID-19 patients showed congestions of numerous micro-vessels by aggregated NETs associated with endothelial damage. Interpretation: These data suggest that organ dysfunction in severe COVID-19 is associated with excessive NET formation and vascular damage. Funding: Deutsche Forschungsgemeinschaft (DFG), EU, Volkswagen-Stiftung
CRIS-Team Scopus Importer:2020-08-14
Keywords: Aggregated neutrophil extracellular traps; Coagulopathy; Endothelialitis; Immunothrombosis; SARS-CoV-2

VEGFR2 Signaling Prevents Colorectal Cancer Cell Senescence to Promote Tumorigenesis in Mice With Colitis - Försch, Sebastian; Sperka, Tobias; Lindner, Christina; Taut, Astrid; Rudolph, Karl L.; Breier, Georg; Boxberger, Frank; Rau, Tilman; Hartmann, Arndt; Stürzl, Michael; Wittkopf, Nadine; Haep, Lisa; et al. (Gastroenterology, 2015)
Senescence prevents cellular transformation. We investigated whether vascular endothelial growth factor (VEGF) signaling via its receptor, VEGFR2, regulates senescence and proliferation of tumor cells in mice with colitis-associated cancer (CAC).CAC was induced in VEGFR2(?IEC) mice, which do not express VEGFR2 in the intestinal epithelium, and VEGFR2(fl/fl) mice (controls) by administration of azoxymethane followed by dextran sodium sulfate. Tumor development and inflammation were determined by endoscopy. Colorectal tissues were collected for immunoblot, immunohistochemical, and quantitative polymerase chain reaction analyses. Findings from mouse tissues were confirmed in human HCT116 colorectal cancer cells. We analyzed colorectal tumor samples from patients before and after treatment with bevacizumab.After colitis induction, VEGFR2(?IEC) mice developed significantly fewer tumors than control mice. A greater number of intestinal tumor cells from VEGFR2(?IEC) mice were in senescence than tumor cells from control mice. We found VEGFR2 to activate phosphatidylinositol-4,5-bisphosphate-3-kinase and AKT, resulting in inactivation of p21 in HCT116 cells. Inhibitors of VEGFR2 and AKT induced senescence in HCT116 cells. Tumor cell senescence promoted an anti-tumor immune response by CD8(+) T cells in mice. Patients whose tumor samples showed an increase in the proportion of senescent cells after treatment with bevacizumab had longer progression-free survival than patients in which the proportion of senescent tumor cells did not change before and after treatment.Inhibition of VEGFR2 signaling leads to senescence of human and mouse colorectal cancer cells. VEGFR2 interacts with phosphatidylinositol-4,5-bisphosphate-3-kinase and AKT to inactivate p21. Colorectal tumor senescence and p21 level correlate with patient survival during treatment with bevacizumab.
EVALuna2:1356

Viral FLIP blocks Caspase-8 driven apoptosis in the gut in vivo - Ruder, Barbara; Günther, Claudia; Stürzl, Michael; Neurath, Markus; Cesarman, Ethel; Ballon, Gianna; Becker, Christoph (PLoS ONE, 2020)
A strict cell death control in the intestinal epithelium is indispensable to maintain barrier integrity and homeostasis. In order to achieve a balance between cell proliferation and cell death, a tight regulation of Caspase-8, which is a key player in controlling apoptosis, is required. Caspase-8 activity is regulated by cellular FLIP proteins. These proteins are expressed in different isoforms (cFLIPlong and cFLIPshort) which determine cell death and survival. Interestingly, several viruses encode FLIP proteins, homologous to cFLIPshort, which are described to regulate Caspase-8 and the host cell death machinery. In the current study a mouse model was generated to show the impact of viral FLIP (vFLIP) from Kaposi's Sarcoma-associated Herpesvirus (KSHV)/ Human Herpesvirus-8 (HHV-8) on cell death regulation in the gut. Our results demonstrate that expression of vFlip in intestinal epithelial cells suppressed cFlip expression, but protected mice from lethality, tissue damage and excessive apoptotic cell death induced by genetic cFlip deletion. Finally, our model shows that vFlip expression decreases cFlip mediated Caspase-8 activation in intestinal epithelial cells. In conclusion, our data suggests that viral FLIP neutralizes and compensates for cellular FLIP, efficiently counteracting host cell death induction and facilitating further propagation in the host organism.
CRIS-Team Scopus Importer:2020-02-11

Viral inhibitor of apoptosis vFLIP/K13 protects endothelial cells against superoxide-induced cell death - Thurau, Mathias; Marquardt, Gaby; Britzen-Laurent, Nathalie; Weinlaender, Kristina; Naschberger, Elisabeth; Jochmann, Ramona; Alkharsah, Khaled R.; Schulz, Thomas F.; Thome, Margot; Neipel, Frank; Stürzl, Michael (Journal of Virology, 2009)
Human herpesvirus 8 (HHV-8) is the etiological agent of Kaposi's sarcoma (KS). HHV-8 encodes an antiapoptotic viral Fas-associated death domain-like interleukin-1β-converting enzyme-inhibitory protein (vFLIP/K13). The antiapoptotic activity of vFLIP/K13 has been attributed to an inhibition of caspase 8 activation and more recently to its capability to induce the expression of antiapoptotic proteins via activation of NF-κB. Our study provides the first proteome-wide analysis of the effect of vFLIP/K13 on cellular-protein expression. Using comparative proteome analysis, we identified manganese superoxide dismutase (MnSOD), a mitochondrial antioxidant and an important antiapoptotic enzyme, as the protein most strongly upregulated by vFLIP/K13 in endothelial cells. MnSOD expression was also upregulated in endothelial cells upon infection with HHV-8. Microarray analysis confirmed that MnSOD is also upregulated at the RNA level, though the differential expression at the RNA level was much lower (5.6-fold) than at the protein level (25.1-fold). The induction of MnSOD expression was dependent on vFLIP/K13-mediated activation of NF-κB, occurred in a cell-intrinsic manner, and was correlated with decreased intracellular superoxide accumulation and increased resistance of endothelial cells to superoxide-induced death. The upregulation of MnSOD expression by vFLIP/K13 may support the survival of HHV-8-infected cells in the inflammatory microenvironment in KS. Copyright © 2009, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up

β6-integrin serves as a novel serum tumor marker for colorectal carcinoma - Bengs, Susan; Becker, Eugenia; Busenhart, Philipp; Spalinger, Marianne R.; Raselli, Tina; Kasper, Stephanie; Lang, Silvia; Atrott, Kirstin; Mamie, Celine; Vavricka, Stephan R.; von Boehmer, Lotta; Knuth, Alexander; et al. (International Journal of Cancer, 2019)
Colorectal cancer (CRC) is one of the leading causes of cancer-related deaths worldwide and the need for novel biomarkers and therapeutic strategies to improve diagnosis and surveillance is obvious. This study aims to identify β6-integrin (ITGB6) as a novel serum tumor marker for diagnosis, prognosis, and surveillance of CRC. ITGB6 serum levels were validated in retro- and prospective CRC patient cohorts. ITGB6 serum levels were analyzed by ELISA. Using an initial cohort of 60 CRC patients, we found that ITGB6 is present in the serum of CRC, but not in non-CRC control patients. A cut-off of ≥2 ng/mL ITGB6 reveals 100% specificity for the presence of metastatic CRC. In an enlarged study cohort of 269 CRC patients, ITGB6 predicted the onset of metastatic disease and was associated with poor prognosis. Those data were confirmed in an independent, prospective cohort consisting of 40 CRC patients. To investigate whether ITGB6 can also be used for tumor surveillance, serum ITGB6-levels were assessed in 26 CRC patients, pre- and post-surgery, as well as during follow-up visits. After complete tumor resection, ITGB6 serum levels declined completely. During follow-up, a new rise in ITGB6 serum levels indicated tumor recurrence or the onset of new metastasis as confirmed by CT scan. ITGB6 was more accurate for prognosis of advanced CRC and for tumor surveillance as the established marker carcinoembryonic antigen (CEA). Our findings identify ITGB6 as a novel serum marker for diagnosis, prognosis, and surveillance of advanced CRC. This might essentially contribute to an optimized patient care.
CRIS-Team Scopus Importer:2019-06-18
Keywords: colorectal cancer; ITGB6; metastasis; serum tumor marker; surveillance; therapy response